Integrating UAV-derived enhanced disease detection index and texture features for monitoring southern corn rust severity - Yanan Wei; Qing Li; Jia Yin; Dalei Hao; Renan Caldas Umburanas; Yongyuan Gao; Weijian Yu; Zhixiong Li; Yachang He; Guanyu Qiao; Yu Zhang; Carlos Camino; et al. (Computers and Electronics in Agriculture, 2026)

Seismic response of an offshore jacket-type HVSR station in liquefiable seabed using a modified SANISAND model - Wen-Jie Ren; Ling-Yu Xu; Dong Cai; Ye-Jun Sun; Jun Wang; Chen Wang; Zheng-Hai Sha; Feng-Xue Jin; Wei-Yun Chen (Soil Dynamics and Earthquake Engineering, 2026)

Antifungal activity and mechanism of 2-Fluoroadenine against Botrytis cinerea in postharvest tomato fruit - Liu Yang; Yan-Ze Wang; Ya-Ya Lei; Hui-Wen Wang; Yu-Chen Sun; Shao-Yong Zhang; Zhi-Jun Zhang; Xiong-Fei Luo; Ying-Qian Liu (Postharvest Biology and Technology, 2026)

Guaiane sesquiterpenes from Lindera glauca: isolation, structural elucidation, and hepatoprotective effect - Lan-Lan Nie; Xin-Yu Sun; Qing Shi; Ya-Nan Duan; Jia-Yun Yang; Jin-Chang Huang; Xin-Wen Zhang; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2026)

In situ sludge reduction induced by graphene oxide: Mechanistic insights into metabolic uncoupling, maintenance energy and cryptic growth - Yaodong Wu; Yiqi Sun; Rui Yu; Yanan Cui; Fan Yang; Jun Li; Zehao Zhang (Bioresource Technology, 2026)

Chemical constituents from Gerbera delavayi and their chemotaxonomic significance - Ming-yue Chen; Li Jiang; Yu-shuang Wen; Ying-jie Xu; Lin Tian; Jia Sun; Yong-jun Li (Biochemical Systematics and Ecology, 2026)

Screening optimum reference genes for quantitative real-time polymerase chain reaction analysis in invasive apple snail, Pomacea canaliculata under different conditions - Ya-Wen Chang; Han-Di Long; Ran Wei; Zhen-Jun Sun; Guo-Xian Zha; Cheng-Dong Wu; Hong-Fang Xie; Jie Hu; Yu-Zhou Du (Molecular Biology Reports, 2026)

Conceptual design and neutronic-thermal–hydraulic analysis of a 1 MWth helium-cooled ultra-high-temperature space reactor - Baihui Jiang; Jing Zhao; Qian Sun; Yu Ji; Jun Sun; Lei Shi (Annals of Nuclear Energy, 2026)

Regional contrasts in phytoplankton communities and organic carbon pools: Hydrographic forcing and zooplankton grazing in the Cosmonaut and Cooperation Seas - Cuiting Li; Dong Li; Jun Zhao; Ji Hu; Xinliang Wang; Guijun Guo; Jianming Pan; Bin Wu; Peisong Yu; Weiping Sun; Guanbei Wu; Haifeng Zhang; et al. (Marine Pollution Bulletin, 2026)

Bypassing surface state limitations on modified hematite photoanodes via two-electron thiol coupling for stable photoelectrochemical disulfide synthesis - Xuekai Zhang; Xueli Sun; Xin Jia; Yuqian Wang; Fengxiang Yu; Guohao Pang; Xinning Shi; Jun Zhong; Jingran Xiao (Chemical Engineering Journal, 2026)

Lignin-first depolymerization of softwood over a NiCu/TiO2 catalyst for the sustainable production of dihydroconiferyl alcohol - Peng Zhu; Yu-Xin Zhang; Qiang Wang; Guo-Hui Cheng; Jun-Li Ren; Ling-Ping Xiao; Run-Cang Sun (Bioresource Technology, 2026)

L-proline enhances growth performance, digestive function and stress resistance of Chinese mitten crab (Eriocheir sinensis) larvae in high salinity-alkalinity rearing water - Cheng-yi Weng; Yu-xuan Zhao; An-jun Xiang; Yu-hai You; Huan Ma; Zhi-qiang Liu; Jian-yang Sun; Meng-jie Zhao; Chen Zheng; Yu-chen Chen; Yong-xu Cheng; Xiao-zhen Yang (Aquaculture, 2026)

Corrigendum to “A case study of Lepiota brunneoincarnata poisoning with endoscopic nasobiliary drainage in Shandong, China” [Toxicon 161C (2019) 12-16] - Jian Sun; Hong-Shun Zhang; Hai-Jiao Li; Yi-Zhe Zhang; Qian He; Jun-Jia Lu; Yu Yin; Cheng-Ye Sun (Toxicon, 2026)

Projected depletion of high mountain Asia glaciers by 2100: linking mass loss to asynchronous peak runoff - Muhammad Mannan Afzal; Fuming Xie; Yu Zhu; Adeel Ahmad Nadeem; Fazli Hameed; Yi Luo; Tandong Yao; Fubao Sun; Xin Wang; Qiao Liu; Jyoti Karki; Jun Zhou; et al. (Journal of Hydrology, 2026)

Predicting soil-water partition coefficients of PFAS using machine learning: Model development, interpretation, and validation - Yue Zhou; Hao Chen; Xi Wang; Jun Huang; Jing Wei; Liman Wei; Yu Wang; Hongwen Sun (Environmental Pollution, 2026)

Overcoming bacterial fouling: Self-cleaning CNTs-PEI/Cu-ZnIn2S4 membranes for sustained water disinfection - Yuan Gao; Jiaqi Sun; Pei-Lin Gao; Qi Zhao; Xinyi Yu; Yujie Song; Jun Hu; Dan Wang; Zhi-Gang Shen; Ze-Hai Xu; Hua Sheng; Zhong-Ting Hu (Chemical Engineering Journal, 2026)

Rapid aerobic sludge granulation by short-term in-situ chitosan dosing: Performance, mechanism and microbial response - Fengfan Yu; Ruirui Wang; Yanhang Wang; Mengjie Qian; Jintao Sun; Jinwen Song; Jinte Zou; Jun Li (Bioresource Technology, 2026)

A versatile near-infrared fluorescent probe for Zn2+ detection in food and biological matrices - Tianjiao Hou; Chunlin Fan; Hong Deng; Yifei Sun; Wenjun Miao; Chunyuan Hou; Yu Zhang; Jun Luo; Xuan Shen (Analytica Chimica Acta, 2026)

Occurrence and risk assessment of pesticide residues, heavy metals, and mycotoxins in green and roasted coffee beans distributed in the Republic of Korea - Su-Jeong Hwang; Young-hee Kwon; Hye-sun Hwang; Ye-jee Byun; Hye-Jun Kim; Ji-Hye Kang; Yu-na Jeong; Hee-Soo Koo (Food Additives & Contaminants: Part A, 2026)

Performance degradation of early-age tunnel lattice girder-shotcrete support structures under blasting vibration - Hao-chen Liu; Yi-chen Du; Zhao-shun Jing; Wei-teng Li; Zhi-jian Liu; Yu-chun Mei; Hao-nan Sun; Jun-feng Liu (Transportation Geotechnics, 2026)

Heat transfer performance comparison and mechanism analysis of SCO2 and SCO2/R41 mixture in a double-pipe heat exchanger - Dong Wang; Keyu Sun; Hao Yu; Kangkang Zhang; Yinshuang Tao; Jun Shen (International Journal of Refrigeration, 2026)

Effects of fruit bagging on pesticide fate and fruit quality in peach under mixed-pesticide applications - Jun Yu; Pei Wang; Xiaolong Chen; Xing Sun; Jing Ge; Xiangyang Yu (Food Research International, 2026)

Long-term exposure to air pollution, proteomic aging clocks, and liver-related outcomes in Chinese adults - Yating Huang; Dong Sun; Axing Lv; Jun Lv; Canqing Yu; Dianjianyi Sun; Pei Pei; Ling Yang; Yiping Chen; Huaidong Du; Dan Huang; Xiaoming Yang; et al. (Environmental Research, 2026)

Towards intensified oxidative coupling of methane in engineered non-uniform temperature fields - Xiaoyu Cui; Jincheng Huang; Yu Fu; Jun Zhang; Yuhan Sun (Chemical Engineering Journal, 2026)

Investigation of the regulatory effects of the initial oxidation–reduction potential on lactic acid-producing bacteria in culture and silage fermentation and its metabolic mechanism - Mengxin Li; Yuanjiang Rong; Qiang Yu; Ya Su; Yulong Xi; Yixi Long; Yixiao Xie; Hong Sun; Jun Hao; Fuyu Yang; Yulong Zheng (Bioresource Technology, 2026)

Gut Limosilactobacillus reuteri-secreted Components Mitigate Susceptibility to Radiation by Alleviating Oxidative Stress in the Intestinal Epithelium - Hyeyun Kim; Se-Hui Lee; Sun Park; Dongju Seo; Jung-Soo Suh; Yeeun Yang; Jaewan Jeon; Ji Young Kim; Seong-Jun Cho; Jiyoung Yu; Kyunggon Kim; Kwang-Sun Kim; et al. (Probiotics and Antimicrobial Proteins, 2026)

Retraction notice to “PBAT/PLA humic acid biodegradable film applied on solar greenhouse tomato plants increased lycopene and decreased total acid contents” [Sci. Total Environ. 871 (2023) 162077] - Lu Lu; Ying Han; Jiayin Wang; Jing Xu; Yansu Li; Mintao Sun; Fujian Zhao; Chaoxing He; Yujun Sun; Yijia Wang; Pengfei Huang; Xianchang Yu; et al. (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Revealing scale-dependent imbalance between landscape ecological risk and ecosystem services: Multi-scale analysis and driving mechanisms - Yanchao Sun; Wei Wu; Zhe Li; Kai Li; Yufan Wu; Yu Xin; Jun Cai (Journal of Environmental Management, 2026)

Mobile self-assembled membranes: A novel strategy for boosting light hydrocarbon separation efficiency - Yanan Jia; Zixuan Huang; Minglong Wang; Zhi Li; Hongyi Yu; Jun Xu; Bei Liu; Mingjun Deng; Jingming Li; Kun Li; Mingke Yang; Ruihang Zhang; et al. (Chemical Engineering Journal, 2026)

Surfactant-enhanced microbial regulation of bituminous coal for improved CO2 adsorption: Interfacial and structural mechanisms - Xin Yi; Hua Gong; Jun Deng; Zujin Bai; Yu Zhang; Yuwei Wang; Wenbin Sun; Shuangyu Tian (Chemical Engineering Journal, 2026)

Tensile strain engineering of LSCF@SDC heterointerfaces for synergistically boosting catalytic activity and suppressing Sr segregation in solid oxide cells - Miao Zhang; Hengbo Yin; Bozheng Yu; Jiakun Sun; Wei Han; Liuzhen Bian; Linzhi Wang; Chaoyi Wang; Jun Peng; Shengli An (Chemical Engineering Journal, 2026)

Erratum to “Simultaneous enhanced nitrogen removal and energy recovery in sediment microbial fuel cells using pyrite as anode filler for low C/N ratio wastewater treatment” [Bioresour. Technol. 451 (2026) 134515] - Yun Zheng; An-Qi Wang; Ming-Kun Yu; Xin Sun; Han-Qi Xiang; Chao Wang; Xiao-Yu Ding; Qiu-Jun Wang; Jun Zhou; Ping Wei; Xiao-Yu Yong (Bioresource Technology, 2026)

Differential Wound Healing Potential of Tonsil Parenchymal and Epithelial Mesenchymal Stromal Cell-Derived Exosomes - Harry Jung; Hyeonsun Kim; Jihyeon Lee; Hyeon Gyeong Kim; Jae Jun Lee; Kyunghyuk Park; Bukyoung Cha; Sang Hyen Yu; Minji Kim; Sun-Wha Im; Ok Joo Lee; Hae Sang Park (Tissue Engineering and Regenerative Medicine, 2026)

Investigation on the density homogenization and swelling pressure evolution of compacted bentonite with technological voids based on friction analysis - Jing Ma; Yong-gui Chen; Yu-jun Cui; Zhao Sun; Wei-min Ye; Qiong Wang (Bulletin of Engineering Geology and the Environment, 2026)

Subduction-controlled Late Triassic rifting along the northern margin of Gondwana - Si-Lin Sun; Jian-Jun Fan; Bo-Chuan Zhang; Jia-Wei Bai; Yang Wang; Jun-Pu Lv; Xin-Yu Hou (International Geology Review, 2026)

DEM modelling of tillered wheat plants with dynamic parameter calibration for high-speed cutting simulation - Kai Sun; Jianqun Yu; Jun Fu; Yajun Yu; Jinwen Zhao; Long Zhou; Yang Wang (Biosystems Engineering, 2026)

Physics-guided adaptive UKF for robust AUV integrated navigation under degraded underwater observations - Yunhong Miao; Xiaojie Liu; Yu Sun; Xiaochen Liu; Chong Shen; Chenguang Wang; Jun Tang; Jun Liu (Ocean Engineering, 2026)

Ginsenoside Rg3 ameliorates di-(2-ethylhexyl) phthalate-induced spermatogenic impairment via attenuating ferroptosis and restoring sertoli cell secretory dysfunction - Xu-Fei Gao; Nan Ma; Yu-Zhuo Zhang; Jing Zhang; Zhi Liu; Hong-Yan Zhu; Xiao-Jie Gong; Yin-Shi Sun; Di Qu; Jun-Nan Hu; Zi Wang; Wei Li (Journal of Environmental Sciences, 2026)

Radiofrequency-responsive nanogel co-delivering cisplatin and EGCG for enhancing the efficacy of hepatocellular carcinoma interventional therapy by thermoresistance modulation and immune remodeling - Yaowei Bai; Mengqin Guo; Kexin Wang; Yu Lei; Jun Wu; Bo Sun; Wenlong Wu; Xiatong Bai; Yang Su; Ling Li; Yanbing Zhao; Chuansheng Zheng; et al. (Chemical Engineering Journal, 2026)

Simultaneous enhanced nitrogen removal and energy recovery in sediment microbial fuel cells using pyrite as anode filler for low C/N ratio wastewater treatment - Yun Zheng; An-Qi Wang; Ming-Kun Yu; Xin Sun; Han-Qi Xiang; Chao Wang; Xiao-Yu Ding; Qiu-Jun Wang; Jun Zhou; Ping Wei; Xiao-Yu Yong (Bioresource Technology, 2026)

Habitat and phenology dynamics of Potamogeton crispus in a north China shallow lake: patterns and drivers - Yuping Dong; Quanzhou Yu; Jun Song; Leigang Sun; Yuguo Gao; Tianquan Liang; Qingxin Tang; Zhenguo Niu (Aquatic Sciences, 2026)

Climate Controls Cold‐ But Not Warm‐Adapted Sphagnum Distribution and Carbon Sink Capacity - Si‐Nan Wang; Jun‐Xiao Ma; Håkan Rydin; Azim Mallik; Zicheng Yu; Meng Wang; Zhongqiu Sun; Zhao‐Jun Bu (Global Change Biology, 2026)
Despite the critical role of Sphagnum mosses in carbon (C) sequestration, it remains unclear how climate governs their distribution and C sink function. To address this, a reciprocal transplant experiment was performed over 2 years in two peatlands in the Changbai Mountains, utilizing moss monolith mesocosms from low‐elevation ( S. imbricatum ), high‐elevation ( S. fuscum ), and wide‐elevation‐range ( S. magellanicum ) Sphagnum species. We found that when low‐elevation Sphagnum populations were transplanted upward, both the non‐structural carbohydrates (NSC) content and photosystem II efficiency (Φ PSII ) increased, with concomitant reduced ecosystem respiration (ER) and enhanced C sequestration at high elevation. In contrast, for high‐elevation populations, downward transplant significantly weakened gross primary productivity (GPP), primarily by reducing Sphagnum photosynthesis and physiological performance, accompanied by slightly enhanced peat decomposition, ultimately suppressing net ecosystem productivity (NEP) by more than 50%. These results indicate that the 4°C temperature difference associated with the elevational gradient does not restrict the upward distribution of warm‐adapted S. imbricatum and S. magellanicum populations, but it severely restricts the downward distribution of cold‐adapted S. fuscum and S. magellanicum populations. Altered vegetation composition and microbial community coincided with NEP changes in ex‐situ transplants. Our study demonstrates that geographical origin, rather than genetic divergence, strongly affects the short‐term performance of Sphagnum under both cooling and warming conditions. Climate thus controls the distribution and C sink capacity of cold‐ but not warm‐adapted Sphagnum , highlighting the vulnerability of cold‐adapted Sphagnum to warming.

Non-uniform gradient depressurization strategy for balancing heat transfer and gas production in Dual-Gas Co-Production systems - Xian Sun; Hang Zheng; Hui Yang; Fu-Jun Cheng; Zhen Pan; Wen-Chen Han; Hao-Xiang Sun; Yang Yu; Ling-Ban Wang; Chang-Yu Sun (Fuel, 2026)

Ferroelectric field gating-assisted thermoelectric energy conversion - Ji Young Park; Sun-Woo Kim; Byoungjin Yoon; Youngbo Shim; Do-Heon Kim; Seong Wook Cho; Jun Chen; Young Hun Jeong; Sangwoo Ryu; Hak Ki Yu; Zhong Lin Wang; Hyesung Park; et al. (Chemical Engineering Journal, 2026)

Non-contact effects of the parasitoid Sclerodermus guani on its two cerambycid host species - Yu-jun Kong; Yong-hao Nan; Hui-quan Sun; Ke Wei; Jian-rong Wei (BioControl, 2026)

A Mechanistic Framework Integrating Renal QSP-PK-PD and Machine Learning for Baseline-Informed Stratification of Diuretic Resistance - Jialiang Zhou; Vingyou Lou; Yixin Zhao; Linxiu Tang; Zihan Hu; Jiaqi Sun; Jun Chen; Peng Cheng; Yu Cheng; Hua He (The AAPS Journal, 2026)

Response of offshore wind turbine monopile-liquefiable seabed-seawater coupled system to vertical and horizontal seismic excitations - Chen Wang; Jia-Jia Xu; Ye-Jun Sun; Jun Wang; Fei Cai; Dong Cai; Zheng-Hai Sha; Feng-Xue Jin; Ling-Yu Xu (Frontiers in Marine Science, 2026)
A comprehensive understanding of the underlying mechanisms governing offshore wind turbine (OWT) response in liquefiable seabeds during seismic events remains incomplete, particularly with respect to vertical ground motion components and tripartite seawater-structure-soil interaction dynamics. A 3D integrated monopile-seabed-seawater model for a monitored 6.45-MW OWT is developed, featuring acoustic elements for seawater hydrodynamics, advanced constitutive models for liquefaction and material damping, and coupled vertical-horizontal seismic input. The dynamic characteristic of the OWT is rigorously validated through ​continuous vibration acceleration monitoring. Key findings reveal that: (1) Increasing monopile embedment depth in non-liquefied soil layers effectively mitigates liquefaction-induced residual lateral displacements; (2) Monopile vertical displacement amplitude depends critically on both seismic input frequency and the phase difference between horizontal/vertical peak ground accelerations; (3) Seawater presence restrains monopile displacements, while neglecting seabed-seawater coupling leads to underestimated excess pore water pressure (EPWP) buildup in shallow seabed layers during seismic events; (4) Vertical seismic motion dominates seawater’s influence on OWT seismic response by coupling with hydrodynamic pressure to amplify the EPWP changes in liquefiable seabeds. The results demonstrate that comprehensive consideration of coupled vertical seismic excitation and fluid-soil-structure interaction is essential for accurate liquefaction assessment of OWT foundations.

Hybrid Encoding and Adaptive Guidance for Enhanced Single-Cell Multi-omics Clustering - Jing Li; Hong Wang; Jiafeng Yu; Cheng Liang; Xingtang Zhao; Jun Zhao; Yanshen Sun (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Mechanisms and control strategies of shrimp melanosis during storage: A review - Duanquan Lin; Qian Hong; Kai-Yuan Cao; Shu-Jun Hong; Yu-Lei Chen; Le-Chang Sun; Min-Jie Cao (Food Bioscience, 2026)

Atrazine increases hepatic inflammation and injury via endoplasmic reticulum (ER) stress mediated excessive formation of mitochondria-associated membranes (MAMs) and activation of the cGAS-STING pathway - Zi-Jun Sun; Guan-Yue Shan; Hui Wan; Yu-Xin Zhang; Zhi-Cheng Gao; Wen-Na Shi; Lei Lv; Wei-Qun Yan; Hai-Jun Li (Environmental Pollution, 2026)

Building a yeast cell factory for green biomanufacturing of (R)-(+)-γ-decalactone: A natural peach-like aroma compound - Yizi Yu; Kaifeng Wang; Tao Sun; Shushu Li; Ying Zhou; Mei-Li Sun; Lu Lin; Rodrigo Ledesma-Amaro; Xiao-Jun Ji (Chemical Engineering Journal, 2026)

Fine mapping of the TdHLS gene controlling hairy leaf sheath from wild emmer wheat - Nannan Liu; Wenxin Wei; Junna Sun; Zuhuan Yang; Wei Pan; Xiaoming Xie; Jiazheng Yu; Jiarui Zhang; Boyuan Zhang; Weilong Guo; Yinghui Li; Qixin Sun; et al. (Theoretical and Applied Genetics, 2026)

Endoplasmic Reticulum Stress in the Keratinocytes Contributes to Chronic Itch by Activation of Lipocalin 2/MC4R/TRPV1 Pathway - Wei Ge; Yu Feng; Li Zhang; Qian-Liang Wang; Cheng-Wei Zhang; Zhi-Hong Wang; Guo-Kun Zhou; Shi-Yu Sun; Xiu-Hua Miao; Tong Liu; Bin Wu; Jun Yan (Neuroscience Bulletin, 2026)

Quasi-static and transient unloading laws and rock failure characteristics under true triaxial test - Jun Zhou; Guangming Zhao; Xianrui Meng; Chonyan Liu; Wensong Xu; Meilu Yu; Huaiqian Liu; Jinshan Sun; Lixiang Xie (Bulletin of Engineering Geology and the Environment, 2026)

Colletotrichum aenigma causes anthracnose disease of Ficus carica L. in China - Yu-kun Qi; Wen-zhang Liu; Feng-ying Han; Wen-cheng Zhu; Shi-jun Sun; Qing-hai Wang; Ling-xi Zhou (Crop Protection, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Five new prenylated flavonoids derivatives from Dysosma versipellis and their DPPH radical scavenging activity - Meng Zhang; Hong-Yun Bai; Ling-Yu Ye; Xiao-Ke Zheng; Meng Li; Hui Chen; Jing-Ke Zhang; Zhi-You Hao; Shen Liang; Yan-Jun Sun; Wei-Sheng Feng (Phytochemistry Letters, 2026)

Structural optimization of natural plant products: Construction and insecticidal activities study of eugenol's derivatives - Wen Zhang; Xiao-Han Zhang; Li-Hong Sun; Cheng-Yuan Liu; Wen-Hui Zhang; Yi-Wen Huang; Jun-Long Wang; Ji Zhang; Jun-Yu Liang (Pesticide Biochemistry and Physiology, 2026)

The F-box protein ZmFBK1 facilitates autophagy-mediated degradation of maize NLR protein Rp1-D21 to suppress the hypersensitive response - Chang-Xiao Tang; Shi-Jun Ma; Qi-Dong Ge; Yang Sun; Tong-Tong Liu; Man Yang; Zi-Xuan Kang; Yu-Chen Dai; Xuan Zhang; Xueman Liu; Yanyong Cao; Guan-Feng Wang (Molecular Plant, 2026)

Effects of hot air pretreatment on digestibility and quality of steamed bread - Yuze Jia; Jun-Hu Cheng; Xiangwei Tang; Xucong Yu; Da-Wen Sun (Food Chemistry, 2026)

Viscosity-sensitive molecular rotors derived from cyclic chalcone for dual applications: Food monitoring and two-photon fluorescence lifetime imaging - Jun-Yu Luan; Hai-Jiao Sun; Xiao-Hui Wang; Xue-Bo Zhao; Kun-Peng Wang; Ying Fang; Zhi-Qiang Hu (Food Chemistry, 2026)

Methylprednisolone attenuates tendon adhesion via modulating the eIF3a-TGF-β1 Axis in tenocytes and CCS-ROS-NLRP3 Axis in macrophages - Peng Jun Xu; Ya Xin Gu; Jia Yu Shi; Qian Qian Yang; Minrui Ji; Jie Sun; Fei Ju; Yan Xue; Chang Liu; Xu Hao Ji; Junxi Lu; Bo Zhang; et al. (Chemical Engineering Journal, 2026)

Integrated metallurgical process for direct preparation of high-entropy-doped LiMn Fe1-PO4 cathode materials from iron-rich manganese slag - Ding-hao Le; Qing Wen; Chao Sun; Yu-jin Chen; Pei-yao Li; Jie-xi Wang; Jia-feng Zhang; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2026)

Improving rice cooking and eating quality: Panicle nitrogen fertilizer modifies amylopectin structure and amylopectin-protein interactions in post-ripening - Zongkui Chen; Xinrui Li; Yue Huang; Xiangyu Xu; Jinghan Cao; Jiayue Wang; Ziyou Yu; Wenqi Yuan; Zhixin Li; Jingsha Tang; Zhonglin Wang; Zhiyuan Yang; et al. (Carbohydrate Polymers, 2026)

N-Carbon Coated Mn-MoOx Nanocomposite for Efficient Adsorption of Rhodamine B - Denglin Zhu; Sizhan Shu; Chenqi Zhao; Jun Sun; Qiaoshun Chen; Jiani Wang; Qian Ling; Yuxiang Yao; Hao Yu; Shengyang Ou; Pingfan Wu (Water, Air, & Soil Pollution, 2026)

Fine mapping and candidate gene dissection of the wheat powdery mildew resistance gene PmPBDH - Yuli Jin; Jiatong Li; Delin Li; Ningning Yu; Ya Zhao; Bo Wang; Jun Guo; Jiadong Zhang; Guantong Pan; Yaoxue Li; Yintao Dai; Nina Sun; et al. (Theoretical and Applied Genetics, 2026)

Population pharmacokinetics of rivaroxaban after transjugular intrahepatic portosystemic shunt - Min Jia; Yiming Chai; Yuan Gao; Changyou Jing; Kunlei Zhu; Tong Zhu; Liang Wang; Aili Sun; Jun Yang; Yanqiu Zhu; Yingmei Feng; Yu Cao; et al. (European Journal of Clinical Pharmacology, 2026)
Purpose Rivaroxaban, a new direct oral anticoagulant (DOAC), has demonstrated better efficacy and safety than traditional anticoagulants. Individualized anticoagulation is crucial in patients with a transjugular intrahepatic portosystemic shunt (TIPS) and portal vein hypercoagulability to avoid stent thrombosis. As TIPS shunts portal blood directly into the systemic circulation and may substantially affect the first-pass extraction/distribution of direct oral anticoagulants, no population prospective pharmacokinetic studies have been published in patients undergoing TIPS placement so far. The goal of this study was to establish a PopPK model for rivaroxaban in post-TIPS patients, investigate clinical covariate effects on PK, and provide an optimized dosing regimen. Methods In this single-centre prospective study, 39 adult patients underwent TIPS and received rivaroxaban 5 or 10 mg once daily thereafter. Population PK analysis was conducted in NONMEM with 131 plasma concentrations available from 38 evaluable patients (median age: 56 years; median body weight: 63.8 kg). Parameterized model was then applied to simulate steady-state exposure of 5, 7.5, 10, and 15 mg once daily regimen. Results The final PopPK model was based on a one-compartment with sequential zero-order followed by first-order absorption kinetics, and included the effects of an absorption lag time and linear elimination. The apparent clearance and volume of distribution were 7.48 L/h and 4.75 L, respectively. Based on patient-specific simulations of 38 subjects, at the 5 mg/day dose, an exposure within predefined limits was potentially preserved in 96.7% of the cases vs. 62.5% for the 10 mg/day (thresholds: AUC ss,24 ≤ 1.77 mg·h/L and C max, ss ≤ 140 µg/L). This trend was confirmed by Monte-Carlo simulations in 1,000 virtual patients and suggests TDM when the higher dosage is given. Conclusions This PopPK model provides an initial characterisation of rivaroxaban disposition in post-TIPS patients and reveals a markedly reduced apparent V/F relative to non-TIPS populations. The 5 mg once-daily regimen is generally safe, while the 10 mg dose may be considered with therapeutic drug monitoring to account for substantial inter-individual pharmacokinetic variability in post-TIPS patients. Trial registration Chinese Clinical Trial Registry, ChiCTR (ChiCTR2300073784); registered 20 July 2023.

MnO2-resistant ABTS spectrophotometry for trace permanganate - Chenyu Tang; Jianying Wu; Yao Huang; Jing Zou; Xuewei Yu; Bo Sun; Zhongda Yan; Haoqiang Tan; Qingfeng Cheng; Jun Ma (ENGINEERING Environment, 2026)

Paleoproterozoic granite chronology, geochemical characterization, and geological significance in the Longdu region of northeastern Zambia - Yu-Xuan Wu; A-Lei Gu; Jun-Ping Ren; Ling-An Bai; Li-Bo Zuo; Hong-Wei Sun; Shi Xing; Zi-Jiang Liu (International Geology Review, 2026)

Exposure to traffic-related air pollution and the risk of premature rupture of membranes: a cohort analysis of the Korean CHildren’s ENvironmental health Study (Ko-CHENS) - Dong-Wook Lee; Kyung A. Lee; Jongmin Oh; Hwan-Cheol Kim; Sanghwan Song; Yun-Chul Hong; Eunhee Ha; Suejin Kim; Choonghee Park; Sanghwan Song; Jueun Lee; Huibyeol Park; et al. (Environmental Science and Pollution Research, 2026)

A novel nature-assisted bipolar membrane electrodialysis strategy for hypersaline wastewater treatment: Desalination and green resource recovery pathway expansion - Yanbo Liu; Xiaomeng Liu; Xinhao Sun; Yifei Wu; Viacheslav A. Arlyapov; Wei Zuo; Yu Tian; Jun Zhang (Water Research, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Environmental aquatic chemistry in the Research Center for Eco-Environmental Sciences: Efforts for cleaner water - Gang Liu; Meng Sun; Weijun Zhang; Deyin Hou; Hong Zhang; Yaohui Bai; Wei An; Chao Liu; Wenzheng Yu; Tao Zhang; Fubo Luan; Jinmiao Zha; et al. (Journal of Environmental Sciences, 2026)

Responses of a harmful algal bloom-causing dinoflagellate Karenia mikimotoi to elevated temperature and high N:P ratio - Xiang Ye; Wen-Jing Sun; Wei-Ping Zhang; Yang Zhou; Shuo-Yu Zhang; Can-Jun Cai; Shu-Feng Zhang; Jae-Seong Lee; Minghua Wang; Da-Zhi Wang (Harmful Algae, 2026)

Early evolution of the Meso-Tethys Ocean: Constraints from Permo-Triassic flysch deposits - Si-Lin Sun; Jian-Jun Fan; Bo-Chuan Zhang; Jia-Wei Bai; Xin-Yu Hou; Yang Wang; Li-Qiang Zhang (Gondwana Research, 2026)

GaAs/GaN-based self-powered catalytic systems driven by tribovoltaic effect enable efficient degradation of azo dyes - Meng-Nan Liu; Yan-Xin Wu; Yu-Tong Sun; Xu Li; Ru Li; Jun Zhang; Yun-Ze Long (Chemical Engineering Journal, 2026)

Multi-energy complementary optimization for low-carbon public buildings with thermal comfort and time-of-use electricity constraints: life-cycle cost-benefit and global sensitivity analysis - Ya Sun; Yu-Jie Hu; Yao Tao; Bao-Jun Tang (Building and Environment, 2026)

Contrasting size responses of loricate ciliates to long-term warming: agglutinated forms decrease while hyaline forms increase - Yunfan Zhang; Wenhua Bian; Hanyue Chen; Wuchang Zhang; Chaofeng Wang; Jichen Qiu; Xiaoxia Sun; Jun Lin; Ying Yu; Meiping Feng; Bingzhang Chen (Marine Biology, 2026)

Screening for resistance to three soil-borne diseases and profiling genetic diversity of 30 peanut genotypes - Xiang Yin; Chun Jiao Jiang; Xiao Zhou; Hao Jie Sun; Guang Di Yuan; Xiu Zhen Wang; Ming Jun Zhang; Feng Xu; Chuan Tang Wang; Jing Yu; Zhongliang Su (Genetic Resources and Crop Evolution, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

CYP genetic polymorphism, and CYP3A inducers and inhibitors regulate apatinib metabolism: Consequences for drug exposure and toxicity risks - Zhe Wang; Le-hao Jin; Ni-hong Pang; Jun-er Xu; Xiao-yu Xu; Wei Sun; Xiao-dan Zhang; Jian-chang Qian (Toxicology and Applied Pharmacology, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Organic molecule functionalization of Cu single-atom catalysts for enhanced electrocatalytic CO2 reduction to methane - Yihai Wu; Zhenchao Xu; Jianglan Chen; Hongyu Li; Yu Fu; Yuhan Sun; Jun Zhang (Journal of Environmental Chemical Engineering, 2026)

Imidazolyl ionic liquid-based hypercrosslinked polymers as adsorbents for reversible capture of iodine - Xiaomeng Su; Ming Zhao; Liqiu Sun; Yue Yu; Jianjun Wang; Liyan Wang; Jun Li; Dan Wang; Liying Qi; Kuo Zhang; Zhichun Shi (Journal of Environmental Chemical Engineering, 2026)

Mechanism of fructose and ammonium sulfate preference regulation in yellow Monascus pigment production: a metabolomic and proteomic study - Xianjin Liu; Wei Zou; Bin Xie; Yufan Zhang; Haolan Han; Xiang Yu; Jun Liu; Yiwen Sun; Yuanliang Hu; Yanli Feng (Food Bioscience, 2026)

Synergistic engineering of a whole-cell catalyst immobilized on bimetallic CaZn-MOF for efficient PET Depolymerization - Yun-kang Chang; Xiao-huan Liu; Nan-Li; Jun-li Jin; Hai-tong Sun; Shuo Li; Fei-fei Zhang; Yu-xuan Song; Xin-hong Yu; Qi-zhi Cao; Fei Liu; Na Xu; et al. (Chemical Engineering Journal, 2026)

Catalytic hairpin assembly-assisted dual-enhanced SERS satellite nanocomplex for ultrasensitive detection of lipopolysaccharides in injection samples - Chan Huang; Xiuying Li; Xuan Zeng; Lingzhi Chen; Huabin Zhang; Xinjie Guo; Yiqun Chang; Wenshi Huang; Yichu Nie; Tianen Zhou; Jiaqi Yu; Jun Xu; et al. (Chemical Engineering Journal, 2026)

Dynamics of sulfate reduction regulate arsenic mobilization and speciation in paddy soils in response to root exudates - Guo-Hao Zhang; Hong-Yan Wang; Jun-Jie Lin; Guo-Xin Sun; Zheng Chen; Zhi-Guo Yu (Plant and Soil, 2026)

Microinterface effects of catalytic materials on PMS/PDS-mediated degradation of organic pollutants: Mechanistic insights, structural influences, and enhancement strategies - Yifan Chen; Jingyi Sun; Bingjie Yan; Yihe Wang; Zhengda Lin; Wei Zuo; Yu Tian; Jun Zhang (Water Research, 2026)

Anthropogenic forcing drives centennial-scale phytoplankton productivity dynamics in the East China Sea revealed by biomarker records - Yanfang Guo; Fei Yu; Yi Yang; Yushan Gao; Meiqi Shen; Chao Gao; Xiaoxia Lü; Dazhi Wang; Jun Sun (Water Research, 2026)

Neolithic genomes reveal long distance interactions in agropastoral border zone of Yan Mountain Region - Daxuan Zhang; Bing Sun; Fajun Li; Xue Zhao; Zhanhu Zhao; Jun Li; Shizhu Gao; Yu Li; Qiankun Quan; Natalia Berdnikova; Ivan Berdnikov; Shan Chen; et al. (Science Bulletin, 2026)

Spatial and seasonal variation in bioturbation potential of Macrobenthic communities in Bohai Bay - Yifeng Shi; Wenzhe Xu; Rui Gu; Wenxin Zhou; Guicheng Zhang; Yu Guo; Yiyan Guo; Jun Sun (Progress in Oceanography, 2026)

The integument esterase LbEST-inte17 confers malathion tolerance via a non-metabolic mechanism in Liposcelis bostrychophila (Psocoptera: Liposcelididae) - Sheng-Yuan Sun; Ming Ni; Peng-Yu Guo; Wei Zhao; Dan-Dan Wei; Jin-Jun Wang (Pesticide Biochemistry and Physiology, 2026)

Long-term ozone exposure and risks of diabetes and hypertension: Mediated by inflammatory, lipid and oxidative stress biomarkers in a prospective cohort - Yishu Yang; Hongyue Sun; Zhuohan Jiang; Mengfan Yan; Huajie Yang; Zinuo Wang; Honglu Zhang; Xueli Yang; Fang Hou; Pei Yu; Ling Zhang; Zhiwei Sun; et al. (Journal of Hazardous Materials, 2026)

Synergistic Fe-N3 and Fe2O3 structures for high-valent metal-oxo species generation and enhanced tetracycline degradation in Fe-N-C/PMS systems - Weichen Zhu; Wei Zuo; Yu Tian; Hong Qi; Pu Wang; Jun Zhang; Lipin Li; Wei Zhan; Huihang Sun (Journal of Hazardous Materials, 2026)

Efficient nitrogen removal in nitrite-dependent anaerobic methane oxidation biofilms and associated nitrogen and sulfur transformation pathways - Zhi-Cheng Zhao; Guo-Jun Xie; Xin Tan; Lu-Yao Liu; Cheng-Cheng Dang; Xiao-Wei Wang; Xuan Wang; Xin-Yu Wan; Ya-Song Chen; Wan Sun; Nan-Qi Ren (Chemical Engineering Journal, 2026)

Study on deformation and failure characteristics of jointed surrounding rock using a physical model composed by interlooking blocks - Bing-jun Sun; Wei-teng Li; Yu-chun Mei; Xian-feng Yin; Yang Li; Ting-chun Li (Bulletin of Engineering Geology and the Environment, 2026)

A novel deep learning system for STEMI prognostic prediction from multi-sequence cardiac magnetic resonance - Yifan Chen; Meng Jiang; Chao Xia; Hang Zhao; Panpan Ke; Sheng Chen; Heng Ge; Keran Li; Xu Wang; Yufei Wang; Yezi Chai; Qiming Liu; et al. (Science Bulletin, 2025)

Effects of exogenous GR24 on the growth and gene expression of maize seedlings under drought stress - Ziyan Yu; Anqi Su; Yuqi Zhang; Wenbo Chai; Xiao Wei; Yuxian Yang; Wenhui Rao; Yan Zou; Youyang Qin; Zeyuan Liang; Yang Zhao; Jun Wang; et al. (Phytochemistry, 2025)

Seismic behavior of a jacket-type offshore substation with inclined pile foundations on liquefiable seabed - Ling-Yu Xu; Qiang Ma; Bin Li; Ye-Jun Sun; Jun Wang; Guo-Xing Chen; Fei Cai (Ocean Engineering, 2025)

Cradle-to-gate carbon footprint of industrial-scale fermentative production of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH) - Hsien-Tse Chen; Yu-Hsiang He; Pei-Yi Lin; Wei-Shu Huang; Kaarmukhilnilavan R. Srinivasan; Jun-You You; Pei-Yu Sun; Allen H. Hu; Penjit Srinophakun; Maythee Saisriyoot; Si-Yu Li (Journal of Cleaner Production, 2025)

Associations of pre- and postnatal levels of three heavy metals with visual impairment in 3-year-old children - Dajeong Ham; Sung Yeon Kim; Sanghyuk Bae; Suejin Kim; Choonghee Park; Sanghwan Song; Jueun Lee; Huibyeol Park; JungHeum Jo; A-Ra Jung; Seung Do Yu; Hyun Jeong Kim; et al. (Environmental Research, 2025)

Phosphorized metal-organic framework with superior capacitive deionization performance - Xinjuan Liu; Jun Xu; Bengbeng Yu; Yaoyu Chen; Chenchen Zhang; Yujie Wei; Yong Zhou; Lei Li; Taiqiang Chen; Yuhua Xue; Likun Pan; Chang Q. Sun (Desalination, 2025)

Dynamic adaptive dual-network synergy achieves high strength and high toughness in polyurea for impact resistance - Ke Guo; Jingyuan Liu; Jia Qu; Qi Liu; Jing Yu; Rongrong Chen; Jiahui Zhu; Gaohui Sun; Peili Liu; Jun Wang (Chemical Engineering Journal, 2025)

Vapor-phase polymerization of polypyrrole in PVA hydrogels for enhanced electrical conductivity in multimodal sensing applications - Ruobing Tian; Yu Zhang; Yuanna Sun; Jiahao Liu; Xueming Tang; Jinlong Gao; Guixin Lv; Yan Jiang; Jun Fu (Chemical Engineering Journal, 2025)

Machine learning-guided multi-objective optimization for selective lithium extraction and valuable metal reuse from spent lithium-ion batteries - Jiayi Qu; Boge Zhang; Ronghua Jiang; Jun Huang; Mingjie Li; Sicheng Zheng; Wenjing Yu; Pengxin Sun; Yihua Xu; Yanping Hou; Hongfei Lin; Zebin Yu (Chemical Engineering Journal, 2025)

Corrigendum to “Tunability of Pickering particle features of whey protein isolate via remodeling partial unfolding during ultrasonication-assisted complexation with chitosan/chitooligosaccharide” [Carbohydrate Polymers 325 (2024) 121583] - Hongmei Yu; Yuanrong Zheng; Changyu Zhou; Lianliang Liu; Libin Wang; Jinxuan Cao; Yangyin Sun; Jun He; Daodong Pan; Zhendong Cai; Qiang Xia (Carbohydrate Polymers, 2025)

Migrasome: a novel insight into unraveling physiological and pathological function - Yu Ye; Jun Zhang; Yue Liu; Xiaochun Sun (Molecular Biology Reports, 2025)

Rapid detection of transgene insertion patterns in living modified Phalaenopsis via inverse PCR and nanopore sequencing validated against Illumina and PacBio sequencing platforms - Yu Kyong Hu; Jun-Kyung Lee; Yong-Gil Shin; Byoung-Eun Min; Ki‐Hong Jung; Chan Hui Lee; Sun-Goo Hwang; Sung Don Lim (Plant Biotechnology Reports, 2025)

Disintegration characteristics, splitting tensile strength and microscopic mechanisms of marine silty soil improved by PAM and CLS - Yin-Lei Sun; Shi-Chen Tu; Zheng-Ping Xiao; Chuan Yu; Xian-Wei Zhang; Ying-Jun Song (Science of The Total Environment, 2025)

Ribonuclease 4 is a pancreatic endogenous β cell proliferation factor - Muxiong Chen; Yaxin Liu; Jun Sun; Wenguang Wang; Zhi Huang; Yinzhen Xiong; Dan Zhou; Hong Yu; Jinghao Sheng; Rongpan Bai; Zhengping Xu (Science Bulletin, 2025)

BmeIF4E2 promotes AcMNPV infection in the silkworm, Bombyx mori, by direct interaction - Xin-Yi Ding; Jiang-Zhi Su; Wen-Jing Yu; Qian-Qian Jiao; Zuo-Min Shao; Ai-Jun Wan; Sheng Qin; Xia Sun; Xue-Yang Wang; Ding-Ding Lü; Mu-Wang Li (Pesticide Biochemistry and Physiology, 2025)

Vibration and noise reduction of underwater gliders with a novel wing integrating flexible cladding and phononic crystals - Mengdi Zhang; Peng Wang; Jun Chen; Xuan Wang; Tongshuai Sun; Yu Song; Yunlong Yin; Kai Xin; Dinghuo Hu; Shaoqiong Yang (Ocean Engineering, 2025)

Long-term organic fertilization reduces cadmium bioavailability via enhanced binding to organic fractions and Fe-bearing minerals - Zhi-Lai Chi; Qiang-Long Hu; Lin Shi; Fu-Sheng Sun; Jun Wang; Guang-Hui Yu (Journal of Hazardous Materials, 2025)

Fe0 drives tetracycline resistance genes reduction and resistance mechanism shift in activated sludge system - Hong Chen; Dong Cheng; Min Sun; Shiyi Zhao; Jun Sheng; Xin Yu; Xianying Li; Gang Xue; Xiaoming Zou (Journal of Environmental Management, 2025)

Associations between prenatal exposure to air pollution and infant growth trajectories in the first two years: Exploring potential sexual dimorphism and sensitive windows - Zhen-Hua Li; Si-Wei Dai; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2025)

Nitrogen-regulated amylose structure and complexation during post-ripening: A key to improving rice cooking and eating quality - Zongkui Chen; Xinrui Li; Wenqi Yuan; Yue Huang; Jiayue Wang; Xiangyu Xu; Xiaomeng Shen; Xuanjun Guo; Ziyou Yu; Zhiyuan Yang; Yongjian Sun; Jun Ma; et al. (Carbohydrate Polymers, 2025)

Revisiting the genesis of Bi-Te-Au-S associations: Implications for the ore-forming processes in gold deposits - Gao-Hua Fan; Jian-Wei Li; Zhan-Ke Li; Xue-Feng Yu; Xiao-Dong Deng; Jin-Hao Liu; Hang-Jin Jiang; Hong-Jun Sun; Tian-Ming Zhang (Chemical Geology, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Enhancing E. coli removal in mesophilic anaerobic digestion: New insights from inoculum comparison and metagenomic analysis - Haipeng Wang; Zetang Chai; Jianrui Li; Hao Sun; Hong-Yu Ren; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Bioresource Technology, 2025)

Unveiling dynamics of microbial communities, species interactions, and ecological assembly during low-temperature-induced sludge bulking in full-scale wastewater treatment systems - Han-Jun Sun; Xian Zhao; Jie Ding; Yu-Qian Wang; Wen-Shuo Wang; Zhi-Hua Feng; Sha Zhao; Liang Wang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2025)

Suppression of OTUD4 protects against myocardial ischemia-reperfusion injury by increasing autophagic flux and inhibiting apoptosis in cardiomyocytes - Xin-xin Sun; Lin Qi; Ming-jun Dai; Fang-lin Lu; Yi-min Xiao; Wei-jin Sun; Yu Zhuang (Journal of Molecular Medicine, 2025)

Wuhapuella caenivorax gen. nov., sp. nov., a Novel Member of the Family Weeksellaceae, a Flocculent Bacteria Isolated from an Urban Sewage Treatment Plant - Yangyang Sun; Qianzhi Wang; Shunda Qiu; Changcui Chen; Siqi Wu; Na Gao; Han Chen; Jun Yu; Chunlei Yang; Hao Li; Shijie Bai; Dongru Qiu; et al. (Current Microbiology, 2025)

The combination of HDACi encapsulated liposomal vaccines with oncolytic peptide QR-KLU induces an immune-mediated abscopal effect for cancer immunotherapy - Tao Sun; Jingjing Du; Yu Lei; Jun Guo; Chuansheng Zheng; Dongyuan Wang (Journal of Pharmaceutical Investigation, 2025)
Purpose Tumor vaccines have been showing a relatively weak response rate in cancer patients. The combination of liposomal cancer vaccines with different kinds of agents could affect different arms of the immune system and/or tumor microenvironment (TME), potentially leading to more satisfactory immune responses. In this paper, we investigated effects of using a combination of liposomal cancer vaccines containing Pam 2 - mucin 1 (MUC1) antigens, αGalCer and pan-histone deacetylase inhibitor (HDACi) SAHA with oncolytic peptide QR-KLU for cancer immunotherapy. Methods The physical properties of the SAHA contained liposomal vaccines was identified such as nanoparticle diameter and polydispersity index, zeta potential. Cell based assays were conducted to evaluate the cell toxicity of SAHA contained liposomal vaccines and lytic peptide QR-KLU. The in vivo assays with B16F10-MUC1 tumor-bearing mouse model were used to evaluate the tumor immune response and anti-cancer effect by the combination therapy of QR-KLU and SAHA contained liposomal vaccines. Results SAHA contained liposomal vaccines showed improved anti-cancer effect than liposomal vaccine alone on B16F10-MUC1 cells. The B16F10-MUC1 cells were sensitive to oncolytic peptide QR-KLU and were killed at low micromolar levels by QR-KLU. In order to test the enhanced tumor immune response by the combination therapy, we intratumorally injected lytic peptide QR-KLU into B16F10-MUC1 tumor-bearing mouse model, and then the mice were sequentially treated with SAHA@liposomal vaccines via intraperitoneal administration. The combined therapy demonstrated greatest reductions in tumor volume and systemic immune response compared with QR-KLU or SAHA@liposomal vaccines monotherapy. We further found the treatment was T-cell dependent, and also resulted in an abscopal effect as demonstrated by the regression of distal non-treated lesions. Conclusion Our research demonstrated that the combination of lytic peptide and SAHA@liposomal vaccines represents a new approach to cancer immunotherapy, which can be considered as a simple and potential method for simple but immunologically effective approach for the development of anti-MUC1 cancer vaccines.

Returning low C/N crop straw to the paddy field can achieve the dual benefits of reduced methane emissions and enhanced yield stability - Chuanhai Shu; Binbin Liu; Yu Li; Qiqi Chen; Leilei Li; Yuanqing Shi; Hongkun Xie; Zhonglin Wang; Qin Liao; Qingyue Cheng; Feijie Li; Na Li; et al. (Agriculture, Ecosystems & Environment, 2025)

Control system for soil microbes detrimental to trees using metabolites derived from algal bloom-causing microorganisms - Byung Sun Yu; Yujun Park; Seohyun Park; Jun-Woo Cho; Kyudong Han (Science of The Total Environment, 2025)

Synergistic enhancement of Pt electrocatalyst stability and activity in hydrogen oxidation reaction by polyoxometalate and carbon dot co-boosting - Fei-Yang Yu; Zhong-Ling Lang; Xian Wang; Jing Sun; Yu-Chen Liu; Hua-Qiao Tan; Jun-Jie Ge; Yang-Guang Li; Zhen-Hui Kang (Science Bulletin, 2025)

Distribution characteristics and influencing factors of chlorophyll a in the Pearl River Estuary and surrounding waters during spring and summer of 2023 - You LE; Yuanliang ZHAO; Xianjie LIU; Yang LU; Jin-Yu Terence YANG; Shuqun SONG; Jun SUN (Regional Studies in Marine Science, 2025)

Multielement conodont apparatus (Cornudina) from the Lower Triassic of China, revealed by high-resolution X-ray microtomography - Wu-Jun Xu; Zuo-Yu Sun; Shuang Liu; Cheng Ji; Hao Lu; Zhao-Liang Ma; Fei-Yang Wu; Shou-Ming Chen; Jian-Dong Huang (Palaeoworld, 2025)

OsSPT38 encodes a novel SUMO E3 ligase that improves rice stress resilience and grain yield - Zi-Sheng Zhang; Zheng-Yi Zhang; Jin-Qiu Xia; Si-Yan Chen; Liang-Qi Sun; Jie Wu; Da-Yu He; Jing-Xian Wang; Qin-Yu Liang; Lei Wang; Ke Ruan; Tian Sang; et al. (Molecular Plant, 2025)

Nighttime warming impedes invasion of Chromolaena odorata into tropical coral islands - Zhangmei Sun; Lingling Zhang; Heng Yu; Yuan Lai; Heng Zhang; Yan Liu; Jun Wang; Yuanwen Kuang (Journal of Environmental Management, 2025)

Synergistic microaerobic bio-decontamination of dimethyl sulfide and elemental mercury in the low-O2 content flue gas by a sulfur-oxidizing membrane biofilm reactor - Han-Biao Yang; Lu-Lu Sun; Xiu-Qin Tan; Yuan Zeng; Yu-Qi Huang; Zhen-Shan Huang; She-Jun Chen; Zai-Shan Wei (Chemical Engineering Journal, 2025)

Modulation of Bi4O5I2 energy band with oxygen vacancy defect engineering to optimize hydroxyl radical generation for photocatalytic sterilization - Tianyi Sun; Yunlei Zhou; Huanshun Yin; Shuqi Gong; Zhengkun Yu; Hanyu Liu; Jiating Cheng; Jun Wang (Chemical Engineering Journal, 2025)

Thermal p-n junctions: a macroscopic thermal diode based on heterogeneous materials - Yue Zhang; Baotong Li; Pengfei Sun; Yu Hou; Jun Hong; Meng Shi; Liang Zeng; Qingfang Liu (Chemical Engineering Journal, 2025)

Hierarchically shortened b-axis ZSM-5 nanosheet endows super catalytic stability for methanol-to-hydrocarbons reaction - Zhan Liu; Ying-Jun He; Zhi-Yi Hu; Jia-Min Lyu; Shen Yu; Yu-Hang Song; Xiao-Qiang Liao; Zhi-Wen Yin; Ming-Hui Sun; Yu-Chun Zhi; Li-Hua Chen; Bao-Lian Su (Chemical Engineering Journal, 2025)

Recycling of sub-continental lithosphere during early ocean spreading revealed by Triassic trachytes in the central Tibetan Plateau - Zong-Yong Yang; Qiang Wang; Jun Wang; Lin Ma; Derek Wyman; Andrew C. Kerr; Xian-Wu Bi; Peng Sun; Xiu-Zheng Zhang; Lu-Lu Hao; Xiao Liu; Chuan-Bing Xu; et al. (Chemical Geology, 2025)

The Acetic Acid Produced by Lactobacillus Species Regulates Immune Function to Alleviate PEDV Infection in Piglets - Ming-Jie Sun; Jun Hong Xing; Qing-Song Yan; Bo-Shi Zou; Ying-Jie Wang; Tian-Ming Niu; Tong Yu; Hai-Bin Huang; Di Zhang; Shu-Min Zhang; Wu-Sheng Sun; Ruo-Nan Zou; et al. (Probiotics and Antimicrobial Proteins, 2025)

In vitro and in vivo assessment of diosmetin-loaded lactoferrin-modified liposomes for brain delivery in intracerebral hemorrhage therapy - Yingjiang Gu; Hanyue Luo; Jun Zhu; Hao Ma; Yang Zhang; Jinshan Xing; Yuzhou Liu; Yu Cai; Wenxia Sun; Pei Luo (Drug Delivery and Translational Research, 2025)

Formation of a DMM-EM2 Mixing Trend in Continental Intraplate Basalts by Variable Degrees of Melting of Hybrid Mantle Controlled by the Lithospheric Lid - Xun Yu; Gang Zeng; Xiao-Jun Wang; Fa-Jun Sun; Hui-Li Zhang (Journal of Earth Science, 2025)

GSDME-dependent astrocyte pyroptosis promotes the progression of neuroinflammation in experimental cerebral malaria - Jun Wang; Qinghao Zhu; Guodong Tong; Kangjie Yu; Jiao Liang; Yuxiao Huang; Yi Wang; Chao Yang; Tong Li; Weilu Liang; Ganze Li; Xiaoran Liu; et al. (Apoptosis, 2025)

Spatial heterogeneity and seasonal succession of phytoplankton community in the Cosmonaut Sea, East Antarctica: driving forces and implications - Guanbei Wu; Dong Li; Jun Zhao; Jianming Pan; Ji Hu; Peisong Yu; Weiping Sun; Haifeng Zhang; Changfeng Zhu; Cuiting Li (Frontiers in Marine Science, 2025)
Understanding the dynamics of the phytoplankton community in the marginal seas of the Southern Ocean is crucial for delineating its role in global carbon cycling. This study investigated spatiotemporal variations in phytoplankton community structure and organic carbon pools in the Cosmonaut Sea, East Antarctica, with an emphasis on spatial heterogeneity and environmental drivers during late austral summer (February). Water samples were collected from 15 stations during the 40th Chinese Antarctic Research Expedition (CHINARE-40, February 2024), and nutrient, pigment, particulate organic carbon (POC), and dissolved organic carbon (DOC) concentrations were quantified. The CHEMTAX analysis revealed that the phytoplankton community was dominated by diatoms (38% ± 16%), dinoflagellates (22% ± 12%), and Prymnesiophyceae Phaeocystis antarctica (12% ± 10%). Diatoms and P. antarctica contributed significantly to POC (r = 0.36, p < 0.01) and DOC (r = 0.69, p < 0.01), respectively. Spatial distribution patterns displayed pronounced heterogeneity; large ice-edge diatoms dominated cold, high-light, and shallow mixed-layer regions, while small pelagic diatoms and dinoflagellates dominated in stratified, nutrient-limited, and low-light environments. Comparative analysis with adjacent Southern Ocean sectors further highlighted how distinct water masses shape niche competition. Furthermore, our results suggest a trend toward phytoplankton miniaturization, with increasing prevalence of dinoflagellates and P. antarctica under projected positive phases of the Southern Annular Mode, potentially diminishing biological carbon pump efficiency and weakening carbon sequestration. Collectively, these findings clarify how the Cosmonaut Sea phytoplankton community responds to environmental variability, providing essential insights into biogeochemical cycling and carbon budget dynamics in the Southern Ocean under climate change.

Nematicidal activity of 3-indoleacetonitrile against Bursaphelenchus xylophilus: Inhibition of development and reproduction through induction of excessive reactive oxygen species - Shichao Yu; Tong Mao; Yongchao Shang; Jun Sun; Peicheng Liu; Li Hua Jin (Pesticide Biochemistry and Physiology, 2025)

Enantiomeric meroterpenoids from Rhododendron capitatum and their anti-inflammatory activity - Hang Xie; Qing Shi; Yu-Meng Miao; Xin-Yu Sun; Jin-Chang Huang; Chun Lei; Qing Mu; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Uncertainty pattern and an integration strategy in flood susceptibility modeling: Limited sample size - Jun Liu; Xueqiang Zhao; Yangbo Chen; Huaizhang Sun; Yu Gu; Shichao Xu (Journal of Hydrology, 2025)

Reducing environment and enhanced productivity controlled the accumulation of organic matter in the Upper Yangtze Basin, South China during the Late Ordovician-Early Silurian - Yan-Jun Bao; Yuan-Yuan Sun; Di Zhang; Jian-Fei Yan; Yu-Peng Men; Wei Sun; Jia-Shan Lin; You-Li Wan; Jian-Wei Kang; Wen-Hua Wang; Qiangba Zhaxi (Journal of Asian Earth Sciences, 2025)

Red/black phosphorus heterostructure anchored on graphene for lithium-sulfur batteries with accelerated conversion kinetics and improved long-term stability - Xinxin Dong; Xinyu Chen; Xin Tong; Guoqing Liu; Hao Yu; Wei Liu; Huihui Li; Jun Sun; Xiaoyu Gu; Sheng Zhang (Chemical Engineering Journal, 2025)

ERRα Knockout Promotes M2 Microglial Polarization and Inhibits Ferroptosis in Sepsis-Associated Brain Dysfunction - Jun Jin; Yang Dong; Yu Huang; Lili Wu; Lei Yu; Yuanyuan Sun; Qingshan Zhou; Hai-Yan Yin; Wan-Jie Gu (Molecular Neurobiology, 2025)
Sepsis-associated brain dysfunction (SABD) is a critical neurological complication with high mortality, yet its pathogenesis remains poorly understood. This study investigated the role of estrogen-related receptor α (ERRα) in SABD pathogenesis using ERRα knockout (KO) mice and cecal ligation and puncture (CLP) models. We found that ERRα KO mice exhibited improved survival rates, milder neurological symptoms, reduced pro-inflammatory cytokine production (TNF-α, IL-1β), and increased anti-inflammatory cytokine (IL-10) levels compared to wild-type controls. Additionally, ERRα deficiency promoted microglial M2 polarization and attenuated ferroptosis, as evidenced by decreased iron accumulation, reduced lipid peroxidation, and normalized mitochondrial morphology. Mechanistically, these protective effects were mediated through inhibition of the NF-κB signaling pathway. In vitro studies with ERRα knockdown in LPS-stimulated BV2 microglia confirmed these findings. Our results suggest that ERRα as a critical regulator of microglial function in SABD through coordinated control of inflammatory responses, polarization states, and ferroptosis, suggesting that targeting ERRα may represent a promising therapeutic strategy for SABD treatment.

Cold Stress Memory Genes in Cucumber are Widely Regulated by “Hit-and-Run” Model - Qinghua Di; Lu Liu; Yan Yan; Mengdi Zhou; Jun Wang; Chaoxing He; Yansu Li; Xianchang Yu; Mintao Sun (Journal of Plant Growth Regulation, 2025)

Vanadyl Acetylacetonate and Berberine Synergistically Ameliorate Diabetes-induced Vascular Dysfunction and Reduce Endothelial Toxicity through ERK and Akt Regulation - Jun Sun; Ningning Shi; Xiaomin Zhang; Jiameng Dong; Lili Zhao; Tianzi Wei; Chunting Guan; Xiang Li; Xihan Yu; Congcong Hou (Biological Trace Element Research, 2025)

Architectural features and antioxidative biofunctionality of a novel pectin from Angelica keiskei Koidz - Si-Ru Chen; Yu-Ru Zhu; Li-Ting He; Hong-Liang Sun; Jing Huang; Yan-Zi Yang; Hua-Jun Zhao; Bo Yang; Meng-Xia Yan (Natural Product Research, 2025)

Study on the deformation and failure control of massive surrounding rock in shallow buried tunnel based on a new simulation technology - Bing-Jun Sun; Wei-Teng Li; Yang Li; Yu-Chun Mei; Ting-Chun Li (Tunnelling and Underground Space Technology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Fast degradation of chlorinated volatile organic compounds using soluble cobalt complexes - Maryam Mirabediny; Tsz Tin Yu; Jun Sun; Matthew Lee; Denis M O’Carroll; Michael J. Manefield; Biswanath Das; Naresh Kumar (Process Safety and Environmental Protection, 2025)

Preparation of powdery reduced iron from high-phosphorus iron ore: Effects of raw material particle size combination - Hongda Xu; Xiaojin Wen; Jue Kou; Jun Zhang; Kexin Yu; Tichang Sun (Minerals Engineering, 2025)

Machine learning based prediction by PlantCdMiner and experimental validation of cadmium-responsive genes in plants - Chaoqun Xu; Ling Sun; Lu-Dan Zhang; Ze-Jun Guo; Ji-Cheng Wang; Li-Han Zhuang; Dong-Na Ma; Ling-Yu Song; Jing Li; Qian-Su Ding; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

Engineering ultrasmall red fluorescent carbon dots for targeted blood-brain barrier crossing, oxidative stress alleviation and mitochondrial repair in cerebral ischemia-reperfusion injury treatment - Jiacheng Xu; Xidong Wu; Xinyue Cao; Shuoxun Chen; Maohua Chen; Zhiwei Li; Hui Hu; Liang Chen; Lipeng Gao; Yu Chen; Jun Sun (Chemical Engineering Journal, 2025)

Self-exfoliation of cellulose nanofibrils via one-pot pseudosolvent swelling/esterification for functional pellicular materials - Yugao Ding; Xinyi Yu; Zhen Zhang; Wang Sun; Jun You; Nisha He; Guofu Zhou (Carbohydrate Polymers, 2025)

N6-methyladenosine reader YTHDF3-mediated CEBPA translation maintains genomic stability and stem cell function to prevent liver injury - Yaxu Liang; Weiwei Yu; Haifeng Sun; Dayu Wang; Zhibo Wang; Hailing Shi; Yang Cao; Zijie Zhang; Jun Liu; Zhongyu Zou; Jiangbo Wei; Tong Wu; et al. (Science China Life Sciences, 2025)

Machine learning strategy secures urban smart drinking water treatment plant through incremental advances - Yu-Qi Wang; Hong-Cheng Wang; Zi-Jie Xiao; Ling-Jun Bu; Jiuling Li; Xiao-Chi Feng; Bin Liang; Wen-Zong Liu; Fei-Yun Sun; Shi-Qing Zhou; Ai-Jie Wang (Water Research, 2025)

Landfill depths alter microbial community structure and ecological assembly by affecting δ13C and organic matter - Yu-Xin Wang; Qing-Yu Liu; Jun-Yan Du; Hao-Qun Sha; Jing Su; Yue Sun; Jing-Ying Mao; Xiao-Song He (Waste Management, 2025)

Meroterpenoids with bicyclic polyprenylated acylphloroglucinol scaffold and anti-inflammatory activity from Hypericum lancasteri - Jin-Qiu You; Yun-Qi Jin; Yu-Meng Miao; Xin-Yu Sun; Jia-Yu Yang; Jin-Chang Huang; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Unraveling the roles of algal extracellular and intracellular organic matters in photosensitized degradation of tetracycline: Insights from triplet excited algal organic matters - Xiaoyuan Zhang; Huiqi Liang; Minxiang Zeng; Shanshan Li; Yu Liu; Qiyuan Sun; Jinfeng Lu; Jun Ma (Journal of Hazardous Materials, 2025)

Companion animals as sources of hazardous critically important antimicrobial-resistant Escherichia coli: Genomic surveillance in Shanghai - Yiwen Chen; Min Li; Bingqing Sun; Luming Xia; Yifei Zhang; Jun Feng; Min Chen; Zile Cheng; Chao Lv; Weiye Chen; Jiewen Huang; Qingtian Li; et al. (Journal of Hazardous Materials, 2025)

Dolphins-inspired antifouling self-healing hydrophilic coatings with hierarchical hydrogen bonds for enhanced durability in antifouling performance based on dynamic poly(urethane-urea) - Yu Guan; Rongrong Chen; Jiahui Zhu; Gaohui Sun; Qi Liu; Jingyuan Liu; Jing Yu; Zailin Yang; Jun Wang (Chemical Engineering Journal, 2025)

Fungal network and plant metabolites drive the assembly of the peanut root microbiome - Chen-Yu Ma; Xiao-Han Wu; Hao-Ming Wang; Xiang-Yu Zhang; Yan-Jun Fei; Shi-Yi Huang; Yi-Bo Wu; Zi-Han Zhao; Hui-Jun Jiang; Kai Sun; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

Cloud Droplet Spectrum Evolution Driven by Aerosol Activation and Vapor Condensation: A Comparative Study of Different Bulk Parameterization Schemes - Jun Zhang; Jiming Sun; Yu Kong; Wei Deng; Wenhao Hu (Advances in Atmospheric Sciences, 2025)

Increased fine roots, exudates and altered rhizospheric functions in the invasive plant Sphagneticola trilobata compared to the native Sphagneticola calendulacea - Tongxi Tian; Yina Yu; Jingjing Yuan; Jiaxin Sun; Zhiyang Li; Xiaomin Zhu; Xiangcheng Wu; Jun Wang; Guangyan Ni (Rhizosphere, 2025)

Deciphering the role of small RNAs in the development of empurpled phenotypes in the Gossypium hirsutum mutant HS2 - Minghua Lv; Ting Deng; Jiahong Cao; Xinyu Zhang; Fangfang Cai; Jun Mei; Dongliang Yu; Yuqiang Sun (Plant Gene, 2025)

Occurrence, source, and ecological impacts of dry depositing aerosol metal elements in the Bohai Bay - Liying Peng; Xudong Cui; Xueou Wang; Yu Guo; Xing Ma; Yujian Wen; Zhi Wang; Yiyan Guo; Jun Sun (Marine Environmental Research, 2025)

Selective salt separation and resource recovery via nanofiltration in coal-to-ethylene glycol wastewater - Zheng-Jun Fu; Bo-Zhi Chen; Kai Yu; Jian-Guo Hu; Pengli Chen; Hui-Qin Zhang; Mei-Ling Liu; Shi-Peng Sun (Journal of Water Process Engineering, 2025)

Novel mechanisms for selenite biotransformation and selenium nanoparticles biogenesis in Acinetobacter sp. SX5 isolated from seleniferous soil - Sheng-Wei Huang; Yuan-yuan Yao; Hua-xu Zhang; Wan-ying Guo; Ming-hui Fang; Hai-bo Wang; Yu-jun Sun; Ming-hao Li (Journal of Hazardous Materials, 2025)

Redox-active ligands for oxygen evolution reactions activity: Modulation of metal valence states in synthesis and accelerated reconstruction by rapid hydrolysis in alkaline electrolytes - Pengxin Sun; Jing Liu; Li Wang; Cheng Wu; Ronghua Jiang; Jun Huang; Yanping Hou; Mingjie Li; Boge Zhang; Zebin Yu (Journal of Environmental Chemical Engineering, 2025)

Fabrication of sweet potato leaf-derived nanocellulose and its influence on the properties and interactions in peanut protein films - Ming-yang Sun; Yu-qi Yang; Qi Gao; Jia-nan Chen; Chong-ting Guo; Miao Yu; Jia-jia Rao; Xue-jun Gu; You-lin Xue (Food Hydrocolloids, 2025)

Metabolic and ecological responses of denitrifying consortia to different carbon source strategies under fluctuating C/N conditions - Rui-Zhe Sun; Yuan Pan; Jun Wang; Tong Gao; Han-Qing Yu; Jin Wang (Environmental Research, 2025)

Adverse associations of pre-pregnancy exposure to PM2.5 and its components with fetal growth alleviated by residential greenness: a prospective cohort study - Si-Wei Dai; Zhen-Hua Li; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Chun-Yong Wang; Xiao-Yu Zhao; Hai-Yang Weng; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Pollution, 2025)

Kinetics and morphology study of hydrate formation from CO2-H2O emulsion in glass beads - Ming-Long Wang; Yi-Fei Sun; Hong-Nan Chen; Jin-Rong Zhong; Dan Rao; Yu Liu; De-Jun Xuan; Bei Liu; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2025)

Solid-state fermentation of distillers grains with Aspergillus pachycristatus for echinocandin B biosynthesis - Jiaxin Tang; Weibing Zhang; Jing Xu; Luyan Sun; Yaqi Dang; Haoyang Li; Liyan Yu; Jing Su; Ting Xue; Rui Guo; Jun Xie; Lei Wang (Bioresource Technology, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Life‐cycle greenhouse gas emissions associated with nuclear power generation in the United States - Jun Hong Clarence Ng; Pradeep Vyawahare; Pahola Thathiana Benavides; Yu Gan; Pingping Sun; Richard Boardman; Jason Marcinkoski; Amgad Elgowainy (Journal of Industrial Ecology, 2025)
Under the 2022 Inflation Reduction Act, tax credits of up to $3/kgH 2 are available to hydrogen producers if they generate emissions at levels below 0.45 kgCO 2 e/kgH 2 , spurring producers to explore how hydrogen production via electrolysis using electricity generated by nuclear power may qualify for such tax credits. With uranium as a primary fuel for nuclear power plants (NPPs) and no on‐site emissions, the upstream emissions associated with nuclear fuel supply chains largely determine the carbon intensity of nuclear energy. Using the GREET (Greenhouse gases, Regulated Emissions, and Energy use in Technologies) model, we evaluated the life‐cycle greenhouse gas (GHG) emissions of uranium production and the use of uranium to generate electricity in light water reactor (LWR) NPPs. We evaluated the process chemicals and energy inputs throughout the nuclear fuel supply chain to identify the major contributors to nuclear fuel cycle GHG emissions. Such emissions are estimated at 3.0 gCO 2 e/kWh at NPPs in the United States. The greatest share of nuclear fuel cycle GHG emissions—comprising 53% of total emissions—are associated with electricity consumption throughout the fuel supply chain. We extended the analysis to include an evaluation of the carbon intensity of H 2 production via electrolysis using nuclear power from LWRs. Finally, we examined the impact of future (2035 and 2050) electricity supply chain scenarios on nuclear fuel cycle GHG emissions. Our analysis revealed a decrease of 33% (2035) and 46% (2050) in the carbon intensity of nuclear electricity relative to current nuclear fuel cycle GHG emissions.

State-of-the-art review on liberation of cathode material in pretreatment recycling of spent lithium-ion battery - Chenye Wang; Ren Tao; Peng Xing; Jun Ni; Zhigen Cun; Shaojun Liu; Xingrui Wang; Yu Dai; Zhibin Long; Zhenhua Sun; Huiquan Li (Resources, Conservation and Recycling, 2025)

Unraveling mechanism of denitrification process for treating low carbon-to-nitrogen ratio wastewater with different zero-valent iron exogenous enhancement strategies - Ze-Tong Feng; Yan Yu; Ying-Jun Sun; Jia-Min Zhou; Xin Ma; Fei Ding; Yi-Liu Zheng; Ren-Cun Jin; Chun-Qiang Shen; Qian-Qian Zhang (Journal of Water Process Engineering, 2025)

The transferrin a signaling pathway mediates uranium-induced hematopoietic dysfunction - Jin Gao; Fajian Luo; Qiu Chen; Na Chen; Jun Wan; Liang Sun; Yiyao Cao; Hong Ren; Yu Tu; Haiwen Huang; Fengmei Cui (Environmental Pollution, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Spirulina (Arthrospira) cultivation in photobioreactors: From biochemistry and physiology to scale up engineering - Guoyu Ma; Qiping Gao; Lu Yuan; Yu Chen; Zhongzhen Cai; Liang Zhang; Jun Hu; Yunjun Wang; Shusong Wu; Yahui Sun (Bioresource Technology, 2025)

Seismic fragility analysis of shield tunnels in liquefiable layered deposits - Ling-Yu Xu; Ju-Ping Xi; Jia-Wei Jiang; Fei Cai; Ye-Jun Sun; Guo-Xing Chen (Soil Dynamics and Earthquake Engineering, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Building the resilient food waste supply chain for the megacity: Based on the Multi-scale Progressive Fusion framework - Tianrui Zhao; Huihang Sun; Yihe Wang; Wei Zhan; Lipin Li; Yanliang Li; Weijia Li; Xiaomi Tang; Shanshan Luo; Xuanlong Shang; Jun Zhang; Yu Tian (Resources, Conservation and Recycling, 2025)

Conodonts suggest a late Spathian (late Early Triassic) age for Thaisaurus chonglakmanii (Reptilia: Ichthyosauromorpha) from Thailand - Si-Yao Ye; Kui Wu; Zuo-Yu Sun; P. Martin Sander; Adun Samathi; Yuan-Yuan Sun; Cheng Ji; Varavudh Suteethorn; Jun Liu (Palaeoworld, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Functional divergence of CAD-like family genes in Saccharum complex under biotic and abiotic stress - Zhu-Qing Wang; Sheng-Ren Sun; Hao-Yu Wang; Zheng-Wang Bi; Hai-Long Chang; Shuo-Hang Zhang; Jun-Lv Chen; Yuan-Xia Qin; Jian-Tao Wu; Wei Zhang; Huan-Ying Xu; San-Ji Gao; et al. (Plant Cell Reports, 2025)

Monthly variations in nutrient utilization along 45°E transect in the Cosmonaut Sea, East Antarctica during austral summer - Xufeng Yang; Dong Li; Jun Zhao; Cai Zhang; Changfeng Zhu; Shunan Cao; Guangfu Luo; Gaojing Fan; Yongming Sun; Ji Hu; Haifeng Zhang; Peisong Yu; et al. (Acta Oceanologica Sinica, 2025)

Sources and distribution characteristics of chromophoric dissolved organic matter in the Cosmonaut Sea and the Cooperation Sea, Antarctica - Ji Hu; Siyou Xue; Bin Zhou; Jun Zhao; Dong Li; Gaojing Fan; Disong Yang; Leilei Zhang; Haifeng Zhang; Peisong Yu; Cai Zhang; Xufeng Yang; et al. (Acta Oceanologica Sinica, 2025)

Spatial dynamics of phytoplankton assemblages and organic carbon stock in the highly productive Amundsen Sea Polynya and adjacent seasonal ice zone - Dong Li; Jun Zhao; Ji Hu; Jianming Pan; Jianfeng He; Yongming Sun; Peisong Yu; Xufeng Yang; Cai Zhang; Haifeng Zhang; Weiping Sun; Gaojing Fan (Acta Oceanologica Sinica, 2025)

A geospatial-based framework for rapid simulation of storm-induced flooding and comprehensive risk assessment leveraging GWDD and fuzzy-SWARA - Hai Sun; Xiaowei Zhang; Jun Wang; Zhimin Li; Qiwei Yu; Xuejing Ruan (Urban Climate, 2025)

Chemosensory protein 8 confers thiamethoxam resistance in Diaphorina citri - Qian Li; Wan-Wei Hu; Ao Fang; Zhuo-Bing Wang; Xiao-Fang Yuan; Yue Sun; Zheng-Hui Zou; Nuo Chen; Tian-Xing Jing; Ying-Xue Liu; Wei Chen; Hai-Zhong Yu; et al. (Pesticide Biochemistry and Physiology, 2025)

Exploring the physical disruptions of anammox granular sludge under propylene glycol stress: Implications for nitrogen removal and long-term stability - Hui-Min Fu; Xiao-Wen Jiang; Cai-Ping Sun; Shi-Jun Li; Xun Weng; Meng-Wen Peng; Peng Yan; Xiao-Wei Xu; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Overcoming the conventional thermodynamic limit of water electrolysis to boost renewable energy storage - Hui Sun; Wen-Tao Bi; Qian He; Li Zhu; Yu-Qing Dong; Fang Li; Zhen-Guo Guo; Jun Ding; Jian-Bo He (Chemical Engineering Journal, 2025)

Endophytic colonization of Phomopsis liquidambaris recruits rhizospheric Ralstonia by inducing acetic acid secretion to facilitate phosphorus uptake by Arachis hypogaea L. in continuously cropped soil - Hui-Jun Jiang; Xiang-Yu Zhang; Chen-Yu Ma; Kai Sun; Xing-Guang Xie; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

Comparative effects of biochars from different feedstocks on the desiccation process of loess - Yao Geng; Pengju Qin; Yu Lu; Yifei Sun; Jun Zhang; Xiaoqiang Dong (Bulletin of Engineering Geology and the Environment, 2025)

Spatial distribution of bacterial communities driven by environmental factors in the sediment of Lateolabrax japonicus ponds - Yu-Min Xu; Zheng Zhu; Wu-Lang Luo; Wei Huang; Jun-Han Liang; Hong-Yan Sun; Qi-Wei Qin (Aquaculture, 2025)

Reducing methane emissions by developing low-fumarate high-ethanol eco-friendly rice - Yunkai Jin; Tong Liu; Jia Hu; Kai Sun; Lihong Xue; Mathilde Bettembourg; Girma Bedada; Pengfu Hou; Peiying Hao; Jintian Tang; Zihong Ye; Chunlin Liu; et al. (Molecular Plant, 2025)

Boosting chlorobenzene oxidation over MIL-101(Cr) derived CrOx catalysts: The stepwise regulation of CrOx clusters and oxygen species by calcination atmospheres - Boqiong Jiang; Jun Liu; Keyan Wei; Hanfeng Lu; Xiaole Weng; Jingyi Han; Yi Zhang; Shaocai Yu; Yuhai Sun (Journal of Hazardous Materials, 2025)

Carbon residue from co-pyrolysis of cartons and plastics: Characteristics, environmental behaviors and applications - Zhipeng Li; Ruochun Zhang; Jun Huang; Dandan Yu; Zhanjun Cheng; Guanyi Chen; Peizhe Sun (Journal of Environmental Management, 2025)

A novel electrochemical sensor based on La-MOF@C60-β-cyclodextrin composite for sensitive detection of dichlorophen in lake and tap water - Yu Xie; Wei Zhou; Jia-Wen Yin; Yi Li; Lin-Li Hou; Li-Min Liu; Li-Jun Liu; Kalle Salminen; Jian-Jun Sun (Journal of Environmental Chemical Engineering, 2025)

Biomonitoring and food surveillance on heavy metals reveal need for food safety in a coastal region - Xin Zhang; Xiaoqian Yang; Xiaoyue Hu; Zhonghua Meng; Zhigang Yu; Zhan Sun; Ying Zhang; Zhifeng Yang; Sha Li; Jia-Sheng Wang; Qiang Jia; Lanzheng Liu; et al. (Food Research International, 2025)

A smartphone-integrated bimetallic ratiometric fluorescent probe for specific visual detection of tetracycline antibiotics in food samples and latent fingerprinting - Yin-Xia Sun; Bo-Tao Ji; Jiang-Hai Chen; Li-Ping Liu; Lu-Lu Gao; Zhe-Peng Deng; Yu Sun; Jian-Jun Wang; Biao Zhao; Jin-Guo Li (Food Chemistry, 2025)

Dynamic evolution of volatile compounds during cold storage of sturgeon fillets analyzed by gas chromatography-ion mobility spectrometry and chemometric methods - Jia-hua Yang; Shan Cui; Mei-jun Sun; Kai Liu; Hao Tao; Dan Zhang; Zi-heng Yan; Chun-yu Kang; Chun-qing Zhao (Food Chemistry, 2025)

Regulation of silanol nests in zeolite to form stable Td-Co(II) species for efficient propane dehydrogenation - Huihui Deng; Baozhen Li; Wenchun Zheng; Qin Sun; Mengjia Zhu; Jun Zuo; Yu Tang; Lizhi Wu; Li Tan (Chemical Engineering Journal, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

The research of nicotinamide and β-arbutin on reducing melanin content in the skin of leopard coral grouper (Plectropomus leopardus) - Zhi Bin Sun; Shi Ying Liu; Xin An Wang; Ai Jun Ma; Zhi Hui Huang; Zhi Feng Liu; Wei Heng Sun; Peng Fei Yan; Dong Hui Gou; Hui Yu Xiao; Hao Zhe Li; Vorathep Muthuwan; et al. (Aquaculture, 2025)

Identifying localized heat zones in urban heat islands from a hill and saddle perspective - Wenbo Yu; Jun Yang; Jiayi Ren; Zhenchao Zhang; Dongqi Sun; Bing Xue; Wei Sun; Xiangming Xiao; Jianhong(Cecilia) Xia; Xueming Li (Sustainable Cities and Society, 2025)

Sex-specific associations between maternal exposure to metal mixtures and fetal growth trajectories: A prospective birth cohort study - Zhen-Hua Li; Cheng-Yang Hu; Si-Wei Dai; Hui-Ya Ma; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Xiu-Jun Zhang (Science of The Total Environment, 2025)

Effects of PM2.5 components on hypertension and diabetes: Assessing the mitigating influence of green spaces - Hongyue Sun; Chengjie Pan; Mengfan Yan; Zhongli Wang; Jiayu He; Honglu Zhang; Ze Yang; Zinuo Wang; Yiqing Wang; Hongyan Liu; Xueli Yang; Fang Hou; et al. (Science of The Total Environment, 2025)

Benzofurans and dibenzofurans from galls on twigs of the endangered Chinese endemic tree Parrotia subaequalis and their inhibitory properties against Staphylococcus aureus and ATP-citrate lyase - Peng-Jun Zhou; Xi-Ying Wu; Ze-Yu Zhao; Yi Zang; Zhong-Shuai Sun; Yue-Ling Li; Na Li; Juan Xiong; Yeun-Mun Choo; Ze-Xin Jin; Jia Li; Jin-Feng Hu (Phytochemistry, 2025)

Research progress of electrospinning in food field: A review - Fa-Lin Sun; Ming-Yue Zhao; Yue Li; Zhi-Ying Li; Xiu-Jun Li; Nuo Wang; Bo-Wen Hu; Hao-Yu Xue; Min Zhao; Jin-Long Tian (Food Hydrocolloids, 2025)

A novel Ag/Bi/Bi2O2CO3 photocatalyst effectively removes antibiotic-resistant bacteria and tetracycline from water under visible light irradiation - Suo Wang; Changyu Li; Huanshun Yin; Bin Gao; Zhengkun Yu; Yunlei Zhou; Jun Wang; Hongxia Xu; Jichun Wu; Yuanyuan Sun (Environmental Research, 2025)

Unlocking long-term stability: Electrolyte additives for suppressing zinc dendrite growth in aqueous zinc metal batteries - Hee Jae Kim; Sun Kim; Jun Ho Yu; Jae-Hong Lim; Hitoshi Yashiro; Seung-Taek Myung (Chemical Engineering Journal, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

The dilemma of single-crystal high-nickel LiNixCoyMn1-x-yO2 (x ≥ 0.9) cathodes: Inhomogeneous delithiation inside and outside the particle - Yue Zou; Dongyan Yu; Yonglin Tang; Yawen Yan; Yu Qiao; Jun Bao; Shi-Gang Sun (Chemical Engineering Journal, 2025)

Kv3.1 Interaction with UBR5 Is Required for Chronic Inflammatory Pain - Ying Zeng; Meng-Lan Sun; Di Liu; Yue Huang; Shan Xie; Ya-Xuan Zhao; Zi-Xuan Wu; Ya Liu; Gan Ma; Ling Xie; Yu-Tao Dang; Ling-Yun Hao; et al. (Molecular Neurobiology, 2025)

Integrating genome-wide association and whole transcriptome analysis to reveal genetic control of grain quality traits in barley - Haiye Luan; Jiajia Gao; Xin Qu; Yu Li; Yuhao Wu; Jun Wang; Shufen Li; Meng Xu; Xiao Xu; Miao Sun; Yinghu Zhang; Huiquan Shen (Euphytica, 2025)

Sea State Parameter Prediction Based on Residual Cross-Attention - Lei Sun; Jun Wang; Zi-Hao Li; Zi-Lu Jiao; Yu-Xiang Ma (Journal of Marine Science and Engineering, 2024)
The combination of onboard estimation and data-driven methods is widely applied for sea state parameter prediction. However, conventional data-driven approaches often exhibit limited adaptability to this task, resulting in suboptimal prediction performance. To enhance prediction accuracy, this study introduces Cross-Attention mechanisms to optimize the task of real-time sea state parameters prediction for maritime operations, innovatively develops a Residual Cross-Attention mechanism, and integrates it into representative networks for sea state parameter prediction. Three benchmark networks were selected, each evaluated under three configurations, without attention, with Cross-Attention, and with Residual Cross-Attention, resulting in a total of nine experimental scenarios for error assessment. The results demonstrate that both Cross-Attention and Residual Cross-Attention reduce prediction error to varying degrees and improve model robustness.

Apoc1 Knockdown Alleviates High Glucose-induced Oxidative Stress and Apoptosis of Renal Tubular Cells by Binding to Clusterin - Liyin Chai; Zhengyang Liu; Jun Zeng; Li Gong; Sha Xiang; Jing Yu; Haili Sun; Chaolin Wen; Fang Wang; Ning Li; Bingbing Shen; Mei Mei (Cell Biochemistry and Biophysics, 2024)

Insight into the effect of potassium amyl xanthate on copper pollution caused by chalcopyrite bio-dissolution - Rui Liao; Jun Wang; Shichao Yu; Xin Sun; Shitong Liu; Baojun Yang; Guanzhou Qiu (Journal of Environmental Management, 2024)

Synergistic antimicrobial potential of essential oil nanoemulsion and ultrasound and application in food industry: A review - Qian-Jun Shen; Jinyue Sun; Jia-Neng Pan; Ting Yu; Wen-Wen Zhou (Innovative Food Science & Emerging Technologies, 2024)

Investigation of the intelligent anti-aging bitumen using microcapsule clean-product secreting waste cooking oil through polyacrylamide-gel in porous-shell structure - Qian Sun; Qin-Yu Xing; Rong-Yue Shao; Jun-Feng Su; Xin-Yu Wang (Fuel, 2024)

Purification, structural identification, in vitro hypoglycemic activity and digestion characteristics of polysaccharides from the flesh and peel of wampee (Clausena lansium) - Jun-ye He; Juan-li Fang; Chong-yang Yu; Xu Zhang; Peng-peng Sun; Yuan-yuan Ren (Food Research International, 2024)

Highly selective capture of lead(II) by a barium-zinc-antimony-oxo cluster-based material: Ion-exchange pathway with single-crystal-to-single-crystal structural transformation - Wei-Yang Wen; Jia-Hua Luo; Hai-Yan Sun; Yu-Wei Ren; Lu Yang; Tian-Yu Pan; Jun-Hao Tang; Wen Ma; Jia-Ting Liu; Bing Hu; Mei-Ling Feng; Xiao-Ying Huang (Chemical Engineering Journal, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Retraction Note: MiR-125 family improves the radiosensitivity of head and neck squamous cell carcinoma - Qi-Wei Wang; Ya-Nan Sun; Li-Jun Tan; Jian-Nan Zhao; Xiao-Jie Zhou; Tian-Jiao Yu; Jiang-Tao Liu (Molecular Biology Reports, 2024)

Host preference and mortality caused by the parasitoid Sclerodermus guani on different cerambycid species - Qun Yu; Shuang Li; Yu-Jun Kong; Zuo-Xiang Sun; Dan-Dan Cao; Jian-Rong Wei (BioControl, 2024)

Biogenic silica dynamics in coastal wetland sediments: A key driver of silicon and carbon biogeochemical cycling - Xiangwei Zhao; Zhaoliang Song; Yuntao Wu; Lukas Van Zwieten; Laodong Guo; Changxun Yu; Zimin Li; Lele Wu; Xiaomin Yang; Xiangbin Ran; Jun Sun; Yuqiu Wei; et al. (Limnology and Oceanography, 2024)
Biogenic silica (biogenic Si) is a bioactive component crucial for the biogeochemical cycling of Si in terrestrial and aquatic ecosystems. Its formation and dissolution dynamics are intricately linked to carbon (C) cycling. However, knowledge about the source, composition, and factors controlling the distribution of biogenic Si in coastal wetland sedimentary environments is still limited. To address this lack of knowledge, we introduced a suite of geometric models for biogenic Si biovolume calculation and investigated biogenic Si assemblages, along with biogenic Si and biogenic Si‐occluded C contents, in sediments from representative coastal wetlands along the west coast of Bohai Bay. Our analysis showed that sedimentary biogenic Si predominantly derived from phytoliths (78.1% ± 5.8%), diatoms (18.2% ± 4.8%), and sponge spicules (3.7% ± 2.9%). Notably, phytolith assemblages were primarily composed of forms derived from the Poaceae family. The biogenic Si‐occluded C content (0.035–1.870 g kg −1 ) within these wetland sediments was consistent across both sites, accounting for 0.97–5.71% of the total organic C pool. Structural equation modeling indicated that total organic C, pH, and amorphous aluminum oxides either directly or indirectly influenced the biogenic Si content in coastal wetlands sediments. These results demonstrate the critical role that biogenic Si plays in the Si biogeochemical cycle and provide valuable information that advances our understanding of the biogeochemical interactions between Si and C in coastal wetland ecosystems.

Corrigendum to “Association of urban green space with metabolic syndrome and the role of air pollution” [Landsc. Urban Plann. 248 (2024) 105100] - Yi Sun; Yunli Chen; Yuanyuan Huang; Yan Luo; LiPing Yan; Sailimai Man; Canqing Yu; Jun Lv; Chuangshi Wang; Jun Wu; Heling Bao; Bo Wang; et al. (Landscape and Urban Planning, 2024)

Catalyst-free regeneration of plasma-activated water via ultrasonic cavitation: Removing aggregation concealment of antibiotic-resistant bacteria with enhanced wastewater sustainability - Zhenyang Hu; Hongwen Xu; Jun Cheng; Huan Zhang; Yali Zhao; Jian Hu; Yingying Sun; Lijun Huang; Weirong Yao; Zhilong Yu; Yunfei Xie (Journal of Hazardous Materials, 2024)

Process exploration of domestication, start-up and rapid recovery strategies for anaerobic digestion of sole corn stover: Methane production efficiency and dominant microbial responses - Haipeng Wang; Hao Sun; Hong-Yu Ren; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Journal of Cleaner Production, 2024)

Tracing potentially toxic elements in button mushroom cultivation and environmental implications: Insights via stable lead (Pb) isotope analysis - Xun Liu; Junjie Yu; Xueping Lu; Manli Yang; Yazhou Liu; Hui Sun; Ying Ni; Guo Lin; Chuansheng Wu; Jun Tang (Journal of Cleaner Production, 2024)

Metagenomic insights into the mechanism of sophorolipid in facilitating co-anaerobic digestion of mushroom residues and cattle manure: Functional microorganisms and metabolic pathway analysis - Zixuan Zhao; Fei Wu; Jian Sun; Lan Jiang; Yiran Zhang; Jun Wang; Zhijiang Shao; Yifan Sun; Zichen Duan; Yu Zhang; Tongtong Bai; Yucheng Liu; et al. (Journal of Environmental Management, 2024)

N-graphyne surrounded Bi2S3/BiOBr composites: In-situ ultrasound-assisted synthesis and superior photocatalytic activity - Xiangzhi Huang; Haohao Chen; Mingxuan Sun; Junjie Zhao; Huanying Teng; Yu Gao; Jun Li; S.W. Lee; J.G. Tang (Fuel, 2024)

Structural characteristics of cell wall pectic polysaccharides from wampee and their decreased binding with pectinase by wampee polyphenol - Jue-jun Zhou; Xu Zhang; Chong-yang Yu; Peng-peng Sun; Yuan-yuan Ren (Food Chemistry, 2024)

Proposing moderate unfolding of interfacial proteins to enhance the techno-functional features of complex microgel particles formed by whey protein-chitooligosaccharide conjugation - Hongmei Yu; Yuanrong Zheng; Kangshuai Lou; Changyu Zhou; Jinxuan Cao; Lihui Du; Yangying Sun; Jun He; Daodong Pan; Zhendong Cai; Qiang Xia (Food Hydrocolloids, 2024)

A polysulfides adsorption strategy through cation-anion interactions for achieving high-safety lithium-sulfur batteries in multiple scenarios - Xinxin Dong; Xin Tong; Weihao Song; Guoqing Liu; Hao Yu; Wei Liu; Jin Niu; Jun Sun; Xiaoyu Gu; Sheng Zhang (Chemical Engineering Journal, 2024)

Construction of PTFE/PI-PI/PANI-PA composite nanofibrous membrane for efficient photothermal membrane distillation and VOCs interception - Jingge Ju; Jun Yu; Tiantian Zhang; Yan Zhang; Yanfei Chen; Jiacheng Han; Ying Sun; Weimin Kang (Chemical Engineering Journal, 2024)

Multi-band compatible camouflage enabled by phase transition modulation of flexible GST films - Jian Wang; Zuoxu Wu; Xiaoyu Sun; Zunqian Tang; Chong Wang; Fangyuan Yu; Zirui Zhao; Jun Mao; Qian Zhang; Feng Cao (Chemical Engineering Journal, 2024)

The CYP3A inducer dexamethasone affects the pharmacokinetics of sunitinib by accelerating its metabolism in rats - Guang-rong Lu; Rui-zhen Wang; Xin-yu Zhao; Jun-er Xu; Cheng-ke Huang; Wei Sun; Rui-jie Chen; Zhe Wang (Chemico-Biological Interactions, 2024)

Uptake of zinc from the soil to the wheat grain: Nonlinear process prediction based on artificial neural network and geochemical data - Kai-Ning Lv; Yong Huang; Guo-Li Yuan; Yu-Chen Sun; Jun Li; Huan Li; Bo Zhang (Science of The Total Environment, 2024)

Association of metals and bisphenols exposure with lipid profiles and dyslipidemia in Chinese adults: Independent, combined and interactive effects - Jiemin Wei; Ruifang Liu; Ze Yang; Hongbo Liu; Yiqing Wang; Jingyun Zhang; Meiqing Sun; Changkun Shen; Jian Liu; Pei Yu; Nai-jun Tang (Science of The Total Environment, 2024)

How urban heat island magnifies hot day exposure: Global unevenness derived from differences in built landscape - Wenbo Yu; Jun Yang; Dongqi Sun; Jiayi Ren; Bing Xue; Wei Sun; Xiangming Xiao; Jianhong (Cecilia) Xia; Xueming Li (Science of The Total Environment, 2024)

Hotspot–subduction zone interactions and their resource effects at ∼120 Ma on the central Tibetan Plateau - Jia-Wei Bai; Jian-Jun Fan; Ye Zhan; Bo-Chuan Zhang; Si-Lin Sun; Yu-Jie Hao (Lithos, 2024)

Early Palaeozoic affinity of Hainan Island to Gondwana: New clues from metamorphic monazite and titanite of the Baoban Complex - Huiqing Ren; Jun Hu; Sanzhong Li; Dai Zhou; Ian Somerville; Lei Wang; Yongjiang Liu; Yanhui Suo; Shengyao Yu; Guozheng Sun; Xiangdong Wang (Lithos, 2024)

A high-flux phytic acid functionalized SiO2 blend polysulfone ultrafiltration membrane for extraction of uranium from seawater - Haowen Sun; Qi Liu; Jingyuan Liu; Jiahui Zhu; Jing Yu; Rongrong Chen; Rumin Li; Jun Wang (Journal of Environmental Chemical Engineering, 2024)

Fabrication of a family of porous azo polymers with multifunctional adsorption and separation performances - Yu Liu; Jun-Hong Jian; Jian Luan; Xiao-Sa Zhang; Ze-Bang Sun; Hong-Xiao Liu; Wen Yang; Wen-Ze Li (Journal of Environmental Chemical Engineering, 2024)

An unknow fault diagnosis Scheme: A novel random deep forest for fault diagnosis of HVACs - Ying Yan; Jianqiang Sun; Chenglong Yu; Xiaorong Sun; Edmond Qi Wu; Tao Li; Jun Cai; Adrian David Cheok (Energy and Buildings, 2024)

A reverberating triple AND logic gate nanomachine for intracellular multi-enzyme tracking and MicroRNA detection - Xu Zhu; Jun Zhu; Jin Wang; Guoquan Wu; Tianyu Su; Liying Fan; Junjie Li; Yufan Liu; Dehong Yu; Rongrong Sun; Ning Xin; Fenglei Gao (Chemical Engineering Journal, 2024)

Magneto-elastic for wireless intraocular pressure monitoring - Yu Lin; Shengxin Xiang; Wenjun Zou; Xiaohua Chen; Feixiang Gao; Yi Liu; Yijie Sun; Ping Chen; Quanxi Zhang; Xuelian Han; Baoping Wang; Yong Yao; et al. (Chemical Engineering Journal, 2024)

Lowering Schottky barrier in MoC-based cocatalyst via heteroatoms tunning for enhanced photocatalytic hydrogen evolution - Ru-zhou Miao; Yu-long Bao; Guang Yang; Ying-jie Sun; Xiao-jing Wang; Jun Zhao; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2024)

Microspheres-mediated magnetic thermal ablation combined with immune checkpoint blockade therapy for liver cancer - Xingwei Sun; Jiakun Yang; Jiaxi You; ZePeng Yu; Liang Yin; Hao Zhang; Di Wang; Jun Gu; Xuming Bai; Yong Jin; Zhixiang Zhuang (Chemical Engineering Journal, 2024)

Genesis of Pb–Zn-Ag-Sb mineralization in the Tethys Himalaya, China: Early magmatic-hydrothermal Pb–Zn(-Ag) mineralization overprinted by Sb-rich fluids - Xiang Sun; Ru-Yue Li; Hao-Yu Sun; Paul H. Olin; M. Santosh; Bin Fu; Jun Deng (Mineralium Deposita, 2024)

Effects of cadmium on the intestinal health of the snail Bradybaena ravida Benson - Yan-Mei Da; Shun-Shun Li; Yan-Qi Li; Le-Yu Deng; Ming-Jun Li; Tao Huang; Qing-Ye Sun; Jazbia Shirin; Guo-Wei Zhou (Ecotoxicology, 2024)

Nitrogen deposition in the middle-aged and mature coniferous forest: Impacts on soil microbial community structure and function - Jun Zhang; Fei Yu; Zhaoyong Hu; Shouqin Sun; Xiangyang Sun; Juying Sun; Wei Zhang; Genxu Wang (Applied Soil Ecology, 2024)

Blood trihalomethane and urinary haloacetic acid concentrations in relation to hypertension: An observational study among 1162 healthy men - Guangming Li; Shiyu Xu; Carmen Messerlian; Yu Zhang; Ying-Jun Chen; Yang Sun; Vicente Mustieles; Yi Wang; An Pan; Chong Liu; Yi-Xin Wang (Journal of Hazardous Materials, 2024)

Residual distribution and risk assessment of neonicotinoids in urban green space soils of the pearl river delta, South China: A socioeconomic analysis - Haojie Luo; Yanan Sun; Jun Pan; Ping Ding; Pengchong Wen; Yunjiang Yu; Limei Cai; Guocheng Hu (Journal of Hazardous Materials, 2024)

Volatomic differences among Vitis amurensis cultivars and its hybrids with V. vinifera revealed the effects of genotype, region, and vintage on grape aroma - Ming-Yu Li; Xuan-Xuan Pei; Ning Shi; Yi-Ming Yang; Shu-Tian Fan; Yan-Feng Sun; Qing-Sen Kong; Chang-Qing Duan; Keji Yu; Jun Wang (Food Research International, 2024)

Environmentally degradable carbon dots for inhibiting P. globosa growth and reducing hemolytic toxin - Hao Li; Chengming Sun; Mengling Zhang; Huibo Wang; Yu Chen; Jun Song (Environmental Pollution, 2024)

A high-entropy strategy for stable structure of sodium ion batteries: From fundamentals to applications - Xu Liu; Xin-Yu Liu; Nan Zhang; Peng-Fei Wang; Zong-Lin Liu; Jun-Hong Zhang; Jie Shu; Yan Sun; Chun-Sheng Li; Ting-Feng Yi (Chemical Engineering Journal, 2024)

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

The role of circular RNA during the urological cancer metastasis: exploring regulatory mechanisms and potential therapeutic targets - Yan Xu; Zhipeng Gao; Xiaoyu Sun; Jun Li; Toshinori Ozaki; Du Shi; Meng Yu; Yuyan Zhu (Cancer and Metastasis Reviews, 2024)

Microplastics weaken the digestion and absorption functions in the golden pompano (Trachinotus blochii) by affecting the intestinal structure, bacteria and metabolites - Fu Cheng Yao; Chun Xiu Jin; Huan Liang; Yu Zhang; Yue Gu; Fei Biao Song; Zhi Zhou; Jun Long Sun; Jian Luo (Chemosphere, 2024)

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

Bayesian analysis of physiologically based toxicokinetic (PBTK) modeling for pentachlorophenol exposure in pregnant women - Chunfeng Wu; Yajiao Tan; Xiaoyi Wei; Xun Li; Sifei Sun; Bing Lyu; Zhen Shen; Xiao Wei; Shuo Xiao; Yuanyuan Ruan; Jun Yu; Gengsheng He; et al. (Toxicology in Vitro, 2024)

Genomic analysis of Alteromonas sp. M12 isolated from the Mariana Trench reveals its role in dimethylsulfoniopropionate cycling - Yue Lin; Min Zhang; Yu-Xiang Lai; Teng Liu; Meng Meng; Yan Sun; Yu Wang; Qing-Yu Dong; Chen-Xi Li; Meng-Xue Yu; Jin Cheng; Shu-Jun Liu; et al. (Marine Genomics, 2024)

Association of urban green space with metabolic syndrome and the role of air pollution - Yi Sun; Yunli Chen; Yuanyuan Huang; Yan Luo; LiPing Yan; Sailimai Man; Canqing Yu; Jun Lv; Chuangshi Wang; Jun Wu; Heling Bao; Bo Wang; et al. (Landscape and Urban Planning, 2024)

Field investigation of unsaturated hydraulic conductivity using actively heated fiber-optic technology - Jie Liu; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang; Bin Shi (Journal of Hydrology, 2024)

Long-term reduced and no tillage increase maize (Zea mays L.) grain yield and yield stability in Northeast China - Yan-Jie Lv; Xiao-Long Zhang; Lei Gong; Shou-Bing Huang; Bao-Long Sun; Jin-Yu Zheng; Yong-Jun Wang; Li-Chun Wang (European Journal of Agronomy, 2024)

The Meso-Tethys Ocean: The nature, extension and spatial-temporal evolution - Jian-Jun Fan; Bo-Chuan Zhang; Jian-Bo Zhou; Yaoling Niu; Si-Lin Sun; Jun-Pu Lv; Yang Wang; Yu-Jie Hao (Earth-Science Reviews, 2024)

Overcoming melanin interference in melanocyte photodynamic therapy with a pyrene-derived two-photon photosensitizer - Vinayak Juvekar; Yu Cao; Chang Woo Koh; Dong Joon Lee; Sun Young Kwak; Sun Mi Kim; Tae Jun Park; Sungnam Park; Zhihong Liu; Hwan Myung Kim (Chemical Engineering Journal, 2024)

Stable 3D porous N-MXene/NiCo2S4 network with Ni–O atomic bridging for printed hybrid micro-supercapacitors - Pengcheng Sun; Jingyuan Liu; Qi Liu; Jing Yu; Rongrong Chen; Jiahui Zhu; Gaohui Sun; Ying Li; Dalei Song; Jun Wang (Chemical Engineering Journal, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Complete genome sequence of Erwinia pyrifoliae strain YKB12327, isolated from an apple tree in Korea - Hualin Nie; Sanghee Lee; Seo-Rin Ko; Young Kee Lee; Mi-Hyun Lee; Jun Myoung Yu; Jae Sun Moon; Ah-Young Shin; Suk-Yoon Kwon (Journal of Plant Pathology, 2024)

Soluble metal porphyrins - Zero-valent zinc system for effective reductive defluorination of branched per and polyfluoroalkyl substances (PFASs) - Jun Sun; Tsz Tin Yu; Maryam Mirabediny; Matthew Lee; Adele Jones; Denis M. O'Carroll; Michael J. Manefield; Priyank V. Kumar; Russell Pickford; Zeno Rizqi Ramadhan; Saroj Kumar Bhattacharyya; Björn Åkermark; et al. (Water Research, 2024)

Expression of genes related to gonadal development and construction of gonadal DNA methylation maps of Trachinotus blochii under hypoxia - Yue Gu; Chun Xiu Jin; Zai Hui Tong; Tian Jiang; Fu Cheng Yao; Yu Zhang; Jie Huang; Fei Biao Song; Jun Long Sun; Jian Luo (Science of The Total Environment, 2024)

Predicting the deformation of compacted loess used for land creation based on the field monitoring with fiber-optic technology - Jie Liu; Bin Shi; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang (Engineering Geology, 2024)

Numerical Analysis of the Effect of River Channel Excavation on Existing Subway Tunnels - Hai-ming Wang; Xiao Yu; Bang-ning Xing; Hao Wang; Jie Su; Hua-jun Zhang; Fa-xiang Sun (Geotechnical and Geological Engineering, 2024)

Aptamer based hybrid monolithic pipette tips supported by melamine sponge for enrichment of proteins - Yue-lun Sun; Jie Cheng; Bin-bin Liu; Jun-qin qiao; Ling-yu Zhao; Hong-zhen Lian; Li Mao (Analytica Chimica Acta, 2024)

Roles of photochemical consumption of VOCs on regional background O3 concentration and atmospheric reactivity over the pearl river estuary, Southern China - Jiayin Sun; Xiaoyu Yu; Zhenhao Ling; Guizhen Fang; Lili Ming; Jun Zhao; Shichun Zou; Huatian Guan; Haichao Wang; Xuemei Wang; Zhe Wang; Yuan Gao; et al. (Science of The Total Environment, 2024)

Asymmetry of hemispheric climate during MIS 16 versus MIS 12 - Xiaolin Ma; Haowen Dang; Jimin Yu; Mengfei Yang; Yachen Sun; Xingxing Liu; Wentao Ma; Jun Tian; Zhangdong Jin (Quaternary Science Reviews, 2024)

First record of the latest Devonian ostracods from Xainza region, Tibet, China: implications on palaeoenvironment and palaeobiogeography - Jun-Jun Song; Wen Guo; Yu-Cong Sun; Juan Ma; Jia-Yuan Huang; Yi-Chun Zhang; Wen-Kun Qie (Palaeoworld, 2024)

Large greenhouse gases emissions from lakes in Inner Mongolia, China - Heyang Sun; Ruihong Yu; Xinyu Liu; Zhuangzhuang Zhang; Xiaohui Ren; Xiangwei Li; Zhen Qi; Jun Wang; Zhiwei Guo; Penghang Zhu; Xixi Lu; Baoshan Cui (Journal of Hydrology, 2024)

The investigation of oxygen species in silicalite-1 supported MnOx-Na2WO4 catalyst towards efficient oxidative coupling of methane - Yujie Wang; Wenbo Kong; Yu Fu; Lei Zheng; Bingrong Pan; He Zhu; Shuqing Li; Jiong Li; Jun Zhang; Yuhan Sun (Journal of Environmental Chemical Engineering, 2024)

Late Jurassic–Early Cretaceous Rebangco ophiolite, Tibet: Constraints on the Meso-Tethys Ocean tectonic evolution - Jia-Wei Bai; Jian-Jun Fan; Yu-Jie Hao; Bo-Chuan Zhang; Si-Lin Sun (Journal of Asian Earth Sciences, 2024)

Preparation of slag-based foam concrete and its carbon dioxide sequestration performance - Jing Zhao; Yu-qing Li; Jing-jing Yang; Xiao-qiang Cao; Jun-xiang Wang; Gang Wang; Lu-lu Sun; Qi-ming Huang; Wei-min Cheng; Zhi-wen Lyu (International Journal of Greenhouse Gas Control, 2024)

Effect of two different Flammulina velutipes polysaccharides on the physicochemical and digestive properties of rice starch and their interaction mechanisms - Tingting Bu; Yuting Ren; Yue Yu; Weicheng Wu; Zhiguo Zhang; Weiwei Hu; Jun Lu; Jian Wang; Ming Cai; Kai Yang; Peilong Sun (Food Bioscience, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

Developmental mechanism of the SWCV nonlinear inertial waves - Chun Liu; Yueqing Li; Jun Sun; Yunlong Zhao; Jiaqi Yu (Dynamics of Atmospheres and Oceans, 2024)

Laboratory study on the frost-proof performance of a molecular vibration infrared Nano-thermoprobe (MVINT) embankment in seasonally frozen ground regions - Zhijian Wu; Guoxu Wang; Jun Bi; Wang Cao; Chengxin Chu; Yu Lu; Tian Sun; Bowen Tai (Cold Regions Science and Technology, 2024)

Marinobacter albus sp. nov., Isolated from Sand Sediment in a Coastal Intertidal Zone - Tai-Hang Deng; Yu Zhang; Wen-Wu Zhang; Yue Su; Jia-Wei Gao; Jun-Jie Ying; Lin Xu; Xiao-Ming Xia; Cong Sun (Current Microbiology, 2024)

Complex Topology of Ubiquitin Chains Mediates Lysosomal Degradation of MrgC Proteins - Jiacheng Yu; Dan Li; Mingming Xie; Jun Xie; Zhen Wang; Xiaoping Gu; Zhengliang Ma; Yu’e Sun (Cell Biochemistry and Biophysics, 2024)

Structural elucidation a complex galactosyl and glucosyl-rich pectin from the pericarp of immature fruits of Juglans mandshurica Maxim. - Xi-Zhe Sun; Qing-Yu Zhang; Si-Liang Jiang; Rong-Jian Zhu; Jun-Hong Chai; Jun Liang; Hai-Xue Kuang; Yong-Gang Xia (Glycoconjugate Journal, 2024)

Spatial distribution and environmental/biological co-regulation mechanism of dimethyl sulfur compounds in the eastern Indian Ocean - Liying Peng; Chenjuan Fan; Yu Guo; Changling Ding; Xingzhou Wang; Guicheng Zhang; Jun Sun (Frontiers in Marine Science, 2024)
Dimethyl sulfur compounds including dimethylsulfoniopropionate (DMSP), dimethyl sulfide (DMS), and dimethyl sulfoxide (DMSO), play a crucial part in global sulfur cycling. The eastern Indian Ocean (EIO), characterized by its remarkable diversity of biomes and climate dynamics, is integral to global climate regulation. However, the regulation mechanism of DMS (P, O) in the EIO remains to be elucidated in detail. This paper presented a field survey aimed at investigating the spatial distribution of DMS (P, O) and their relationships with environmental and biological factors in the EIO. The surface concentrations of DMS, DMSPt, and DMSOt varied from 0.07 to 7.37 nmol/L, 0.14 to 9.17 nmol/L, and 0.15 to 3.32 nmol/L, respectively, and their distributions are attributed to high Chl-a concentration near Sri Lanka and the influence of ocean currents (Wyrtki jets, Bay of Bengal runoff). Higher concentrations of DMS (P) and DMSOt were predominantly observed in water columns shallower than 75m and deeper than 75m deep, respectively. The monthly DMS fluxes in the study area peaked in August. Temperature and Dissolved Silica Index (DSI) were the key environmental determinants for DMS distribution, while nitrate (NO 3 - ) was the primary factor for both DMSPt and DMSOt. In terms of biological factors, Prochlorococcus and Synechococcus were significant contributors to DMS (P, O) dynamics. Synechococcus was the dominant influence on the DMS source and DMSPt sink, whereas Prochlorococcus primarily consumed DMSOt. Furthermore, the structural equation modeling (SEM) revealed the relationship between DMS, DMSPt, DMSOt, and the key environmental/biological factors, as well as among them, and together they formed a co-regulatory network in the EIO. This contributes significantly to the advancement of global ecosystem models for DMS (P, O).

Identification of SNPs and candidate genes associated with growth using GWAS and transcriptome analysis in Coilia nasus - Yue Yu; Shi-Ming Wan; Shuang-Meng Zhang; Jun-Qi Liu; Ai-Li Sun; Yao Wang; Yong-Fu Zhu; Shu-Xin Gu; Ze-Xia Gao (Aquaculture, 2024)

STON2 variations are involved in synaptic dysfunction and schizophrenia-like behaviors by regulating Syt1 trafficking - Yuanlin Ma; Kai Gao; Xiaoxuan Sun; Jinxin Wang; Yang Yang; Jianying Wu; Anping Chai; Li Yao; Nan Liu; Hao Yu; Yi Su; Tianlan Lu; et al. (Science Bulletin, 2024)

Self-repaired cathode electrolyte interphase to stabilize the high-nickel cathode interface by a sustained-release multifunctional electrolyte additive - Yue Zou; Qizheng Zheng; Yonglin Tang; Yawen Yan; Shiyuan Zhou; Hong-Gang Liao; Yu Qiao; Jun Bao; Shi-Gang Sun (Chemical Engineering Journal, 2024)

A novel injectable thermo/photo dual-crosslinking hydrogel based on modified chitosan for fast sealing open globe injury - Peifang Xu; Pengjie Chen; Yiming Sun; Maimaiti Nuliqiman; Yifan Zhou; Jing Cao; Shan Yu; Jun Huang; Juan Ye (Carbohydrate Polymers, 2024)

Influence of updated isoprene oxidation mechanisms on the formation of intermediate and secondary products in MCM v3.3.1 - Zhenhao Ling; Huatian Guan; Yonghong Wang; Xiaoyu Yu; Jiayin Sun; Yee Jun Tham; Xuemei Wang; Zhe Wang; Hai Guo (Atmospheric Environment, 2024)

A MYB transcription factor GhTT2 of Gossypium hirsutum regulates proanthocyanidin accumulation and improves osmotic tolerance in Arabidopsis - Jun Mei; Rongrong Mu; Qingqing Niu; Huimin Zhu; Ruoxi Chen; Xiaomiao Cai; Meng Miao; Dongliang Yu; Liping Ke; Yuqiang Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

The impact of eddies and spring warm pool on sinking rates of phytoplankton with different shapes and sizes - Yingjie Mao; Congcong Guo; Linghui Yu; Xun Gong; Jun Sun (Marine Biology, 2024)

Recent advances in catalytic oxidation of VOCs by two-dimensional ultra-thin nanomaterials - Long Sun; Shunzheng Zhao; Xiaolong Tang; Qingjun Yu; Fengyu Gao; Jun Liu; Ya Wang; Yuansong Zhou; Honghong Yi (Science of The Total Environment, 2024)

Isolation and biological activities of chemical constituents from Aspergillus niger - Jing Yi; Yu Zhang; Xuan Wang; Chao Wang; Chengpeng Sun; Jun Wu; Yuhzuo Wu (Phytochemistry Letters, 2024)

A Keichousaurus-bearing regurgitalite from the Middle Triassic Xingyi Fauna, Dingxiao of Xingyi City, Guizhou, South China - Xiao-Jun Ye; Zuo-Yu Sun; Ming-Tao Yao (Palaeoworld, 2024)

A review of combined fouling on high-pressure membranes in municipal wastewater reuse: Behaviors, mechanisms, and pretreatment mitigation strategies - Xiao-Yang Liu; Yu-Bo Chen; Jie Fu; Xianzheng Zhu; Long-Yi Lv; Li Sun; Guang-Ming Zhang; Zhi-Jun Ren (Chemical Engineering Journal, 2024)

Constructing flame retardant microspheres for safe and stable poly (ethylene oxide) based All-Solid-State batteries at high voltage - Guoqing Liu; Hao Yu; Tao Zhu; Jinxuan Chen; Xinxin Dong; Hao Jia; Jun Sun; Xiaoyu Gu; Sheng Zhang (Chemical Engineering Journal, 2024)

The impacts of planting patterns combined with irrigation management practices on soil water content, watermelon yield and quality - Xiaolin Qiang; Zhaojun Sun; Xingqiang Li; Siqi Li; Zhao Yu; Jun He; Qian Li; Lei Han (Agroforestry Systems, 2024)

Interaction between Sea perch iridovirus (SPIV) infection and gut microbes in sea perch Lateolabrax japonicus - Zheng Zhu; Yu-Min Xu; Wen-Feng Yang; Wu-Lang Luo; Wei Huang; Jun-Han Liang; Jin-Ding Chen; Hong-Yan Sun; Qi-Wei Qin (Aquaculture, 2024)

Inhibitory effect of microplastics derived organic matters on humification reaction of organics in sewage sludge under alkali-hydrothermal treatment - Jun Chen; Tong Sun; Peng Yang; Siwei Peng; Junxia Yu; Dongsheng Wang; Weijun Zhang (Water Research, 2024)

Inhibition of pyrite oxidation through forming biogenic K-jarosite coatings to prevent acid mine drainage production - Maoxin Hong; Jun Wang; Baojun Yang; Yang Liu; Xin Sun; Laishun Li; Shichao Yu; Shitong Liu; Yang Kang; Wei Wang; Guanzhou Qiu (Water Research, 2024)

Enzymatic hydrolysis of oat core flour improves physiochemical and sensory behaviors for oat milk - Min Zhang; Kai Huang; Jun Lu; Anni Lu; Xiao Guan; Yu Zhang; Sen Li; Hongdong Song; Hongwei Cao; Zhu Sun; Zhiquan Yu (Journal of Cereal Science, 2024)

Genetic diversity and population structure of different Schisandraceae accessions by EST-SSR markers - Guangli Shi; Binhong Zhu; Dan Sun; Zhenxing Wang; Jun Ai; Jiaqi Geng; Xiang Li; Miao Yu; Chengcheng Zhao; Xiyu Zhang (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Hydroclimatic changes in eastern China during the Holocene based on pollen data and climate modeling - Qin Li; Haibin Wu; Jun Cheng; Wenchao Zhang; Yanyan Yu; Aizhi Sun; Yunli Luo (Global and Planetary Change, 2024)

The impacts of nitrogen addition on the active carbon pools in forest soils along an urban–rural gradient - Ruoxian Fu; Yuanchun Yu; Yue He; Xiaoniu Xu; Xu Sun; Jun Yang; Xiao Tao (CATENA, 2024)

Different concentrations of betaxolol switch cell fate between necroptosis, apoptosis, and senescence in human corneal stromal cells - Jing-Yu Sun; Jun Zhao; Yue Qiu; Ting-Jun Fan (Chemico-Biological Interactions, 2024)

Promotion of anaerobic biodegradation of azo dye RR2 by different biowaste-derived biochars: Characteristics and mechanism study by machine learning - Yu-Qian Wang; Jie Ding; Ji-Wei Pang; Chuan-Dong Wu; Han-Jun Sun; Rui Fang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

Different responses of two adjacent artificial beaches to Typhoon Hato in Zhuhai, China - Jun Zhu; Qing Wang; Chao Zhan; Fengjuan Sun; Wenhao Hua; Jianhui Liu; Hongshuai Qi; Yu Yang (Journal of Oceanology and Limnology, 2024)

Heterozygosity analysis of spontaneous 2n female gametes and centromere mapping of the diploid Hevea brasiliensis based on full-sib triploid populations - Yuan-yuan Zhang; Hong-kun Li; Xiao Huang; Yu-jiao Yuan; Xiao-fei Zhang; Xin-sheng Gao; Xiang-jun Wang; Ming-ming Wei; Hua-sun Huang; Weiguo Li (Plant Reproduction, 2024)

Rapid nanomolar detection of Δ9-tetrahydrocannabinol in biofluids via electrochemical aptamer-based biosensor - Yu Xie; Jin-Ping She; Jia-Xing Zheng; Kalle Salminen; Jian-Jun Sun (Analytica Chimica Acta, 2024)

Pyrolysis characteristics and product distribution of oil sludge based on radiant heating - Zhanlong Song; Tao Tang; Baolin Xu; Jun Yu; Ying Su; Yingping Pang; Xiqiang Zhao; Jing Sun; Yanpeng Mao; Wenlong Wang (Environmental Science and Pollution Research, 2024)

Identification of organic pollutants and heavy metals in natural rubber wastewater and evaluation its phytotoxicity and cytogenotoxicity - Dayu Zhu; Chengjun Ge; Ying Sun; Huamei Yu; Jun Wang; Hongfei Sun (Chemosphere, 2024)

A novel tool for tracing water sources of streamflow in a mixed land-use catchment - Zhi-Xiang Sun; Jun-Fang Cui; Jian-Hua Cheng; Xiang-Yu Tang (Science of The Total Environment, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Corrigendum to “Transport of functional group modified polystyrene nanoplastics in binary metal oxide saturated porous media” [J Hazard Mater 441 (2023) 129834] - Guangcai Zhang; Qiang Ma; Mengdie Yu; Jing Yin; Huimin Sun; Nong Wang; Jun Wang; Xianqiang Yin (Journal of Hazardous Materials, 2024)

Environmental surveillance in Jinan city of East China (2014–2022) reveals improved air quality but remained health risks attributable to PM2.5-bound metal contaminants - Zhigang Yu; Zhan Sun; Lanzheng Liu; Chao Li; Xin Zhang; Gzalnur Amat; Mohan Ran; Xiaoyue Hu; Yunxiang Xu; Xiulan Zhao; Jun Zhou (Environmental Pollution, 2024)

Visible-light-driven photo-Fenton oxidation enhanced by Fe/Bi-nanocrystal phase transformation as a universal way for various organic pollutants mineralization - Tulai Sun; Zi-Yan Jin; Bin Deng; Gan He; Qiong-Yu Wang; Mian Hu; Zhangliang Han; Zhaoke Zheng; Jun Zhao; Jimmy Yun; Jia Zhao; Yihan Zhu; et al. (Chemical Engineering Journal, 2024)

Tunability of Pickering particle features of whey protein isolate via remodeling partial unfolding during ultrasonication-assisted complexation with chitosan/chitooligosaccharide - Hongmei Yu; Yuanrong Zheng; Changyu Zhou; Lianliang Liu; Libin Wang; Jinxuan Cao; Yangyin Sun; Jun He; Daodong Pan; Zhendong Cai; Qiang Xia (Carbohydrate Polymers, 2024)

Dissecting the genetic basis of Fusarium crown rot resistance in wheat by genome wide association study - Jinlong Li; Shanshan Zhai; Xiangru Xu; Yuqing Su; Jiazheng Yu; Yutian Gao; Jiatian Yang; Zhi Zheng; Baoyun Li; Qixin Sun; Chaojie Xie; Jun Ma (Theoretical and Applied Genetics, 2024)

The mitigating effect of new digital technology on carbon emissions: evidence from China - Jun Chen; Yina Chen; Xiangcui Liang; Lu Yu; Jielun Sun; Xintong Luo; Mansi Zhang; Zhuoqi Wu (Environmental Science and Pollution Research, 2024)

MiRNAs enabled Golden pompano (Trachinotus blochii) in response to different reoxygenation patterns after hypoxic stress - Tian Jiang; Jun Long Sun; Chun Xiu Jin; Yu Zhang; Zai Hui Tong; Yue Gu; Fu Cheng Yao; Li Ping Shi; Fei Biao Song; Jian Luo (Aquaculture, 2024)

Identification of point and nonpoint emission sources of neonicotinoid pollution in regional surface water - Yuanchen Chen; Jun Ling; Wenfei Yu; Li Zhang; Ruxin Wu; Dan Yang; Jiajia Qu; Hangbiao Jin; Zhen Tao; Yuexin Shen; Ruirui Meng; Jingtong Yu; et al. (Water Research, 2024)

O-acetyl-homoserine sulfhydrylase deficient Streptococcus suis serotype 2 strain SC19 becomes an avirulent strain and provides immune protection against homotype infection in mice - Tong Wu; Hexiang Jiang; Fengyang Li; Xuan Jiang; Jun Wang; Shaopeng Wei; Yi Sun; Yanyan Tian; Hong Chu; Yu Shi; Nan Zhang; Na Li; et al. (Veterinary Microbiology, 2024)

Sirtuin 3-mediated deacetylation of superoxide dismutase 2 ameliorates sodium fluoride-induced mitochondrial dysfunction in porcine oocytes - Xin-Yue Qi; Jin-Dong Yuan; Zi-Yu Liu; Xi-Qing Jiang; Qi Zhang; Shan-Long Zhang; Lu Zhao; Ling-Yan Ke; Chen-Yuan Zhang; Yan Li; Lu-Yan Zhang; Qian-Qian Xu; et al. (Science of The Total Environment, 2024)

Associations of nighttime light exposure during pregnancy with maternal and neonatal gut microbiota: A cohort study - Ni Wu; Yu Sun; Tianlai Qiu; Jun Liu; Yanan Cao; Tianzi Zang; Xiaoxiao Fan; Jinbing Bai; Jing Huang; Yanqun Liu (Science of The Total Environment, 2024)

Greenhouse gas emissions from Daihai Lake, China: Should eutrophication and salinity promote carbon emission dynamics? - Xiangwei Li; Ruihong Yu; Jun Wang; Heyang Sun; Xinyu Liu; Xiaohui Ren; Shuai Zhuang; Zhiwei Guo; Xixi Lu (Journal of Environmental Sciences, 2024)

Tree-ring structured phase change materials with high through-plane thermal conductivity and flexibility for advanced thermal management - Wan-jun Jiang; Rui-qing Wang; Ting-yu Zhu; Mai Feng; De-xiang Sun; Jing-hui Yang; Xiao-dong Qi; Yong Wang (Chemical Engineering Journal, 2024)

Fructooligosaccharides and fructans from Platycodon grandiflorum: Structural characterization, lung-oriented guidance and targetability - Jun Liang; Wen-Fei Wang; Yi Zhang; Yan-Qun Chai; Ya-Ge Li; Si-Liang Jiang; Xin-Hua Zhu; Yu-Li Guo; Zhen Wei; Xi-Zhe Sun; Hai-Xue Kuang; Yong-Gang Xia (Carbohydrate Polymers, 2024)

Preliminary Investigation on Efficacy and Safety of Substance P-Coated Stent for Promoting Re-Endothelialization: A Porcine Coronary Artery Restenosis Model - Dae Sung Park; Seok Oh; Yu Jeong Jin; Mi Hyang Na; Munki Kim; Jeong Ha Kim; Dae Young Hyun; Kyung Hoon Cho; Young Joon Hong; Ju Han Kim; Youngkeun Ahn; Manuel Hermida-Prieto; et al. (Tissue Engineering and Regenerative Medicine, 2024)

The benefit of omeprazole exposure on all-cause mortality and length of ICU/hospital stay might vary with age in critically ill pediatric patients: A cohort study - Fang-Fang Jiang; Yu Guo; Zheng Zhang; Sun-Jun Yin; Yu-Xin Fan; Yan-Hua Huang; Ya-Jia Li; Li-Rong Chen; Kai Qian; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

m6A modification associated with YTHDF1 is involved in Japanese encephalitis virus infection - Xiao-han Li; Jing Chen; Yu-da Ou; Xiang Zhong; Jia-huan Hu; Rui-cong Sun; Ying-jun Lv; Jian-chao Wei; Yun Young Go; Bin Zhou (Veterinary Microbiology, 2023)

The association between blood heavy metals and gallstones: A cross-sectional study - Jia Wang; Yu-xin Sun; Shuai Xiang; Chen Yang; Xiang-jun Li; Meng-qi Zhang; Yu-jing Li; Xiao-xuan Li; Zhen-kang Qiu (Science of The Total Environment, 2023)

Characterising personal, household, and community PM2.5 exposure in one urban and two rural communities in China - Ka Hung Chan; Xi Xia; Cong Liu; Haidong Kan; Aiden Doherty; Steve Hung Lam Yim; Neil Wright; Christiana Kartsonaki; Xiaoming Yang; Rebecca Stevens; Xiaoyu Chang; Dianjianyi Sun; et al. (Science of The Total Environment, 2023)

Thickness-variation-insensitive near-infrared quantum dot LEDs - Wan-Shan Shen; Yang Liu; Luke Grater; So Min Park; Haoyue Wan; Yan-Jun Yu; Jia-Lin Pan; Fan-Cheng Kong; Qi-Sheng Tian; Dong-Ying Zhou; Zeke Liu; Wanli Ma; et al. (Science Bulletin, 2023)

Biochar reduces uptake and accumulation of polycyclic aromatic hydrocarbons (PAHs) in winter wheat on a PAH-contaminated soil - Jinfeng WANG; Huanyu BAO; Yu Bon MAN; Jun CAI; Jia LI; Benhua SUN; Fuyong WU (Pedosphere, 2023)

pH-Responsive graphene oxide/poly (methacrylic acid) hybrid nanofiltration membrane performance for water treatment - Li-yue Sun; De-hao Yu; Zhao-ge Juan; Yao Wang; Yan-xin Wang; Matt J. Kipper; Lin-jun Huang; Jian-guo Tang (Journal of Environmental Chemical Engineering, 2023)

In silico screening and characterization, inhibition mechanism on ACE, and stability of antihypertensive peptides with Zn-chelating capacity identified from millet bran albumin hydrolysates - Yajun Zheng; Jun Ma; Yizi Guo; YongLiang Zhuang; Zifang Yang; Zilin Zhu; Yu Kan; Junru Li; Ruijie Sun (Food Bioscience, 2023)

Studies on blocking the JAK2/STAT3 signaling pathway with elastin peptides from skipjack tuna (Katsuwonus pelamis) bulbus cordis to alleviate osteoarthritis - Qiaoli Wu; Bing Liu; Rongxian Yu; Xiaoling Sun; Ziyan Wang; Jun Zhou; Chenyang Lu; Jing Zhang; Jiaojiao Han; Xiurong Su (Food Bioscience, 2023)

Molecular and functional characterization of golden pompano (Trachinotus blochii) TBK1 on IFN regulation - Jin-Feng Tong; Rui-Hai Gan; Lang Yu; Shao-Yang Bu; Jun-Long Sun; Xin Wen; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2023)

Joint effects of prenatal exposure to air pollution and pregnancy-related anxiety on birth weight: A prospective birth cohort study in Ma’anshan, China - Zhen-Hua Li; Yi-Cheng Mao; Yang Li; Sun Zhang; Hui-Yu Hu; Zhe-Ye Liu; Xue-Jie Liu; Jia-Wen Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Research, 2023)

Fine mapping and candidate gene analysis of qSB12YSB, a gene conferring major quantitative resistance to rice sheath blight - Yu Wang; Quanyi Sun; Jianhua Zhao; Taixuan Liu; Haibo Du; Wenfeng Shan; Keting Wu; Xiang Xue; Chao Yang; Jun Liu; Zongxiang Chen; Keming Hu; et al. (Theoretical and Applied Genetics, 2023)

Integrated FET sensing microsystem for specific detection of pancreatic cancer exosomal miRNA10b - Yi Yu; Chunzi Liang; Qiang-Qiang Wan; Dan Jin; Xi Liu; Zhiyong Zhang; Zhong-Yue Sun; Guo-Jun Zhang (Analytica Chimica Acta, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

A Modified Pressure Pulse Decay Experimental Apparatus and Its Application in Permeability Measurements - Gang Wang; Xiao-xiang Sun; Zhi-yong Xiao; Chang-Sheng Wang; Jun-hong Yu; Feng Jiang; Cheng-cheng Zheng (Applied Geophysics, 2023)

The effects of nutritional interventions in patients with non-alcoholic fatty liver disease: An umbrella review of meta-analyses of randomized controlled trials - Liuqiao Sun; Hangjun Chen; Qian Ou; Xiaoping Liang; Qiongmei Wu; Xinxue Yu; Hanqing Zhao; Qiaoli Huang; Zehua Yi; Xuying Tan; Jun Wei; Feng Wu; et al. (Trends in Food Science & Technology, 2023)

α-LA attenuates microcystin-LR-induced hepatocellular oxidative stress in mice through Nrf2-mediated antioxidant and detoxifying enzymes - Jun Bai; Chaoyun Chen; Yaochuan Sun; Shangchun Li; Renjiang He; Qingbi Zhang; Qian Sun; Yu Huang; Ailin Tan; Li Yuan; Yinxing Huang; Yuanyuan Lan; et al. (Toxicon, 2023)

An accurate and efficient HOS-meshfree CFD coupling method for simulating strong nonlinear wave–body interactions - Chun-Mei Xie; Jun-Cheng Yang; Peng-Nan Sun; Hong-Guan Lyu; Jun Yu; Yong-Lin Ye (Ocean Engineering, 2023)

Dynamics of chromophoric dissolved organic matter in a highly productive Amundsen Sea polynya - Ji Hu; Siyou Xue; Jun Zhao; Zhengbing Han; Dong Li; Haifeng Zhang; Peisong Yu; Minhui Zheng; Jianming Pan; Yongge Sun (Marine Chemistry, 2023)

Decision support framework adapted to local conditions to select technologies for rural domestic sewage treatment in the Yangtze River Economic Belt - Mei-Yun Lu; Shan-Shan Yang; Xin-Lei Yu; Han-Jun Sun; Ji-Wei Pang; Nan-Qi Ren; Jie Ding (Journal of Cleaner Production, 2023)

Emissions from international airport and its impact on air quality: A case study of beijing daxing international airport (PKX), China - Ya-nan Wang; Chao Zou; Tian-ge Fang; Nai-xiu Sun; Xiao-yu Liang; Lin Wu; Hong-jun Mao (Environmental Pollution, 2023)

Advances and promotion strategies of membrane-based methods for extracting lithium from brine - Yu-ning Zhang; De-hao Yu; Chen-yu Jia; Li-yue Sun; Ang Tong; Yao Wang; Yan-xin Wang; Lin-jun Huang; Jian-guo Tang (Desalination, 2023)

Nitrogen allocation for CO2 fixation promotes nitrogen use in the photosynthetic compensation of soybean under heterogeneous light after a pre-shading - Xin Sun; En-Ze Zhang; Liang Yu; Jun-Bo Du; Wen-Yu Yang (Physiology and Molecular Biology of Plants, 2023)

The formation of proto-austronesians: insights from a revised phylogeography of the paternal founder lineage - Hui-Xin Yu; Xian-Peng Zhang; Yun Bai; Kai-Jun Liu; Hui Li; Yong-Lan Li; Jin Sun; Lan-Hai Wei (Molecular Genetics and Genomics, 2023)

Association between ambient air pollution exposure in pregnant women with antiphospholipid syndrome in Nanjing, China - Bimei Hu; Linjie Xu; Xu Yang; Shiwen Qu; Lan Wu; Yumei Sun; Jun Yan; Yexiao Zhang; Zhaoer Yu; Yixiao Wang; Ruizhe Jia (Environmental Science and Pollution Research, 2023)
Antenatal exposure to air pollutants is thought to be associated with a variety of maternal blood markers as well as adverse birth outcomes. However, the dysgenic influence of air pollutants on the antiphospholipid syndrome (APS) in mothers and their pregnancy outcomes remains unclear. In the current study, 371 mother-infant pairs (189 healthy: 182 APS) from Nanjing Maternal and Child Health Hospital as well as air pollutants concentration from their living environment were used to investigate correlations between air pollution with maternal blood indicators and fetal birth weight in the groups of APS and healthy mothers. Generalized linear model was used to evaluate the contributions of air pollutant exposure during pregnancy to the blood indicators variation. The relationships between birth weight with specific air pollutant and blood index were analyzed using ridge regression. Results showed that APS fetal birth weight was significantly impacted by air pollutant exposure during pregnancy, in particular, the birth weight decreased significantly along with increasing fine particulate matter 2.5 (PM 2.5 ) and fine particulate matter 10 (PM 10 ) exposure concentrations throughout pregnancy. In contrast, birth weight increased significantly with sulfur dioxide (SO 2 ) exposure. In addition, APS-related blood indicators comprised of platelet distribution width (PDW), total bilirubin (TBIL), mean platelet volume (MPV), platelet-larger cell ratio (P_LCR), homocysteine (HCY), alkaline phosphatase (ALP), direct bilirubin (DBIL), basophilic granulocyte (BAS), platelet thrombocytocrit (PCT), preprandial glucose levels (OGTT0), monocytes (MON), and monocytes ratio (MON_ratio) were also strongly related with prenatal exposure to PM 2.5 and PM 10 , in which PDW levels showed most strongly negative impaction on fetal birth weight. Together, we showed that prenatal exposure to air pollutant (PM 2.5 and PM 10 ) may exacerbate the poor birth outcomes of low birth weight by impacting APS maternal blood indicators especially for PDW.

A new anchor-siphon drainage combined method used for slope stabilization - Hong-yue Sun; Xu Wang; Yang Yu; Jun-wei Shu; Tian-long Wang; Rui Luo; Zhao-wei Chu (Journal of Mountain Science, 2023)

Hypoxia enhances steroidogenic competence of buffalo (Bubalus bubalis) granulosa cells - Yu Zhang; Jun Zhang; Junming Sun; Yiqiang Ouyang; Deshun Shi; Fenghua Lu (Theriogenology, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Fluxes in CO2 and CH4 and influencing factors at the sediment-water interface in a eutrophic saline lake - Xiangwei Li; Ruihong Yu; Jun Wang; Heyang Sun; Changwei Lu; Xinyu Liu; Xiaohui Ren; Shuai Zhuang; Zhiwei Guo; Xixi Lu (Journal of Environmental Management, 2023)

Fluorocarbon-based self-layering interpenetrating polymer-network coatings with anti-fouling and anti-icing properties - Zixu Zhang; Rongrong Chen; Jing Yu; Gaohui Sun; Qi Liu; Jingyuan Liu; Jiahui Zhu; Peili Liu; Jun Wang (Chemical Engineering Journal, 2023)

Platelet membrane-functionalized hollow mesoporous Prussian blue nanomedicine for comprehensive thrombolytic management by targeted enhanced fibrinolysis and ROS scavenging - Wenli Zhang; Maoyuan Sun; Yun Liu; Yu Zhang; Lian Xu; Ying Luo; Qianying Du; Jie Xu; Jia Liu; Jun Zhou; Haitao Ran; Zhigang Wang; et al. (Chemical Engineering Journal, 2023)

An inkjet-printing ink based on porous NiS/N-MXene for high-performance asymmetric micro-supercapacitors and self-powered microelectronics - Pengcheng Sun; Jingyuan Liu; Qi Liu; Jing Yu; Rongrong Chen; Jiahui Zhu; Gaohui Sun; Ying Li; Peili Liu; Jun Wang (Chemical Engineering Journal, 2023)

Glutathione-Responsive Sulfur Dioxide-Releasing Dendronized Chitooligosaccharide Polymer for Effective Treatment of Multidrug-Resistant Bacterial Infection - Haitao Yu; Jiejiao Liu; Qianwen Lin; Jun Liu; Siming Yu; Pinghua Sun; Jing Lin (Chemical Engineering Journal, 2023)

A negative feedback bionic hydrogel reverses damaged cartilage microenvironment and induces targeted BMSCs differentiation for cartilage regeneration - Zhi Zheng; Jian Sun; Jun Wang; Suisui He; Yun Huang; Xu Yang; Yuqi Zhao; Cui-Yun Yu; Hua Wei (Chemical Engineering Journal, 2023)

Epoxy-based high-k composite vitrimer: With low dielectric loss, high breakdown strength and surface electrical damage repairability - Yu-Cheng Zhang; Wen-Dong Li; Xin Zhao; Fan-Bo Meng; Peng Sun; Chao Wang; Guang-Zhi Guo; Wen-Rui Li; Guan-Jun Zhang (Chemical Engineering Journal, 2023)

Association of urinary heavy metal combined exposure with periodontitis among US adults from NHANES 2011–2014 - Zhen-Hua Li; Jiong Li; Yi-Cheng Mao; Jia-Wen Zhao; Hui-Yu Hu; Sun Zhang; Zhe-Ye Liu; Xue-Jie Liu; Kai Huang; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Science and Pollution Research, 2023)

Three new compounds with their anti-glioma effects from the roots of Arnebia guttata Bunge - Yu-Mei Yan; Lin-Jun Zou; Min-Hui Li; Zhao-Cui Sun; Min Zhang; Xu-Dong Xu; Chun-Hong Zhang (Natural Product Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Lanostane triterpenoids with anti-proliferative and anti-inflammatory activities from medicinal mushroom Ganoderma lingzhi - Zhen-Zhu Zhao; Bao-Yu Ji; Zhen-Zhen Wang; Ying-Ying Si; Yan-Jun Sun; Hui Chen; Wei-Sheng Feng; Xiao-Ke Zheng; Ji-Kai Liu (Phytochemistry, 2023)

Coupling effect of DOM and microbe on arsenic speciation and bioavailability in tailings soil after the addition of different biologically stabilized sludges - Kewei Li; Jun Chen; Wenjin Sun; Hao Zhou; Yu Zhang; Hao Yuan; Aibin Hu; Dongsheng Wang; Weijun Zhang (Journal of Hazardous Materials, 2023)

An integrated model chain for future flood risk prediction under land-use changes - Jun Liu; Junnan Xiong; Yangbo Chen; Huaizhang Sun; Xueqiang Zhao; Fengmiao Tu; Yu Gu (Journal of Environmental Management, 2023)

Genetic diversity, antibiotic resistance, and virulence characteristics of Staphylococcus aureus from raw milk over 10 years in Shanghai - Jiewen Huang; Wengang Zhang; Bingqing Sun; Qin Jiang; Ying Cao; Jun Shang; Yu Zhang; Xin Gu; Chao Lv; Chaoyi Guo; Min Li; Hui Li; et al. (International Journal of Food Microbiology, 2023)

Associations of Blood and Cerebrospinal Fluid Aβ and tau Levels with Renal Function - Hao-Lun Sun; Xiu-Qing Yao; Li Lei; Wang-Sheng Jin; Yu-Di Bai; Gui-Hua Zeng; An-Yu Shi; Jun Liang; Li Zhu; Yu-Hui Liu; Yan-Jiang Wang; Xian-Le Bu (Molecular Neurobiology, 2023)

Study on gender differences between male and female Sargassum thunbergii based on metabolomic analysis and physiological functions - Tianyi Qiu; Yan Sun; Tongfei Qu; Song Xue; Jun Chen; Yu Zang; Qian Liu; Xuexi Tang (Algal Research, 2023)

Organic carbon preservation in wetlands: Iron oxide protection vs. thermodynamic limitation - Fu-Sheng Sun; Chao Ma; Guang-Hui Yu; Yakov Kuzyakov; Yun-Chao Lang; Ping-Qing Fu; Li-Jun Guo; Hui Henry Teng; Cong-Qiang Liu (Water Research, 2023)

Liquid metal microspheres with an eddy-thermal effect for magnetic hyperthermia-enhanced cancer embolization-immunotherapy - Nailin Yang; Xingwei Sun; Yangkai Zhou; Xiaoyuan Yang; Jiaxi You; Zepeng Yu; Jun Ge; Fei Gong; Zhisheng Xiao; Yong Jin; Zhuang Liu; Liang Cheng (Science Bulletin, 2023)

High performance and mechanism of Tl(I) removal from solution by synergetic application of nanowire γ-MnOOH@biochar and free radicals: Implications to AMD treatment - Jin Wang; Shan Yu; Yanjun Jiang; Yanyi Liu; Xinni Xiong; Jun Xiao; Mengqing Sun; Jingzi Beiyuan; Juan Liu; Gang Song (Journal of Water Process Engineering, 2023)

Exposure to multiple air pollutant mixtures and the subtypes of hypertensive disorders in pregnancy: A multicenter study - Wen Jiang; Guoqi Yu; Cuiping Wang; Shengju Yin; Yun Huang; Qian Chen; Kun Sun; Jun Zhang (International Journal of Hygiene and Environmental Health, 2023)

Hyaluronic acid-based dual network hydrogel with sustained release of platelet-rich plasma as a diabetic wound dressing - Jie Zhou; Yufei Liu; Xiangsheng Liu; Jinpeng Wan; Shuyu Zuo; Tengwu Pan; Yanyu Liu; Feifan Sun; Minli Gao; Xinyi Yu; Weihong Zhou; Jun Xu; et al. (Carbohydrate Polymers, 2023)

Utilizing wastewater and flue gas for enhancing biomass and high-value products from microalgae - Jaemin Joun; Ranjna Sirohi; Byung Sun Yu; Ha Eun Yang; Sang Jun Sim (Phytochemistry Reviews, 2023)

Thymic tuft cells: potential “regulators” of non-mucosal tissue development and immune response - Jun Sun; Ming-xin Li; Yi-meng Xie; Ya-ru Zhang; Yu-rong Chai (Immunologic Research, 2023)

Characteristics of atmospheric carbonyls pollution in winter around petrochemical enterprises over North China - Jin-he Wang; Ou-yang Li; Xue Yang; Guang Pan; Guo-lan Fan; Hou-yong Zhang; Zhi-yong Xia; Xiao-yan Sun; Hong-yu Xu; Yan-jun Chen; Chao Zhu (Air Quality, Atmosphere & Health, 2023)

Responses of biological traits of macrobenthic fauna to a eutrophication gradient in a semi-enclosed bay, China - Yifeng Shi; Yixuan He; Paul K.S. Shin; Yu Guo; Guodong Zhang; Yujian Wen; Guicheng Zhang; Wenzhe Xu; Jun Sun (Marine Environmental Research, 2023)

Effects of circadian rhythm on behavior and physiology of the sea cucumber Apostichopus japonicus - Zihe Zhao; Yushi Yu; Huiyan Wang; Xiyuan Huang; Peng Ding; Yingzhuo Sun; Jun Ding; Yaqing Chang; Chong Zhao (Marine Environmental Research, 2023)

Kinetics and mechanism study of dyes degradation in electric field-promoting catalytic wet air oxidation process - Lin-Feng Zhai; Yi Hu; Shu-Ya Xu; He-You Guo; Min Sun; Jun Yu; Yan Wang (Journal of Environmental Management, 2023)

Tuning strong metal-support interactions to boost activity and stability of aluminium nitride supported nickel catalysts for dry reforming of methane - Shuqing Li; Yu Fu; Wenbo Kong; Jiyang Wang; Changkun Yuan; Bingrong Pan; He Zhu; Xia Chen; Yidan Zhang; Jun Zhang; Yuhan Sun (Fuel, 2023)

Experimental study on seismic performance of novel precast concrete beam-column joints using mechanical connections - Chuanzhi Sun; Mei-Ling Zhuang; Liutao Bai; Li Gao; Changrong Yu; Jun Yang; Hanbo Zhu; Yan Qiao; Yuefeng Shao; Weihua Zhang (Bulletin of Earthquake Engineering, 2023)

Genome-wide identification and expression analysis of SnRK2 gene family in common bean (Phaseolus vulgaris L.) in response to abiotic stress - De-Bao Cai; Xin-Ying Sun; Yu-Peng Zhang; Shu-Qiong Yang; Jun Zhang; Ji-Bao Chen (Biologia, 2023)

Octyl gallate targeting the 3C-like protease exhibits highly efficient antiviral activity against swine enteric coronavirus PEDV - Mingjun Su; Baishuang Yin; Xiaoxu Xing; Zijian Li; Jiyu Zhang; Shufeng Feng; Lu Li; Feiyu Zhao; Xu Yang; Shiping Yu; Jun Wang; Yongchen Zhang; et al. (Veterinary Microbiology, 2023)

Comparison of the cross-protection of PPRSV sublineage 8.7 MLV vaccines against the recombinant NADC30-like strain - Jianda Li; Kai Meng; Yu Wang; Zhao Wang; Jun Peng; Sufang Ren; Yuyu Zhang; Lihui Guo; Fei Liu; Tingting Lv; Jian Jiao; Yanyan Liu; et al. (Veterinary Microbiology, 2023)

One global disseminated 193 kb high-risk hybrid plasmid harboring tet(X4), mcr or blaNDM threatening public health - Min Li; Haoran Zhang; Wengang Zhang; Ying Cao; Bingqing Sun; Qin Jiang; Yu Zhang; Haodong Liu; WenNan Guo; Cheng Chang; Nan Zhou; Chao Lv; et al. (Science of The Total Environment, 2023)

Sex-specific effect of perfluoroalkyl substances exposure on liver and thyroid function biomarkers: A mixture approach - Ze Yang; Ruifang Liu; Hongbo Liu; Jiemin Wei; Xiaohui Lin; Mingyue Zhang; Yu Chen; Jingyun Zhang; Meiqing Sun; Zhe Feng; Jian Liu; Xiangyang Liu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Bacterial community mapping of the AIA mouse gastrointestinal tract under dietary intervention with skipjack tuna (Katsuwonus pelamis) elastin peptides - Qiaoli Wu; Bing Liu; Rongxian Yu; Xiaoling Sun; Ziyan Wang; Jun Zhou; Chenyang Lu; Haitao Wan; Jing Zhang; Jiaojiao Han; Xiurong Su (Food Bioscience, 2023)

RETRACTED ARTICLE: MiR-125 family improves the radiosensitivity of head and neck squamous cell carcinoma - Qi-Wei Wang; Ya-Nan Sun; Li-Jun Tan; Jian-Nan Zhao; Xiao-Jie Zhou; Tian-Jiao Yu; Jiang-Tao Liu (Molecular Biology Reports, 2023)
Background MiRNAs can affect the radiosensitization of head and neck squamous cell carcinoma (HNSCC). We aimed to analyze the function of miR-125 family members in HNSCC using The Cancer Genome Atlas (TCGA) and determine their effect on radiation in laryngeal squamous cell cancer (LSCC). Methods First, we systematically analyzed the role of the miR-125 family in HNSCC using the TCGA database and found that miR-125a-5p is associated with radiotherapy. We then performed comprehensive enrichment analysis of miR-125a-5p and predicted target genes. Then, we performed transfection, cell proliferation assays, reverse transcription polymerase chain reaction, apoptosis assays, micronucleus tests, and western blotting on hep-2 cells selected with puromycin. Results MiR-125 family members exhibited significantly different expression in HNSCC. They were significantly associated with tumor–node–metastasis staging, clinical stages, and histological grades. Radiation therapy had a statistically effect on miR-125 family members, except miR-125a-3p. Moreover, miR-125a-5p was related to overall survival in LSCC. Thus, we predicted 110 target genes and seven hub genes of miR-125a-5p. The proliferation rate of cells transfected with lentivirus vector expressing miR-125a-5p was significantly reduced compared to the other groups. The radiation effect was enhanced in cells transfected with miR-125a-5p. The ratio of apoptotic cells transfected and exposed to X-rays (10 Gy) was distinctly higher than that of the Ad-control group. Western blotting analysis revealed that miR-125a-5p upregulated the apoptotic regulators P53 and rH2AX. Thus, miR-125a-5p may increase radiosensitivity in LSCC via upregulation of pro-apoptotic genes. Conclusions MiR-125 family members could be prognostic biomarkers of HNSCC and improve HNSCC sensitivity to radiotherapy by activating P53. Upregulating miR-125a-5p via lentivirus vectors may be a novel strategy to strengthen the effect of radiotherapy on LSCC.

RETRACTED: PBAT/PLA humic acid biodegradable film applied on solar greenhouse tomato plants increased lycopene and decreased total acid contents - Lu Lu; Ying Han; Jiayin Wang; Jing Xu; Yansu Li; Mintao Sun; Fujian Zhao; Chaoxing He; Yujun Sun; Yijia Wang; Pengfei Huang; Xianchang Yu; et al. (Science of The Total Environment, 2023)

A 209,000-year-old history of methane seepage activity controlled by multiple factors in the South China Sea - Ganglan Zhang; Jun Cao; Yinan Deng; Hongfei Lai; Xuexiao Jiang; Yunxin Fang; Zenggui Kuang; Shengxiong Yang; Qianyong Liang; Piaoer Fu; Tiantian Sun; Meng Jin; et al. (Marine and Petroleum Geology, 2023)

Characteristics of changes in volatile organic compounds and microbial communities during the storage of pickles - Xi-han Sun; Xin Qi; Yu-di Han; Zhi-jun Guo; Cheng-bi Cui; Chang-qing Lin (Food Chemistry, 2023)

Determination of dry soil layer and its soil heat flux distribution using actively heated distributed temperature sensing - Meng-Ya Sun; Bin Shi; Yu-Jun Cui; Chao-Sheng Tang; Xing Zheng; Jin Liu; Zi Ying; Yi-Jie Sun; Yun-Qiang Wang; Jing-Xiong Zhou (Engineering Geology, 2023)

Intelligent shielding material based on VO2 with tunable near-field and far-field electromagnetic response - Si-Yuan Liao; Xiao-Yun Wang; Hai-Peng Huang; Yu-Ying Shi; Qiao-Feng Wang; You-Gen Hu; Peng-Li Zhu; Rong Sun; Ching-Ping Wong; Yan-Jun Wan (Chemical Engineering Journal, 2023)

Collocalia birds inspired Janus-structured bandage with strong wet tissue adhesion for rapid hemostasis and wound healing - Chao Hui; Yuan Gao; Bing-Yu Yan; Li-Qiang Ding; Tian-Cai Sun; Zhong Liu; Seeram Ramakrishna; Yun-Ze Long; Jun Zhang (Chemical Engineering Journal, 2023)

The phosphorus limitation in the post-fire forest soils increases soil CO2 emission via declining cellular carbon use efficiency and increasing extracellular phosphatase - Muhammad Auwal; Han Sun; U.K Adamu; Jun Meng; Lukas Van Zwieten; Bhupinder Pal Singh; Yu Luo; Jianming Xu (CATENA, 2023)

A strategy to maximize astaxanthin production from Haematococcus pluvialis in a cost-effective process by utilizing a PBR-LGP-PBR array (PLPA) hybrid system using light guide panel (LGP) and solar cells - Ju Yeon Lee; Byung Sun Yu; Won Seok Chang; Sang Jun Sim (Bioresource Technology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A20 ameliorates disc degeneration by suppressing mTOR/BNIP3 axis-mediated mitophagy - Xin Peng; Cong Zhang; Jia-Wei Gao; Feng Wang; Jun-Ping Bao; Zhi-Min Zhou; Rui Sun; Hang-Yu Ji; Cabral VLF; Xiao-Tao Wu (Genes & Genomics, 2023)

An enhanced tilted-angle acoustic tweezer for mechanical phenotyping of cancer cells - Hanlin Wang; Joe Boardman; Xiaoyan Zhang; Chao Sun; Meng Cai; Jun Wei; Zhiqiang Dong; Mingqian Feng; Dongfang Liang; Sheng Hu; Yu Qian; Shuang Dong; et al. (Analytica Chimica Acta, 2023)

Sparse Gaussian processes for multi-step motion prediction of space tumbling objects - Min Yu; Jianjun Luo; Mingming Wang; Chuankai Liu; Jun Sun (Advances in Space Research, 2023)

Aestuariibaculum lutulentum sp. nov., a marine bacterium isolated from coastal sediment in Beihai - Jia-Wei Gao; Dong-Yan He; Wen-Wu Zhang; Yu-Ruo Wang; Yue Su; Jun-Jie Ying; Zhi-Cheng Wu; Wu Qu; Lin Xu; Cong Sun (Archives of Microbiology, 2023)

Effective PFAS degradation by electrochemical oxidation methods-recent progress and requirement - Maryam Mirabediny; Jun Sun; Tsz Tin Yu; Björn Åkermark; Biswanath Das; Naresh Kumar (Chemosphere, 2023)

Study on wave attenuation on a coral reef flat in SCS by in-situ measurement and simulation - Wenwei Chen; Xiaolong Liu; Zhiwen Cai; Ze Sun; Jun Yu; Haihua Zhang (Ocean Modelling, 2023)

Evaluating response mechanisms of soil microbiomes and metabolomes to Bt toxin additions - Lei Ge; Lili Song; Luyao Wang; Yujie Li; Yu Sun; Cui Wang; Jun Chen; Guogan Wu; Aihu Pan; Yunfei Wu; Zhexue Quan; Peng Li (Journal of Hazardous Materials, 2023)

Proteomic analysis reveals differential responsive mechanisms in Solanum nigrum exposed to low and high dose of cadmium - Ling-Yu Song; Xiang Liu; Lu-Dan Zhang; Wen-Jun Hu; Chao-Qun Xu; Jing Li; Shi-Wei Song; Ze-Jun Guo; Chen-Yang Sun; Han-Chen Tang; Ji-Cheng Wang; Xue-Yi Zhu; et al. (Journal of Hazardous Materials, 2023)

“Two-in-one” dual-function luminescent MOF hydrogel for onsite ultra-sensitive detection and efficient enrichment of radioactive uranium in water - An-Qi Cui; Xiao-Yi Wu; Jun-Bin Ye; Gang Song; Di-Yun Chen; Jie Xu; Yu Liu; Jia-Ping Lai; Hui Sun (Journal of Hazardous Materials, 2023)

Preclinical Evaluation of an Everolimus-Eluting Bioresorbable Vascular Scaffold Via a Long-Term Rabbit Iliac Artery Model - Dae Sung Park; Myung Ho Jeong; Yu Jeong Jin; Mi Hyang Na; Doo Sun Sim; Munki Kim; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; Jeong Ha Kim; Kyung Seob Lim; Jun-Kyu Park; et al. (Tissue Engineering and Regenerative Medicine, 2023)

Truncated glycoprotein E of varicella-zoster virus is an ideal immunogen for Escherichia coli-based vaccine design - Tingting Chen; Jie Sun; Sibo Zhang; Tingting Li; Liqin Liu; Wenhui Xue; Lizhi Zhou; Siting Liang; Zhili Yu; Qingbing Zheng; Hai Yu; Tong Cheng; et al. (Science China Life Sciences, 2023)

Effects of mowing on Pb accumulation and transport in Cynodon dactylon (L.) Pers - Xinyi Cai; Xi Li; Lingli Peng; Yahao Liang; Mingyan Jiang; Jun Ma; Lingxia Sun; Baimeng Guo; Xiaofang Yu; Juan Du; Nian Li; Shizhen Cai (Environmental Science and Pollution Research, 2023)

Evaluation of BDE-47-induced neurodevelopmental toxicity in zebrafish embryos - Juan Zhuang; Zheng-jun Pan; Ying Qin; Hui Liang; Wen-feng Zhang; Ze-yu Sun; Han-bo Shi (Environmental Science and Pollution Research, 2023)

Deciphering basic and key traits of antibiotic resistome in influent and effluent of hospital wastewater treatment systems - Lin Zhu; Ling Yuan; Xin-Yi Shuai; Ze-Jun Lin; Yu-Jie Sun; Zhen-Chao Zhou; Ling-Xuan Meng; Feng Ju; Hong Chen (Water Research, 2023)

Benzimidazole fungicide biotransformation by comammox Nitrospira bacteria: Transformation pathways and associated proteomic responses - Ping Han; Ana B. Rios-Miguel; Xiufeng Tang; Yaochun Yu; Li-Jun Zhou; Lijun Hou; Min Liu; Dongyao Sun; Mike S.M. Jetten; Cornelia U. Welte; Yujie Men; Sebastian Lücker (Journal of Hazardous Materials, 2023)

New insights into the microbial-driven metal reductive dissolution for enhanced phosphorus release from iron-rich sludge - Ruo-hong Li; Wei-jun Wang; Ren-xin Zhao; Jia-yu Zhang; Lianpeng Sun; Xiao-yan Li; Bing Li (Journal of Cleaner Production, 2023)

Distribution, source identification and ecological effects of aerosol dissolved nutrients in the Bohai Bay - Xudong Cui; Liying Peng; Yu Guo; Guicheng Zhang; Haijiao Liu; Yujian Wen; Guodong Zhang; Jun Sun (Environmental Pollution, 2023)

Enhanced astaxanthin production of Haematococcus pluvialis strains induced salt and high light resistance with gamma irradiation - Ha Eun Yang; Byung Sun Yu; Sang Jun Sim (Bioresource Technology, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

A self-circulating electro-fenton-like process over Fe3O4–CaO2 cathode for highly efficient degradation of levofloxacin - Yangyang Bai; Xiaoqin Sun; Yuan Dang; Sha Yu; Jun-Jie Zhu; Yuanzhen Zhou (Chemosphere, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

New sustainable Mannich-functionalized lignin flocculants for ultra-efficiently tailoring wastewater purification - Bin Wang; Xue-Fei Cao; Shi-Xin Yu; Zhuo-Hua Sun; Xiao-Jun Shen; Jia-Long Wen; Tong-Qi Yuan (Journal of Cleaner Production, 2023)

Simultaneous sludge minimization and membrane fouling mitigation in membrane bioreactors by using a microaerobic - Settling pretreatment module - Yi Zuo; Yanjun Shao; Lihua Wang; Yiyue Sun; Ying An; Lu-Man Jiang; Nan Yu; Rujie Hao; Chuanting Zhou; Jun Tao; Zhen Zhou (Journal of Environmental Management, 2023)

Co-substrate promoting the biodegradation of refractory DOM in semi-coking wastewater: DOM evolution and microbial community - Min-Hui Cai; Ye-Chao Tian; Ai-Min Li; Yan Li; Yu-Ze Han; Jun Li; Hong-Fang Sun; Xin Wang; Qing Zhou; Wen-Tao Li (Journal of Environmental Chemical Engineering, 2023)

Time evolution of elastic stiffness coefficients for a jack-up spudcan in clay during operation - Xiu Zhe Wang; Jiang Tao Yi; Miao Jun Sun; Qiang Xie; Yu Tao Pan (Computers and Geotechnics, 2023)

Interfacial coupled engineering of plasmonic amorphous MoO3-x nanodots/g-C3N4 nanosheets for photocatalytic water splitting and photothermal conversion - Yumei Ren; Desheng Feng; Zhiming Yan; Zixu Sun; Zixuan Zhang; Dongwei Xu; Chong Qiao; Zhonghui Chen; Yu Jia; Seong Chan Jun; Shude Liu; Yusuke Yamauchi (Chemical Engineering Journal, 2023)

Unveiling the enhancement essence on Li2S deposition by the polarized topological β-polyvinylidene fluoride: Beyond built-in electric field effect - Guo Wen Sun; Meng Jing Jin; Qian Yu Liu; Chao Yue Zhang; Jiang Long Pan; Yan Chun Wang; Xiu Ping Gao; Geng Zhi Sun; Xiao Jun Pan; Jin Yuan Zhou (Chemical Engineering Journal, 2023)

Isolation, characterization and functional validation of a soybean transcription factor, GmDof4.2 improves drought tolerance in transgenic tobacco - Ying Zhai; Jiongxin Chen; Jiaqi He; Jun Zhang; Wei Sha; Haiwei Yu; Yan Zhao; Tianyi Ma; Tianguo Sun; Meijuan Zhang; Shanshan Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Dopaminergic Dysfunction and Glucose Metabolism Characteristics in Parkin-Induced Early-Onset Parkinson’s Disease Compared to Genetically Undetermined Early-Onset Parkinson’s Disease - Feng-Tao Liu; Jia-Ying Lu; Yi-Min Sun; Ling Li; Yu-Jie Yang; Jue Zhao; Jing-Jie Ge; Ping Wu; Jie-Hui Jiang; Jian-Jun Wu; Chuan-Tao Zuo; Jian Wang (Phenomics, 2023)

Changes in aquaporins expression due to acute water restriction in naturally aging mice - So-Jeong Kim; Kyung-Wan Baek; Youn-Kwan Jung; Ji-Seok Kim; Bo-Gyu Kim; Hak Sun Yu; Jin Sung Park; Jun-Il Yoo (Journal of Physiology and Biochemistry, 2023)

Development and application of a multiplex qPCR assay for the detection of duck circovirus, duck Tembusu virus, Muscovy duck reovirus, and new duck reovirus - Yan Wen Yin; Chenyong Xiong; Kai Chuang Shi; Shou Yu Xie; Feng Long; Jun Li; Min Zheng; Xian Kai Wei; Shuping Feng; Sujie Qu; Wenjun Lu; Hongjin Zhou; et al. (Virus Genes, 2023)

The effect of nitrite and nitrate treatment on growth performance, nutritional composition and flavor-associated metabolites of grass carp (Ctenopharyngodon idella) - Jun-Ming Zhang; Bing Fu; Yi-chao Li; Jin-Hui Sun; Jun Xie; Guang-Jun Wang; Jing-Jing Tian; Gen Kaneko; Er-Meng Yu (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Transport of functional group modified polystyrene nanoplastics in binary metal oxide saturated porous media - Guangcai Zhang; Qiang Ma; Mengdie Yu; Jing Yin; Huimin Sun; Nong Wang; Jun Wang; Xianqiang Yin (Journal of Hazardous Materials, 2023)

Effects of different pretreatment methods on drying kinetics, three-dimensional deformation, quality characteristics and microstructure of dried apple slices - Jun-Wen Bai; Lu Zhang; Joshua H. Aheto; Jian-Rong Cai; Yu-Chi Wang; Li Sun; Xiao-Yu Tian (Innovative Food Science & Emerging Technologies, 2023)

Terrestrial rather than volcanic mercury inputs to the Yangtze Platform (South China) during the Ordovician-Silurian transition - Yu Liu; Yuanchun Li; Mingcai Hou; Jun Shen; Thomas J. Algeo; Junxuan Fan; Xiaolin Zhou; Qing Chen; Zongyuan Sun; Chao Li (Global and Planetary Change, 2023)

Dual-site oxygen activation for enhanced photocatalytic aerobic oxidation by S-scheme Ni2P/Bi3O4Br-OVs heterojunction - Weijie Yang; Kailong Sun; Jun Wan; Yang-Ai Ma; Yu Wang; Lin Liu; Bicheng Zhu; Feng Fu (Chemical Engineering Journal, 2023)

Influence of degree of compaction on arsenic and antimony co-contaminated soil stabilization: Geoenvironmental properties and chemical species - Shi-Ji Zhou; Ya-Song Feng; Guang-Yu Yang; Hui-Yang Sun; Qing Zhang; Yang Hu; Yan-Jun Du (CATENA, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

Characterization and genomic analysis of JC01, a novel bacteriophage infecting Cronobacter sakazakii - Jie Jiang; Guanda Lan; Jinghua Li; Jun Yu; Honglan Huang; Yanbo Sun; Cuiting Xu; Dandan Liu; Yunwei Gong; Chunyan Zhao (Archives of Virology, 2023)
The lytic bacteriophage JC01 was isolated using a strain of Cronobacter sakazakii previously isolated from powdered infant formula (PIF). The complete genome sequence of phage JC01 was determined. The double-stranded DNA genome of phage JC01 is composed of 61,736 bp with a G + C content of 58.9%, and it contains 76 putative open reading frames (ORFs) without any tRNA genes. The predicted ORFs were classified into functional groups, including DNA manipulation, transcription, phage packaging, phage structure, host lysis, and hypothetical proteins. Based on overall nucleotide sequence comparisons, calculation of phage intergenomic similarities, and phylogenetic analysis, JC01 appears to be a novel bacteriophage infecting C. sakazakii .

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Glycoproteomic analysis reveals the effects of bisecting GlcNAc in intrahepatic cholangiocarcinoma - Wei Dan; Cheng Li; Jun Li; Pengfei Li; Miaomiao Xin; Zexuan Chen; Liuyi Dang; Zihao Yu; Jing Li; Jiechen Shen; Liangshuo Hu; Shisheng Sun (Glycoconjugate Journal, 2022)

Immunogenicity and protective efficacy of a DNA vaccine inducing optimal expression of the SARS-CoV-2 S gene in hACE2 mice - Zhuo-xin Li; Sheng Feng; He Zhang; Xin-yu Zhuang; Chao Shang; Shi-yu Sun; Ji-cheng Han; Yu-biao Xie; Jin-yong Zhang; Wei Wang; Cheng-hui Li; Guan-yu Zhao; et al. (Archives of Virology, 2022)

Nitrogen-metabolising microorganism analysis in rapid sand filters from drinking water treatment plant - Qihui Gu; Jun Ma; Jumei Zhang; Weipeng Guo; Huiqing Wu; Ming Sun; Juan Wang; Xianhu Wei; Youxiong Zhang; Montong Chen; Liang Xue; Yu Ding; et al. (Environmental Science and Pollution Research, 2022)

Bifunctional Ni@NiO catalyst supported on loofah sponge-derived carbon for electrocatalytic air oxidation of biorefractory pollutant in a coupling system - Min Sun; Xiong-Fei Tao; Sheng-Nan Tang; Jun Yu; Yan Wang; Lin-Feng Zhai (Environmental Science and Pollution Research, 2022)

Chili residue and Bacillus laterosporus synergy impacts soil bacterial microbiome and agronomic performance of leaf mustard (Brassica juncea L.) in a solar ﻿greenhouse - Ibraheem Olamide Olasupo; Jun Wang; Xiaoxuan Wei; Mintao Sun; Yansu Li; Xianchang Yu; Yan Yan; Chaoxing He (Plant and Soil, 2022)

Fracture Mechanical Properties of Three—Dimensional Irregular Sandstone Particles Based on Digital-Image - Kai-wen Shi; Yu-jun Zuo; Wen-ji-bin Sun; Hao Liu; Jian-yun Lin; Tao-tao Li; Bin Chen; Lu-lin Zheng (Geotechnical and Geological Engineering, 2022)

Toxicokinetics and metabolism of deoxynivalenol in animals and humans - Yu Sun; Jun Jiang; Peiqiang Mu; Ruqin Lin; Jikai Wen; Yiqun Deng (Archives of Toxicology, 2022)

Paracandidimonas lactea sp. nov., a urea-utilizing bacterium isolated from landfill - Chu Zhang; Qian Pu; Jun-jie Ying; Ying Chen; Cheng-ze Li; Hang-tao Wu; Bin-jie Wang; Yu-han Zhang; Guo-hong Zeng; Ou Li; Xiu-fang Hu; Cong Sun (Archives of Microbiology, 2022)

Study on the seasonal variations of dimethyl sulfide, its precursors and their impact factors in the Bohai Sea and North Yellow Sea - Yu Guo; Liying Peng; Zishi Liu; Xiaoting Fu; Guicheng Zhang; Ting Gu; Danyang Li; Jun Sun (Frontiers in Marine Science, 2022)
Dimethyl sulfide (DMS) is one of the most important volatile biogenic sulfur compounds and plays a significant role in global climate change. Studying the seasonal variations and the environmental factors that affect the concentration of DMS would aid in understanding the biogeochemical cycle of sulfur compounds. Using benzene-assisted photoionization positive ion mobility spectrometry (BAPI-PIMS), the seasonal distribution and the key impact factors of DMS and dimethylsulfoniopropionate (DMSP) in the Bohai Sea and North Yellow Sea were investigated in the summer and autumn of 2019. The concentrations of DMS and its precursors, DMSPp and DMSPd, in the surface seawater were 0.11–23.90, 0.67–41.38, and 0.03–12.28 nmol/L, respectively, in summer, and 0.10–20.79, 0.39–13.51, and 0.18–20.58 nmol/L, respectively, in autumn. The air-to-sea exchange flux of DMS was 43.05 ± 44.52 and 34.06 ± 63.38 μmol/(m·d), respectively, in summer and autumn. The results demonstrated that the temperature was the most dominant environmental factor, and the abundance of dinoflagellates was the most dominant biological factor that affected the distribution of DMS and DMSP in summer. The abundance of diatoms was the most dominant biological factor, and the levels of PO 4 3- , NO 2 - , NO 3 - , and SiO 3 2- were the dominant environmental factors that affected the distribution of DMS and DMSP in autumn. These results of this study would be of great significance in understanding the biochemical cycle of DMS in BS and NYS.

Effect of confining pressure on the fracture mechanical properties of multi-particle sandstone - Kai-wen Shi; Yu-jun Zuo; Wenjibin Sun; Hao Liu; Chao Pan; Taotao Li; Bin Chen; Jian-yun Lin (Arabian Journal of Geosciences, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Characteristics and influencing factors of frontal upwelling in the Yellow Sea in summer - Fan Sun; Fei Yu; Guangcheng Si; Jianfeng Wang; Anqi Xu; Jun Pan; Ying Tang (Acta Oceanologica Sinica, 2022)

Impact of heat stress on milk yield, antioxidative levels, and serum metabolites in primiparous and multiparous Holstein cows - Xue Chen; Jia Nan Dong; Ji Ye Rong; Jun Xiao; Wei Zhao; Natnael D. Aschalew; Xue Feng Zhang; Tao Wang; Gui Xin Qin; Zhe Sun; Yu Guo Zhen (Tropical Animal Health and Production, 2022)

Associations between species-level indoor microbiome, environmental characteristics, and asthma in junior high schools of Terengganu, Malaysia - Xi Fu; Yi Meng; Yanling Li; Xunhua Zhu; Qianqian Yuan; Aminnuddin Ma’pol; Jamal Hisham Hashim; Zailina Hashim; Gunilla Wieslander; Yi-Wu Zheng; Xu-Xin Lai; Michael Dho Spangfort; et al. (Air Quality, Atmosphere & Health, 2022)

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

Correction to: Arthrobacter wenxiniae sp. nov., a novel plant growth-promoting rhizobacteria species harbouring a carotenoids biosynthetic gene cluster - Yu-chen Sun; Pengbo Sun; Jing Xue; Yunpeng Du; Hui Yan; Li-wei Wang; Xin-xin Yi; Jian-guang Sun; Xiuhai Zhang; Jun-lian Gao (Antonie van Leeuwenhoek, 2022)

Microplastics in Sediment of Kuakata Beach, Bangladesh: Occurrence, Spatial Distribution, and Risk Assessment - Partho Banik; M. Belal Hossain; As-Ad Ujjaman Nur; Tasrina Rabia Choudhury; Samia Islam Liba; Jimmy Yu; Md. Abu Noman; Jun Sun (Frontiers in Marine Science, 2022)
Kuakata beach, known as Daughter of Sea in Bangladesh, has drawn a growing number of tourists from all over the world, leading to the higher use of single plastic products. This study was a first attempt to describe the occurrence, spatial distribution, and ecological risk of microplastics (MPs) in Kuakata beach sediments. A total of 24 surface sediment samples were collected from the intertidal zone of the beach, and MPs were extracted using the density separation method and a stereomicroscope. Fourier transform infrared (FTIR) spectroscopy was used for qualitative and quantitative identification. The results revealed that the average MPs in the beach sediment were 232 ± 52 items kg –1 dry weight, which was much higher than many other sandy beaches throughout the world. Analyses of variance showed a significant ( p < 0.01) difference among the mean abundance of MPs in sampling points. Fibers were dominated in every sampling point with an average of 123 ± 27 item kg –1 . Most of the MPs observed were colored (60%), and the rest were transparent (40%). It was found that the size range of 1–5 mm MPs constituted over half (55%) of total MPs covering an average value of 127 ± 34 items kg –1 . Three polymer types were identified in the sediment samples through FTIR analysis which followed the decreasing order of polyethylene terephthalate > polyethylene > polypropylene. Correlation analysis showed a positive relationship between the abundance of MPs and the finer grain size of sediment ( p = 0.055; r = 0.7), indicating grain size-controlled the density of MPs. The pollution load index was assessed to estimate the ecological risk and found that the beach sediment of Kuakata belonged to the risk category I of the pollution index. This investigation provided preliminary information on MPs pollution in the marine ecosystem that the policymakers can use to take appropriate management approaches.

Dissection of the practical soybean breeding pipeline by developing ZDX1, a high-throughput functional array - Rujian Sun; Bincheng Sun; Yu Tian; Shanshan Su; Yong Zhang; Wanhai Zhang; Jingshun Wang; Ping Yu; Bingfu Guo; Huihui Li; Yanfei Li; Huawei Gao; et al. (Theoretical and Applied Genetics, 2022)
Key message We developed the ZDX1 high-throughput functional soybean array for high accuracy evaluation and selection of both parents and progeny, which can greatly accelerate soybean breeding. Abstract Microarray technology facilitates rapid, accurate, and economical genotyping. Here, using resequencing data from 2214 representative soybean accessions, we developed the high-throughput functional array ZDX1, containing 158,959 SNPs, covering 90.92% of soybean genes and sites related to important traits. By application of the array, a total of 817 accessions were genotyped, including three subpopulations of candidate parental lines, parental lines and their progeny from practical breeding. The fixed SNPs were identified in progeny, indicating artificial selection during the breeding process. By identifying functional sites of target traits, novel soybean cyst nematode-resistant progeny and maturity-related novel sources were identified by allele combinations, demonstrating that functional sites provide an efficient method for the rapid screening of desirable traits or gene sources. Notably, we found that the breeding index (BI) was a good indicator for progeny selection. Superior progeny were derived from the combination of distantly related parents, with at least one parent having a higher BI. Furthermore, new combinations based on good performance were proposed for further breeding after excluding redundant and closely related parents. Genomic best linear unbiased prediction (GBLUP) analysis was the best analysis method and achieved the highest accuracy in predicting four traits when comparing SNPs in genic regions rather than whole genomic or intergenic SNPs. The prediction accuracy was improved by 32.1% by using progeny to expand the training population. Collectively, a versatile assay demonstrated that the functional ZDX1 array provided efficient information for the design and optimization of a breeding pipeline for accelerated soybean breeding.

The improved coupling coordination analysis on the relationship between climate, eco-environment, and socio-economy - Yu Jiang; Min Chen; Jun Zhang; Zhihao Sun; Zhuowen Sun (Environmental and Ecological Statistics, 2022)

Isolation and characterization of 34 SNP markers in Acipenser baerii - Quan Gong; Qingzhi Li; Jiahua Sun; Yu Xiao; Xutao Su; Guangxun Liu; Jun Du; Jue Lin (Conservation Genetics Resources, 2022)

Arthrobacter wenxiniae sp. nov., a novel plant growth-promoting rhizobacteria species harbouring a carotenoids biosynthetic gene cluster - Yu-chen Sun; Pengbo Sun; Jing Xue; Yunpeng Du; Hui Yan; Li-wei Wang; Xin-xin Yi; Jian-guang Sun; Xiuhai Zhang; Jun-lian Gao (Antonie van Leeuwenhoek, 2022)

Four new prenylflavonol glycosides from the leaves of Cyclocarya paliurus - Zi-Jun Ye; Hui-Hui Sun; Zu-Hui Chen; Jian-Ping Wu; Jing Li; Hui Zhu; Lu-Lu Huang; Xi-Wen Chang; Sai-Yu Ou; Wen-Xuan Wang; Xiao-Ai He; Gang-Zhi Zhu; et al. (Natural Product Research, 2022)

Genetic diversity and structure of Oncomelania hupensis hupensis in two eco-epidemiological settings as revealed by the mitochondrial COX1 gene sequences - Jie-Ying Zhang; Man-Man Gu; Qiu-Fu Yu; Meng-Tao Sun; Hui-Ying Zou; Zhi-Jun Zhou; Da-Bing Lu (Molecular Biology Reports, 2022)

Alteribacter salitolerans sp. nov., isolated from a saline-alkaline soil - Shuang Wang; Lei Sun; Manik Prabhu Narsing Rao; Guo-Hong Liu; Pin-Jiao Jin; Zhou-Yan Dong; Zheng-Han Lian; Xiao-Yu Hao; Ming-Yi Zhang; Wen-Jun Li (Archives of Microbiology, 2022)

Identification and functional analysis of a pollen fertility-associated gene GhGLP4 of Gossypium hirsutum L. - Hongli Zheng; Rongjia Wang; Qimeng Jiang; Diandian Zhang; Rongrong Mu; Yihan Xu; Vitalis E. Nnaemeka; Jun Mei; Yanyan Zhao; Fangfang Cai; Dongliang Yu; Yuqiang Sun; et al. (Theoretical and Applied Genetics, 2021)

Correction to: The CsGPA1-CsAQPs module is essential for salt tolerance of cucumber seedlings - Yan Yan; Mintao Sun; Yansu Li; Jun Wang; Chaoxing He; Xianchang Yu (Plant Cell Reports, 2021)

A landslide in Heifangtai, northwest of the Chinese Loess Plateau: triggered factors, movement characteristics, and failure mechanism - Jia-xu Kong; Jian-qi Zhuang; Jie-wei Zhan; Zheng-wei Bai; Yan-qiu Leng; Peng-hui Ma; Jian-bing Peng; Zuo-peng Wang; Tian-feng Gu; Jia-xing Sun; Fan-chen Zhang; Yuan-jun Xu; et al. (Landslides, 2021)

Fluorescence Characteristics of Chromophoric Dissolved Organic Matter in the Eastern Indian Ocean: A Case Study of Three Subregions - Yang Liu; Jun Sun; Xingzhou Wang; Xiaofang Liu; Xi Wu; Zhuo Chen; Ting Gu; Weiqiang Wang; Linghui Yu; Yu Guo; Yujian Wen; Guodong Zhang; et al. (Frontiers in Marine Science, 2021)
Comprising one of the major carbon pools on Earth, marine dissolved organic matter (DOM) plays an essential role in global carbon dynamics. The objective of this study was to better characterize DOM in the eastern Indian Ocean. To better understand the underlying mechanisms, seawater samples were collected in October and November of 2020 from sampling stations in three subregions: the mouth of the Bay of Bengal, Southern Sri Lanka, and Western Sumatra. We calculated and evaluated different hydrological parameters and organic carbon concentrations. In addition, we used excitation emission matrix (EEM) spectroscopy combined with parallel factor analysis (PARAFAC) to analyze the natural water samples directly. Parameters associated with chromophoric DOM did not behave conservatively in the study areas as a result of biogeochemical processes. We further evaluated the sources and processing of DOM in the eastern Indian Ocean by determining four fluorescence indices (the fluorescence index, the biological index, the humification index, and the freshness index β / α). Based on EEM-PARAFAC, we identified six components (five fluorophores) using the peak picking technique. Commonly occurring fluorophores were present within the sample set: peak A (humic-like), peak B (protein-like), peak C (humic-like), and peak T (tryptophan-like). The fluorescence intensity levels of the protein-like components (peaks B and T) were highest in the surface ocean and decreased with depth. In contrast, the ratio of the two humic-like components (peaks A and C) remained in a relatively narrow range in the bathypelagic layer compared to the surface layer, which indicates a relatively constant composition of humic-like fluorophores in the deep layer.

Vertical Fine-Scale Distribution of Calanus sinicus in the Yellow Sea Cold Water Mass During the Over-Summering Process - Jun Pan; Fangping Cheng; Fei Yu; Yongqiang Shi; Fan Sun; Guangcheng Si; Chuanjie Wei; Xinyuan Diao; Yongfang Zhao (Frontiers in Marine Science, 2021)
Calanus sinicus , a temperate copepod with a lethal temperature >27°C, is one of the key species in Chinese coastal marine ecosystems. The C. sinicus population increases in spring and declines in early summer annually due to increasing water temperature. Numerous C. sinicus individuals then congregate in the Yellow Sea Cold Water Mass (YSCWM) and remain under the thermocline from early summer to early autumn. Development and reproduction is halted in this cold and foodless bottom water and they avoid ascending to the hot surface water, which is regarded as an over-summering strategy. Based on discrete water sampling approaches, previous studies demonstrated that higher chlorophyll a (Chl a) levels appeared in the mixed hot surface water layer; however, the subsurface chlorophyll a maximum layer (SCML) has seldom been described. In the present study, various probes and a visual plankton recorder (VPR) were used to determine the fine vertical distributions of environmental factors and C. sinicus . VPR observations showed the ecological responses in fine scale and indicated that few C. sinicus individuals ascend at night, the main population preferred to remain below the SCML all day long. The results demonstrated that a constant thin SCML existed in the YSCWM area, and that the SCML location coincided with or was beneath the thermocline and halocline layers, where the temperature was suitable for C. sinicus . The relationship between abundance and Chl a, showed the diel vertical migration trend of C. sinicus to feed at night in the YSCWM area. In addition to temperature as a main influencing factor, dissolved oxygen concentrations and column depth were also influencing factors. Therefore, in addition to avoiding high surface temperature, energy supplement may be an important driving force confining the diel vertical migration of C. sinicus in the Yellow Sea in summer.

Constraints on late cenozoic tectonics in the Southern Longmen Shan: evidence from low-temperature thermochronology - You Zhou; Zhong-Hai Wu; Yu-Jun Sun; Guo-Can Wang; Ji-Long Wang (International Geology Review, 2021)

Baicalin attenuates adriamycin-induced nephrotic syndrome by regulating fibrosis procession and inflammatory reaction - Ning Tan; Chen-Xia Sun; Hui-Jun Zhu; De-Yu Li; Sheng-Guang Huang; Shou-Di He (Genes & Genomics, 2021)

Application of Plant Print Identification Technology in Salt-resistant Soybean Breeding - Yan Li; Xia Li; Zi-qi Chen; Ying Ma; Guang-yu Yang; Ying Zhang; Ming-chun Sun; Li-hong Zhang; Jin-meng Chu; Jing-mei Lu; Jun Zhu; Ji-hong You (Journal of Plant Growth Regulation, 2021)

Caulobacter endophyticus sp. nov., an endophytic bacterium harboring three lasso peptide biosynthetic gene clusters and producing indoleacetic acid isolated from maize root - Jun-lian Gao; Pengbo Sun; Yu-chen Sun; Jing Xue; Guoliang Wang; Li-wei Wang; Yunpeng Du; Xiuhai Zhang; Jian-guang Sun (Antonie van Leeuwenhoek, 2021)

Numerical simulation on the stability of rock slope based on an improved SPH Method - Shu-yang Yu; Xu-hua Ren; Ji-xun Zhang; Hai-jun Wang; Zhao-hua Sun; Yu Zhou (Journal of Mountain Science, 2021)

Tamlana haliotis sp. nov., isolated from the gut of the abalone Haliotis rubra - Wen-Rui Cao; Bang-Tao Liu; Xun-Ke Sun; Yuan-Yuan Sun; Ming-Yu Jiang; Zong-Jun Du (Archives of Microbiology, 2021)

A Study of Wave-Induced Effects on Sea Surface Temperature Simulations during Typhoon Events - Zhanfeng Sun; Weizeng Shao; Wupeng Yu; Jun Li (Journal of Marine Science and Engineering, 2021)
In this work, we investigate sea surface temperature (SST) cooling under binary typhoon conditions. We particularly focus on parallel- and cross-type typhoon paths during four typhoon events: Tembin and Bolaven in 2012, and Typhoon Chan-hom and Linfa in 2015. Wave-induced effects were simulated using a third-generation numeric model, WAVEWATCH III (WW3), and were subsequently included in SST simulations using the Stony Brook Parallel Ocean Model (sbPOM). Four wave-induced effects were analyzed: breaking waves, nonbreaking waves, radiation stress, and Stokes drift. Comparison of WW3-simulated significant wave height (SWH) data with measurements from the Jason-2 altimeter showed that the root mean square error (RMSE) was less than 0.6 m with a correlation (COR) of 0.9. When the four typhoon-wave-induced effects were included in sbPOM simulations, the simulated SSTs had an RMSE of 1 °C with a COR of 0.99 as compared to the Argos data. This was better than the RMSE and COR recovered between the measured and simulated SSTs, which were 1.4 °C and 0.96, respectively, when the four terms were not included. In particular, our results show that the effects of Stokes drift, as well as of nonbreaking waves, were an important factor in SST reduction during binary typhoons. The horizontal profile of the sbPOM-simulated SST for parallel-type typhoon paths (Typhoons Tembin and Bolaven) suggested that the observed finger pattern of SST cooling (up to 2 °C) was probably caused by drag from typhoon Tembin. SST was reduced by up to 4 °C for cross-type typhoon paths (Typhoons Chan-hom and Linfa). In general, mixing significantly increased when the four wave-induced effects were included. The vertical profile of SST indicated that disturbance depth increased (up to 100 m) for cross-type typhoon paths because the mixing intensity was greater for cross-type typhoons than for parallel-type typhoons.

Ziziphus jujuba Mill., a plant used as medicinal food: a review of its phytochemistry, pharmacology, quality control and future research - Shi-Jun Liu; Yan-Ping Lv; Zhi-Shu Tang; Yu Zhang; Hong-Bo Xu; Dong-Bo Zhang; Chun-Li Cui; Hong-Bo Liu; Huan-Huan Sun; Zhong-Xing Song; Si-Min Wei (Phytochemistry Reviews, 2021)

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Molecular Evolution and Local Root Heterogeneous Expression of the Chenopodium quinoa ARF Genes Provide Insights into the Adaptive Domestication of Crops in Complex Environments - Wenjun Sun; Haomiao Yu; Zhaotang Ma; Yuan Yuan; Sijiao Wang; Jun Yan; Xinran Xu; Hui Chen (Journal of Molecular Evolution, 2021)

Ruegeria haliotis sp. nov., Isolated from the Gut of the Abalone Haliotis rubra - Wen-Rui Cao; Dan-Dan Shang; Bang-Tao Liu; Yi-Hao Hu; Xun-Ke Sun; Yuan-Yuan Sun; Ming-Yu Jiang; Zong-Jun Du (Current Microbiology, 2021)

Nesterenkonia haasae sp. nov., an alkaliphilic actinobacterium isolated from a degraded pasture in Songnen Plain - Shuang Wang; Lei Sun; Dan Wei; Nimaichand Salam; Bao-Zhu Fang; Zhou-Yan Dong; Xiao-Yu Hao; Mingyi Zhang; Zhe Zhang; Wen-Jun Li (Archives of Microbiology, 2021)

The molecular mechanism of a novel derivative of BTO-956 induced apoptosis in human myelomonocytic lymphoma cells - Yu-Lin Li; De-Jun Zhou; Zheng-Guo Cui; Lu Sun; Qian-Wen Feng; Shahbaz Ahmad Zakki; Yusuke Hiraku; Cheng-Ai Wu; Hidekuni Inadera (Apoptosis, 2021)

NEAT1 Decreasing Suppresses Parkinson’s Disease Progression via Acting as miR-1301-3p Sponge - Qiang Sun; Yueliang Zhang; Songlin Wang; Fang Yang; Hongxia Cai; Yu Xing; Zengfeng Chen; Jun Chen (Journal of Molecular Neuroscience, 2021)

Effectiveness of Adding Antiplatelets to Oral Anticoagulants in Patients with Acute Ischemic Stroke with Atrial Fibrillation and Concomitant Large Artery Steno-Occlusion - Joon-Tae Kim; Ji Sung Lee; Beom Joon Kim; Jong-Moo Park; Kyusik Kang; Soo Joo Lee; Jae Guk Kim; Jae-Kwan Cha; Dae-Hyun Kim; Tai Hwan Park; Sang-Soon Park; Kyung Bok Lee; et al. (Translational Stroke Research, 2020)

Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

Geographical origin differentiation of Chinese Angelica by specific metal element fingerprinting and risk assessment - Lei Sun; Xiao Ma; Hong-Yu Jin; Chang-jun Fan; Xiao-dong Li; Tian-Tian Zuo; Shuang-Cheng Ma; Sicen Wang (Environmental Science and Pollution Research, 2020)

Solanrubiellin A, a hydroanthraquinone dimer with antibacterial and cytotoxic activity from Solanum lyratum - Hui Chen; Kun Du; Yan-Jun Sun; Zhi-You Hao; Yan-Li Zhang; Jiang Bai; Qing-Hua Wang; Hai-Yu Hu; Wei-Sheng Feng (Natural Product Research, 2020)

Impact of prophylactic/preemptive donor lymphocyte infusion and intensified conditioning for relapsed/refractory leukemia: a real-world study - Yu Wang; Qi-Fa Liu; De-Pei Wu; Jing-Bo Wang; Xi Zhang; Heng-Xiang Wang; Feng Gao; Shun-Qing Wang; Zi-Min Sun; Jian Ouyang; Kai-Lin Xu; Su-Jun Gao; et al. (Science China Life Sciences, 2020)

The CsGPA1-CsAQPs module is essential for salt tolerance of cucumber seedlings - Yan Yan; Mintao Sun; Yansu Li; Jun Wang; Chaoxing He; Xianchang Yu (Plant Cell Reports, 2020)

CCL19 suppresses gastric cancer cell proliferation, migration, and invasion through the CCL19/CCR7/AIM2 pathway - Rui Zhou; Jun Sun; Chunping He; Chao Huang; Honggang Yu (Human Cell, 2020)

The gut-microbiota-testis axis mediated by the activation of the Nrf2 antioxidant pathway is related to prepuberal steroidogenesis disorders induced by di-(2-ethylhexyl) phthalate - Tian-Xin Zhao; Yue-Xin Wei; Jun-Ke Wang; Lin-Dong Han; Mang Sun; Yu-Hao Wu; Lian-Ju Shen; Chun-Lan Long; Sheng-De Wu; Guang-Hui Wei (Environmental Science and Pollution Research, 2020)

QTL mapping for pre-harvest sprouting resistance in japonica rice varieties utilizing genome re-sequencing - Kyeong-Seong Cheon; Yong Jae Won; Young-Min Jeong; Youn-Young Lee; Do-Yu Kang; Jun Oh; Hyoja Oh; Song Lim Kim; Nyunhee Kim; Eungyeong Lee; In Sun Yoon; Inchan Choi; et al. (Molecular Genetics and Genomics, 2020)
Pre-harvest sprouting (PHS) leads to serious economic losses because of reductions in yield and quality. To analyze the quantitative trait loci (QTLs) for PHS resistance in japonica rice, PHS rates on panicles were measured in 160 recombinant inbred lines (RILs) derived from a cross between the temperate japonica varieties Odae (PHS resistant) and Unbong40 (PHS susceptible) under two different environmental conditions—field (summer) and greenhouse (winter) environments. Genome re-sequencing of the parental varieties detected 266,773 DNA polymorphisms including 248,255 single nucleotide polymorphisms and 18,518 insertions/deletions. We constructed a genetic map comprising 239 kompetitive allele-specific PCR and 49 cleaved amplified polymorphic sequence markers. In the field environment, two major QTLs, qPHS-3 FD and qPHS-11 FD , were identified on chromosomes 3 and 11, respectively, whereas three major QTLs, qPHS-3 GH , qPHS-4 GH , and qPHS-11 GH , were identified on chromosomes 3, 4, and 11, respectively, in the greenhouse environment. qPHS-11 GH and qPHS-11 FD had similar locations on chromosome 11, suggesting the existence of a gene conferring stable PHS resistance effects under different environmental conditions. The QTLs identified in this study can be used to improve the PHS resistance of japonica varieties, and they may improve our understanding of the genetic basis of PHS resistance.

A benchmark 1 g shaking table test of shallow segmental mini-tunnel in sand - Yong Yuan; Yusheng Yang; Shaohua Zhang; Haitao Yu; Jun Sun (Bulletin of Earthquake Engineering, 2020)

Extracellular ATP affects cell viability, respiratory O2 uptake, and intracellular ATP production of tobacco cell suspension culture in response to hydrogen peroxide-induced oxidative stress - Qin-zheng Hou; Yu-pei Wang; Bao-qiang Fan; Kun Sun; Jun-yu Liang; Han-qing Feng; Ling-yun Jia (Biologia, 2020)

Reconstructing the 3D digital core with a fully convolutional neural network - Qiong Li; Zheng Chen; Jian-Jun He; Si-Yu Hao; Rui Wang; Hao-Tao Yang; Hua-Jun Sun (Applied Geophysics, 2020)

Selective mGluR1 Negative Allosteric Modulator Reduces Blood–Brain Barrier Permeability and Cerebral Edema After Experimental Subarachnoid Hemorrhage - Cheng Zhang; Ming Jiang; Wei-qi Wang; Shi-jun Zhao; Yan-xin Yin; Qiong-jie Mi; Ming-feng Yang; Yu-qiang Song; Bao-liang Sun; Zong-yong Zhang (Translational Stroke Research, 2020)

Haploidentical stem cell transplantation in patients with chronic myelomonocytic leukemia - Yu-Qian Sun; Chen Zhao; Yu Wang; Chen-Hua Yan; Xiao-Hui Zhang; Lan-Ping Xu; Kai-Yan Liu; Xiao-Jun Huang (Science China Life Sciences, 2020)

A Facile and Sensitive DNA Sensing of Harmful Algal Blooms Based on Graphene Oxide Nanosheets - Le Qiang; Yu Zhang; Chao Wu; Yingkuan Han; Suchun Wang; Yanyan Wang; Congcong Zhang; Guangzhou Liu; Qi Wu; Hong Liu; Ian R. Jenkinson; Jun Sun; et al. (Marine Biotechnology, 2020)

Long-term influence of maize stover and its derived biochar on soil structure and organo-mineral complexes in Northeast China - Qiang Sun; Jun Meng; Binoy Sarkar; Yu Lan; Li Lin; Haifeng Li; Xu Yang; Tiexin Yang; Wenfu Chen; Hailong Wang (Environmental Science and Pollution Research, 2020)

Expression characteristics of immune factors in secondary lymphoid organs of newborn, juvenile and adult yaks (Bos grunniens) - Yufeng Huang; Yan Cui; Sijiu Yu; Penggang Liu; Jun Liu; Jun-Feng He; Juan Sun (Cell and Tissue Research, 2020)

Mesorhizobium rhizophilum sp. nov., a 1-aminocyclopropane-1-carboxylate deaminase producing bacterium isolated from rhizosphere of maize in Northeast China - Jun-lian Gao; Jing Xue; Yu-chen Sun; Han Xue; En Tao Wang; Hui Yan; Shuai Tong; Li-wei Wang; Xiuhai Zhang; Jian-guang Sun (Antonie van Leeuwenhoek, 2020)

The sorption performance of corroded Gaomiaozi bentonite by evolved cement water at different temperatures: the case of europium removal - Zhao Sun; Yong-gui Chen; Yinghui Shang; Yu-jun Cui; Wei-min Ye; Dong-bei Wu (Environmental Science and Pollution Research, 2020)

Overload type and optimization of meadow carrying capacity in Maqin County in the Three-River Source Region, China - Jin-jin Sun; Peng-bin Wang; Yong-shang Tong; Yuan-yuan Hao; You-long He; Hai-bo Wang; Xiao-jun Yu (Journal of Mountain Science, 2020)

Phytoplankton growth and microzooplankton grazing in the central and northern South China Sea in the spring intermonsoon season of 2017 - Dawei Chen; Congcong Guo; Linhui Yu; Yuanzhen Lu; Jun Sun (Acta Oceanologica Sinica, 2020)

A new methylene bisflavan-3-ol from the branches and leaves of Potentilla fruticosa - Yang Zeng; Yu-Xia Sun; Xiu-Hua Meng; Tao Yu; Hong-Tao Zhu; Ying-Jun Zhang (Natural Product Research, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Naturally Occurring Antibodies to Tau Exists in Human Blood and Are Not Changed in Alzheimer’s Disease - Zhong-Yuan Yu; Wei-Wei Li; Hai-Mei Yang; Noralyn B. Mañucat-Tan; Jun Wang; Ye-Ran Wang; Bin-Lu Sun; Zi-Cheng Hu; Li-Li Zhang; Liang Tan; Juan Deng; Yu-Hui Liu (Neurotoxicity Research, 2020)

Exercise training reduces the risk of opportunistic infections after acute exercise and improves cytokine antigen recognition - Kyung-Wan Baek; Jin-Ok Jo; Yun-Jeong Kang; Kyoung Seob Song; Hak Sun Yu; Jung-Jun Park; Yung Hyun Choi; Hee-Jae Cha; Mee Sun Ock (Pflügers Archiv - European Journal of Physiology, 2020)

Non-motor Symptoms in Parkinson’s Disease Patients with Parkin Mutations: More Depression and Less Executive Dysfunction - Jie Song; Bo Shen; Yu-Jie Yang; Feng-tao Liu; Jue Zhao; Yi-Lin Tang; Chen Chen; Zheng-Tong Ding; Yu An; Jian-Jun Wu; Yi-Min Sun; Jian Wang (Journal of Molecular Neuroscience, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Tumor Microenvironment Stimuli-Responsive Polymeric Prodrug Micelles for Improved Cancer Therapy - Zhiqiang Zhang; Miao Yu; Tong An; Jun Yang; Meijuan Zou; Yinglei Zhai; Wei Sun; Gang Cheng (Pharmaceutical Research, 2020)

Mechanism of CNP-mediated DG-PKC and IP4 signaling pathway in diabetic rats with gastric motility disorder - Hui-Ming Lian; Jun-Yu Guo; Yan Sun; Mo-Han Zhang; Li-Hua Piao; Zheng Jin; Ying-Lan Cai (Molecular Biology Reports, 2020)

Major advances in studies of the physical geography and living environment of China during the past 70 years and future prospects - Fahu Chen; Bojie Fu; Jun Xia; Duo Wu; Shaohong Wu; Yili Zhang; Hang Sun; Yu Liu; Xiaomin Fang; Boqiang Qin; Xin Li; Tingjun Zhang; et al. (Science China Earth Sciences, 2019)

Insights into transcriptional characteristics and homoeolog expression bias of embryo and de-embryonated kernels in developing grain through RNA-Seq and Iso-Seq - Jun Wei; Hong Cao; Jing-dong Liu; Jing-hong Zuo; Yu Fang; Chih-Ta Lin; Run-ze Sun; Wen-long Li; Yong-xiu Liu (Functional & Integrative Genomics, 2019)

In vitro activities of imipenem, vancomycin, and rifampicin against clinical Elizabethkingia species producing BlaB and GOB metallo-beta-lactamases - Tein-Yao Chang; Hsing-Yu Chen; Yu-Ching Chou; Yun-Hsiang Cheng; Jun-Ren Sun (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Host–Symbiont Interactions in Deep-Sea Chemosymbiotic Vesicomyid Clams: Insights From Transcriptome Sequencing - Yi Lan; Jin Sun; Weipeng Zhang; Ting Xu; Yu Zhang; Chong Chen; Dong Feng; Hongbin Wang; Jun Tao; Jian-Wen Qiu; Pei-Yuan Qian (Frontiers in Marine Science, 2019)

Panax notoginsenoside Rb1 Restores the Neurotrophic Imbalance Following Photothrombotic Stroke in Rats - Chun-Yan Yang; Jian-Yu Yang; Yun-Xia Xiong; Xue-Feng Zhuang; Hui Su; Sheng Hu; Jia-Qing Ma; Xin-Fu Zhou; Hai-Yun Luo; Jun Sun (Neurotoxicity Research, 2019)

Selenium Content and/or T-2 Toxin Contamination of Cereals, Soil, and Children’s Hair in Some Areas of Heilongjiang and Gansu Provinces, China - Liyan Sun; Silu Cui; Qing Deng; Hui Liu; Yanhong Cao; Shaoping Wang; Jun Yu (Biological Trace Element Research, 2019)

Antihyperlipidemic glycosides from the root bark of Lycium chinense - Hui Chen; Yu-Jie Li; Yan-Jun Sun; Xiao-Kun Li; Gong Jian-Hong; Ya Wu; Fang-Yi Su; Kun Du; Yan-Li Zhang; Wei-Sheng Feng (Natural Product Research, 2019)

Algicoccus marinus gen. nov. sp. nov., a marine bacterium isolated from the surface of brown seaweed Laminaria japonica - Jun-Jie Ying; Shun-Li Zhang; Chao-Yu Huang; Lin Xu; Zhe Zhao; Min Wu; Cong Sun (Archives of Microbiology, 2019)

Evaluating three satellite-based precipitation products of different spatial resolutions in Shanghai based on upscaling of rain gauge - Weiyue Li; Xiaogang He; Weiwei Sun; Marco Scaioni; Dongjing Yao; Jing Fu; Yu Chen; Bin Liu; Jun Gao; Xin Li; Guodong Cheng (International Journal of Remote Sensing, 2019)

MicroRNAs Involved in the Regulation of LC-PUFA Biosynthesis in Teleosts: miR-33 Enhances LC-PUFA Biosynthesis in Siganus canaliculatus by Targeting insig1 which in Turn Upregulates srebp1 - Jun Jun Sun; Li Guo Zheng; Cui Ying Chen; Jin Ying Zhang; Cui Hong You; Qing Hao Zhang; Hong Yu Ma; Óscar Monroig; Douglas R. Tocher; Shu Qi Wang; Yuan You Li (Marine Biotechnology, 2019)

The Adsorption Behavior of Atrazine in Common Soils in Northeast China - Jing Sun; Xiu-lan Ma; Wen Wang; Jing Zhang; Hao Zhang; Yu-jun Wang; Jun Feng (Bulletin of Environmental Contamination and Toxicology, 2019)

Dietary Intakes of Calcium, Iron, Magnesium, and Potassium Elements and the Risk of Colorectal Cancer: a Meta-Analysis - Yu Meng; Jiantao Sun; Jun Yu; Chunhong Wang; Jianmei Su (Biological Trace Element Research, 2019)

Neurons in rat orbitofrontal cortex and medial prefrontal cortex exhibit distinct responses in reward and strategy-update in a risk-based decision-making task - Dan-Dan Hong; Wen-Qiang Huang; Ai-Ai Ji; Sha-Sha Yang; Hui Xu; Ke-Yi Sun; Aihua Cao; Wen-Jun Gao; Ning Zhou; Ping Yu (Metabolic Brain Disease, 2019)

TaEPFL1, an EPIDERMAL PATTERNING FACTOR-LIKE (EPFL) secreted peptide gene, is required for stamen development in wheat - Qingxu Sun; Jipeng Qu; Yan Yu; Zaijun Yang; Shuhong Wei; Yilei Wu; Jun Yang; Zhengsong Peng (Genetica, 2019)

Diltiazem used as a tacrolimus-sparing agent for treatment of pediatric patients with refractory nephrotic syndrome: a case report and retrospective analysis - Jie-Yu Sun; Ya-Hui Hu; Hong-Li Guo; Xia Jing; Ze-Jun Xu; Fang Sun; Hui-Lei Guo; Xuan-Sheng Ding; Feng Chen; Jing Xu (European Journal of Clinical Pharmacology, 2019)

Protective effect of dihydromyricetin on hyperthermia-induced apoptosis in human myelomonocytic lymphoma cells - Qian-Wen Feng; Zheng-Guo Cui; Yu-Jie Jin; Lu Sun; Meng-Ling Li; Shahbaz Ahmad Zakki; De-Jun Zhou; Hidekuni Inadera (Apoptosis, 2019)

Pathological Modification of TDP-43 in Amyotrophic Lateral Sclerosis with SOD1 Mutations - Gye Sun Jeon; Yu-Mi Shim; Do-Yeon Lee; Jun-Soon Kim; MinJin Kang; So Hyun Ahn; Je-Young Shin; Dongho Geum; Yoon Ho Hong; Jung-Joon Sung (Molecular Neurobiology, 2019)

Refined assessment of heavy metal-associated health risk due to the consumption of traditional animal medicines in humans - Tian-Tian Zuo; Yao-Lei Li; Huai-Zhen He; Hong-Yu Jin; Lei Zhang; Lei Sun; Fei Gao; Qi Wang; Yuan-Jun Shen; Shuang-Cheng Ma; Lang-Chong He (Environmental Monitoring and Assessment, 2019)

β-Glucan induces autophagy in dendritic cells and influences T-cell differentiation - Jun Ding; Yongling Ning; Yu Bai; Ximing Xu; Xiao Sun; Chunjian Qi (Medical Microbiology and Immunology, 2019)

Numerical investigation of effects of “baffles - deceleration strip” hybrid system on rock avalanches - Yu-zhang Bi; Si-ming He; Yan-jun Du; Jie Shan; Shuai-xing Yan; Dong-po Wang; Xin-po Sun (Journal of Mountain Science, 2019)

Macrophage-derived CCL18 promotes osteosarcoma proliferation and migration by upregulating the expression of UCA1 - Yang Su; Yan Zhou; Yuan-jue Sun; Ya-Ling Wang; Jun-yi Yin; Yu-jing Huang; Jian-jun Zhang; Ai-na He; Kun Han; Hui-zhen Zhang; Yang Yao; Xiao-Bin Lv; et al. (Journal of Molecular Medicine, 2019)

Garnet amphibolites from the Ganzi–Litang fault zone, eastern Tibetan Plateau: mineralogy, geochemistry, and implications for evolution of the eastern Palaeo-Tethys Realm - Qiu-Huan Li; Yu-Xiu Zhang; Kai-Jun Zhang; Li-Long Yan; Lu Zeng; Xin Jin; Jin-Feng Sun; Xiao-Yao Zhou; Xian-Chun Tang; Lu Lu (International Geology Review, 2018)

Identification and detection sensitivity of Microcystis aeruginosa from mixed and field samples using MALDI-TOF MS - Li-Wei Sun; Wen-Jing Jiang; Jun-Yi Zhang; Wen-Qian Wang; Yang Du; Hiroaki Sato; Masanobu Kawachi; Ran Yu (Environmental Monitoring and Assessment, 2018)

Confluentibacter flavum sp. nov., Isolated from the Saline Lake - Yu. Li; Xin-Jun Hou; Xia Shen; Shuai-Bo Han; Zhao Ju; Zhe Zhao; Xiao-Yun Yu; Min Wu; Cong Sun (Current Microbiology, 2018)

Petrogenesis and metallogenic implications of Late Mesozoic intrusive rocks in the Tongling region, eastern China: a case study and perspective review - Jiancheng Xie; Yu Wang; Quanzhong Li; Jun Yan; Weidong Sun (International Geology Review, 2018)

Early Cretaceous adakitic rocks in the Anqing region, southeastern China: constraints on petrogenesis and metallogenic significance - Jiancheng Xie; Yu Wang; Quanzhong Li; Jianmin Liu; Jun Yan; Weidong Sun (International Geology Review, 2018)

Review of pre-processing technologies for ice cores - Wen-tao Du; Shi-chang Kang; Xiang Qin; Wei-jun Sun; Yu-lan Zhang; Yu-shuo Liu; Ji-zu Chen (Journal of Mountain Science, 2018)

Optimization of culturing conditions for production of somatic embryos and lignins of Schisandra chinensis (Turcz.) Baill - Dan Sun; Zhenxing wang; Yunfei Yu; Changyu Li; Hongyan Qin; Peilei Xu; Ying Zhao; Yingxue Liu; Yiming Yang; Shutian Fan; Jun Ai (Acta Physiologiae Plantarum, 2018)

Seismic stability analysis of slopes with pre-existing slip surfaces - Li-jun Su; Chang-ning Sun; Fang-wei Yu; Sarfraz Ali (Journal of Mountain Science, 2018)

Ectopic expression of sorbitol-6-phosphate 2-dehydrogenase gene from Haloarcula marismortui enhances salt tolerance in transgenic Arabidopsis thaliana - Jian-jie Gao; Yu-ru Sun; Bo Zhu; Ri-He Peng; Bo Wang; Li-Juan Wang; Zhen-Jun Li; Lei Chen; Quan-Hong Yao (Acta Physiologiae Plantarum, 2018)

Identification of a New Uncompetitive Inhibitor of Adenosine Deaminase from Endophyte Aspergillus niger sp. - Xin-guo Zhang; Jin-wen Liu; Peng Tang; Zi-yu Liu; Guang-Jun Guo; Qiao-Yun Sun; Jian-jun Yin (Current Microbiology, 2018)

Labile organic carbon fractions and carbon pool management index in a 3-year field study with biochar amendment - Xu Yang; Di Wang; Yu Lan; Jun Meng; Linlin Jiang; Qiang Sun; Dianyun Cao; Yuanyuan Sun; Wenfu Chen (Journal of Soils and Sediments, 2018)

Safety, pharmacokinetics, and pharmacodynamics of S-(−)-pantoprazole sodium injections after single and multiple intravenous doses in healthy Chinese subjects - Hui-Wen Jiao; Lu-Ning Sun; Yue-Qi Li; Lei Yu; Hong-Wen Zhang; Mei-Feng Wang; Li-Yuan Yu; Zi-Qing-Yun Yuan; Li-Jun Xie; Juan Chen; Ling Meng; Xue-Hui Zhang; et al. (European Journal of Clinical Pharmacology, 2018)

Alternative oxidase functions in the excess excitation energy-induced resistance to pathogen infection - Qin-zheng Hou; Kun Sun; Ling-yun Jia; Jun-yu Liang; Jia-jia Xie; Li-na Lu; Han-qing Feng; Jing Wen (Biologia, 2018)

MiR-26a functions as a tumor suppressor in ambient particulate matter-bound metal-triggered lung cancer cell metastasis by targeting LIN28B–IL6–STAT3 axis - Yan-Yang Lu; Yi Lin; Dong-Xiao Ding; Shu Su; Qiao-Qiao Chi; You-Chi Zhang; Jian Sun; Xu Zhang; Hui-Min Zhu; Qian-Sheng Huang; Yu-Lang Chi; Guo-Zhu Ye; et al. (Archives of Toxicology, 2018)

Transcriptome Analysis of Cucumber Roots Reveals Key Cold-Resistance Genes Induced by AM Fungi - Jun Ma; Chao Sun; Longqiang Bai; Rongrong Dong; Yan Yan; Xianchang Yu; Chaoxing He; Zhirong Zou; Yansu Li (Plant Molecular Biology Reporter, 2018)

Significance of temperature and water availability for soil phosphorus transformation and microbial community composition as affected by fertilizer sources - Dasheng Sun; Qingfang Bi; Kejie Li; Peibin Dai; Yan Yu; Weiwei Zhou; Ting Lv; Xipeng Liu; Jun Zhu; Qichun Zhang; Chongwei Jin; Lingli Lu; et al. (Biology and Fertility of Soils, 2018)

iTRAQ-based comparative proteomic analysis provides insights into somatic embryogenesis in Gossypium hirsutum L. - Hua-Guo Zhu; Wen-Han Cheng; Wen-Gang Tian; Yang-Jun Li; Feng Liu; Fei Xue; Qian-Hao Zhu; Yu-Qiang Sun; Jie Sun (Plant Molecular Biology, 2018)

Minimally Toxic Dose of Lipopolysaccharide and α-Synuclein Oligomer Elicit Synergistic Dopaminergic Neurodegeneration: Role and Mechanism of Microglial NOX2 Activation - Wei Zhang; Jun-hua Gao; Zhao-fen Yan; Xi-yan Huang; Peng Guo; Li Sun; Zhuo Liu; Yang Hu; Li-jun Zuo; Shu-yang Yu; Chen-Jie Cao; Xiao-min Wang; et al. (Molecular Neurobiology, 2018)

Occurrence of organotins in the aquatic environment during an operating cycle of the Three Gorges Reservoir, China - Jun-min Gao; Xiao-ling Chen; Xiu-qian Sun; Ke Zhang; You-peng Chen; Jin-song Guo; Yu Shen (Environmental Science and Pollution Research, 2018)

Effect of nanoparticle hydroxyapatite on the immobilization of Cu and Zn in polluted soil - Rui-Juan Sun; Jie-Hua Chen; Ting-Ting Fan; Dong-Mei Zhou; Yu-Jun Wang (Environmental Science and Pollution Research, 2018)

Chronic Estradiol Administration During the Early Stage of Alzheimer’s Disease Pathology Rescues Adult Hippocampal Neurogenesis and Ameliorates Cognitive Deficits in Aβ1-42 Mice - Jin-yu Zheng; Ke-shan Liang; Xian-jun Wang; Xue-ying Zhou; Jian Sun; Sheng-nian Zhou (Molecular Neurobiology, 2017)

Down-regulation of Noggin and miR-138 coordinately promote osteogenesis of mesenchymal stem cells - Xing-Kun Sun; Jin Zhou; Lei Zhang; Tian Ma; Yu-Han Wang; Yan-Mei Yang; Yan-Ting Tang; Hong Li; Li-Jun Wang (Journal of Molecular Histology, 2017)

An anti-Propionibacterium acnes antibody shows heterologous resistance to an Actinobacillus pleuropneumoniae infection independent of neutrophils in mice - Jian-fang Liu; Qiu-yue Ma; Ri-ning Zhu; Meng-jun Cheng; Chun-tong Bao; Jing-min Gu; Chang-jiang Sun; Paul Richard Langford; Wen-yu Han; Lian-cheng Lei (Immunologic Research, 2017)

Silymarin inhibits adipogenesis in the adipocytes in grass carp Ctenopharyngodon idellus in vitro and in vivo - Peizhen Xiao; Zhou Yang; Jian Sun; Jingjing Tian; Zhiguang Chang; Xuexian Li; Baotong Zhang; Yuantu Ye; Hong Ji; Ermeng Yu; Jun Xie (Fish Physiology and Biochemistry, 2017)

Nonlinear Rayleigh wave inversion based on the shuffled frog-leaping algorithm - Cheng-Yu Sun; Yan-Yan Wang; Dun-Shi Wu; Xiao-Jun Qin (Applied Geophysics, 2017)

Implications of terminal oxidases in the regulation of soybean photosynthetic performance under different light intensities - Xin Sun; Ming-Jie Liu; Ming-Yan Yang; Jing Lu; Jun-Bo Du; Kai Shu; Xiao-Chun Wang; Wen-Yu Yang (Acta Physiologiae Plantarum, 2017)

OsPPR6, a pentatricopeptide repeat protein involved in editing and splicing chloroplast RNA, is required for chloroplast biogenesis in rice - Jianpeng Tang; Wenwei Zhang; Kai Wen; Gaoming Chen; Juan Sun; Yunlu Tian; Weijie Tang; Jun Yu; Hongzhou An; Tingting Wu; Fei Kong; William Terzaghi; et al. (Plant Molecular Biology, 2017)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Transmission network characteristics based on env and gag sequences from MSM during acute HIV-1 infection in Beijing, China - Zhimin Zhang; Lili Dai; Yan Jiang; Kaidi Feng; Lifeng Liu; Wei Xia; Fengjiao Yu; Jun Yao; Wenge Xing; Lijun Sun; Tong Zhang; Hao Wu; et al. (Archives of Virology, 2017)

A genetic variant in the placenta-derived MHC class I chain-related gene A increases the risk of preterm birth in a Chinese population - Junjiao Song; Jing Li; Han Liu; Yuexin Gan; Yang Sun; Min Yu; Yongjun Zhang; Fei Luo; Ying Tian; Weiye Wang; Jun Zhang; Julian Little; et al. (Human Genetics, 2017)

Assessment of arsenic trioxide toxicity on cock muscular tissue: alterations of oxidative damage parameters, inflammatory cytokines and heat shock proteins - Si-wen Li; Ying Guo; Ying He; Xiao Sun; Hong-jing Zhao; Yu Wang; Ya-jun Wang; Ming-wei Xing (Ecotoxicology, 2017)

Effects of temperature, salinity, diet and stocking density on development of the veined Rapa whelk, Rapana venosa (Valenciennes, 1846) larvae - Tao Zhang; Hao Song; Yu-Cen Bai; Jing-Chun Sun; Xiao-Fang Zhang; Shao-Jun Ban; Zheng-Lin Yu; Mei-Jie Yang; Hai-Yan Wang (Aquaculture International, 2017)

Wheat and barley as banker plant in the mass production of Aphidius gifuensis Ashmead (Hymenoptera: Braconidae) parasitizing Schizaphis graminum Rondani (Homoptera: Aphididae) - Hui Zhong Sun; Xiao Dong Wang; Yu Guo Chen; Hai Tao Wang; Shu Jun Li; Yue Qin Song (Journal of Plant Diseases and Protection, 2017)

Characterization of a Gallid herpesvirus 2 strain with novel reticuloendotheliosis virus long terminal repeat inserts - Yan-ping Zhang; Ke-yan Bao; Guo-rong Sun; Hong-chao Lv; Hong-yu Cui; Yu-long Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2017)

Ginsenoside Reduces Cognitive Impairment During Chronic Cerebral Hypoperfusion Through Brain-Derived Neurotrophic Factor Regulated by Epigenetic Modulation - Qun Wan; Xue Ma; Zhi-Jun Zhang; Ting Sun; Feng Xia; Gang Zhao; Yu-Mei Wu (Molecular Neurobiology, 2017)

Analysis of elastic anisotropy of tight sandstone and the influential factors - Lian-Teng Song; Zhong-Hua Liu; Can-Can Zhou; Jun Yu; Li-Jun Xiu; Zhong-Chun Sun; Hai-Tao Zhang (Applied Geophysics, 2017)

Overexpression of Sorghum WINL1 gene confers drought tolerance in Arabidopsis thaliana through the regulation of cuticular biosynthesis - Shu-Guang Bao; Jian-Xin Shi; Feng Luo; Bo Ding; Jin-Yu Hao; Xiao-Dong Xie; Shou-Jun Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

GWAS analysis of QTL for enteric septicemia of catfish and their involved genes suggest evolutionary conservation of a molecular mechanism of disease resistance - Tao Zhou; Shikai Liu; Xin Geng; Yulin Jin; Chen Jiang; Lisui Bao; Jun Yao; Yu Zhang; Jiaren Zhang; Luyang Sun; Xiaozhu Wang; Ning Li; et al. (Molecular Genetics and Genomics, 2017)

XCI-escaping gene KDM5C contributes to ovarian development via downregulating miR-320a - Yi-Xi Sun; Yi-Xin Zhang; Dan Zhang; Chen-Ming Xu; Song-Chang Chen; Jun-Yu Zhang; Ye-Chun Ruan; Feng Chen; Run-Ju Zhang; Ye-Qing Qian; Yi-Feng Liu; Lu-Yang Jin; et al. (Human Genetics, 2017)

RNAi-Induced Electrophysiological and Behavioral Changes Reveal two Pheromone Binding Proteins of Helicoverpa armigera Involved in the Perception of the Main Sex Pheromone Component Z11–16:Ald - Kun Dong; Liang Sun; Jing-Tao Liu; Shao-Hua Gu; Jing-Jiang Zhou; Ruo-Nan Yang; Khalid Hussain Dhiloo; Xi-Wu Gao; Yu-Yuan Guo; Yong-Jun Zhang (Journal of Chemical Ecology, 2017)

Reactive Oxygen Species-mediated Loss of Phenotype of Parvalbumin Interneurons Contributes to Long-term Cognitive Impairments After Repeated Neonatal Ketamine Exposures - Hui Zhang; Xiao-ru Sun; Jing Wang; Zhen-zhen Zhang; Hong-ting Zhao; Hui-hui Li; Mu-huo Ji; Kuan-yu Li; Jian-jun Yang (Neurotoxicity Research, 2016)

Hierarchy evaluation of water resources vulnerability under climate change in Beijing, China - Xiao-Hua Yang; Bo-Yang Sun; Jian Zhang; Mei-Shui Li; Jun He; Yi-Ming Wei; Yu-Qi Li (Natural Hazards, 2016)

Minocycline ameliorates d-galactose-induced memory deficits and loss of Arc/Arg3.1 expression - Xu Li; Fen Lu; Wei Li; Jun Xu; Xiao-Jing Sun; Ling-Zhi Qin; Qian-Lin Zhang; Yong Yao; Qing-Kai Yu; Xin-Liang Liang (Molecular Biology Reports, 2016)

Changes in anthocyanidin and anthocyanin pigments in highbush blueberry (Vaccinium corymbosum cv. Bluecrop) fruits during ripening - Sun Woo Chung; Duk Jun Yu; Hee Jae Lee (Horticulture, Environment, and Biotechnology, 2016)

Spatial and Vertical Distribution of Dechlorane Plus in Mangrove Sediments of the Pearl River Estuary, South China - Yu-Xin Sun; Zai-Wang Zhang; Xiang-Rong Xu; Qin-Wei Hao; Yong-Xia Hu; Xiao-Bo Zheng; Xiao-Jun Luo; Zeng-Hui Diao; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

The response of Serratia marcescens JG to environmental changes by quorum sensing system - Shu-Jing Sun; Hui-Jun Liu; Cai-Hong Weng; Chun-Fen Lai; Liu-Ying Ai; Yu-Chen Liu; Hu Zhu (Archives of Microbiology, 2016)

Seroprevalence and risk factors of severe fever with thrombocytopenia syndrome virus infection in endemic areas - Yong Lyu; Fan Ding; Jie Sun; Peng-Peng Xu; Jie-Ying Hu; Shao-Yu Xie; Kai-Chun Li; Hong-Wei Chang; Wei Qin; Liang Yu; Hua Xie; Guang-Jiang Li; et al. (Infectious Diseases, 2016)

The Syntheses, Structures, Fluorescence Properties and Biological Activity of two Novel Zinc(II) Complexes Controlled by the Tripodal Imidazole Ligand - En-Jun Gao; Shaozhong Zhang; Yang Meng; Fu-Chen Zhao; Xiao-Yu Ma; Hai-Tao Jin; Si-Jia Liu; Jing Ge; Ya-Guang Sun; Wan-zhong Zhang; Ming-Chang Zhu (Journal of Fluorescence, 2016)

Transcriptome Sequencing of the Sweet Potato Progenitor (Ipomoea Trifida (H.B.K.) G. Don.) and Discovery of Drought Tolerance Genes - Qinghe Cao; Ang Li; Jinyang Chen; Yu Sun; Jun Tang; An Zhang; Zhilin Zhou; Donglan Zhao; Daifu Ma; Shan Gao (Tropical Plant Biology, 2016)

The association between the ring finger protein 213 (RNF213) polymorphisms and moyamoya disease susceptibility: a meta-analysis based on case–control studies - Xun-Sha Sun; Jun Wen; Jiao-Xing Li; Rong Lai; Yu-Fang Wang; Hui-Jiao Liu; Wen-Li Sheng (Molecular Genetics and Genomics, 2016)

Microbial metabolism induced chain shortening of polyacrylamide with assistance of bioelectricity generation - Min Sun; Zhong-Hua Tong; Yu-Zhi Cui; Jun Wang (Environmental Science and Pollution Research, 2016)

Ecological risk assessment of heavy metals in sediment in the upper reach of the Yangtze River - Yu-Jun Yi; Jie Sun; Cai-Hong Tang; Shang-Hong Zhang (Environmental Science and Pollution Research, 2016)

Association mapping and genetic dissection of nitrogen use efficiency-related traits in rice (Oryza sativa L.) - Zhiyi Liu; Chengsong Zhu; Yue Jiang; Yunlu Tian; Jun Yu; Hongzhou An; Weijie Tang; Juan Sun; Jianpeng Tang; Gaoming Chen; Huqu Zhai; Chunming Wang; et al. (Functional & Integrative Genomics, 2016)

Effect of rice panicle size on paddy field CH4 emissions - Yu Jiang; Yunlu Tian; Yanni Sun; Yi Zhang; Xiaoning Hang; Aixi Deng; Jun Zhang; Weijian Zhang (Biology and Fertility of Soils, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

Stoichiometric variation of carbon, nitrogen, and phosphorus in soils and its implication for nutrient limitation in alpine ecosystem of Eastern Tibetan Plateau - Haijian Bing; Yanhong Wu; Jun Zhou; Hongyang Sun; Ji Luo; Jipeng Wang; Dong Yu (Journal of Soils and Sediments, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

Neuroglobin Attenuates Beta Amyloid-Induced Apoptosis Through Inhibiting Caspases Activity by Activating PI3K/Akt Signaling Pathway - Yu Li; Yu-bing Dai; Jie-yun Sun; Yue Xiang; Jun Yang; Song-yang Dai; Xiong Zhang (Journal of Molecular Neuroscience, 2016)

Distinct subcellular localization and potential role of LINE1-ORF1P in meiotic oocytes - Yi-Bo Luo; Li Zhang; Zi-Li Lin; Jun-Yu Ma; Jialin Jia; Suk Namgoong; Qing-Yuan Sun (Histochemistry and Cell Biology, 2016)

Study on the behavior of heavy metals during thermal treatment of municipal solid waste (MSW) components - Jie Yu; Lushi Sun; Ben Wang; Yu Qiao; Jun Xiang; Song Hu; Hong Yao (Environmental Science and Pollution Research, 2016)

Wide-angle incidence and P-wave transmission - Jun-Fa Xie; Cheng-Yu Sun; Mei-Yan Lin; Jing-Jing Li (Applied Geophysics, 2015)

Isoprenaline induces epithelial–mesenchymal transition in gastric cancer cells - Yan-Jie Lu; Zhi-Jun Geng; Xiao-Yan Sun; Yu-Hong Li; Xiao-Bing Fu; Xiang-Yang Zhao; Bo Wei (Molecular and Cellular Biochemistry, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Geographical distribution and risk assessment of persistent organic pollutants in golden threads (Nemipterus virgatus) from the northern South China Sea - Qing Hao; Yu-Xin Sun; Xiang-Rong Xu; Zi-Wei Yao; You-Shao Wang; Zai-Wang Zhang; Xiao-Jun Luo; Bi-Xian Mai (Ecotoxicology, 2015)

The diversity of coral associated bacteria and the environmental factors affect their community variation - Yan-Ying Zhang; Juan Ling; Qing-Song Yang; You-Shao Wang; Cui-Ci Sun; Hong-Yan Sun; Jing-Bin Feng; Yu-Feng Jiang; Yuan-Zhou Zhang; Mei-Lin Wu; Jun-De Dong (Ecotoxicology, 2015)

A Potent Multi-functional Neuroprotective Derivative of Tetramethylpyrazine - Hai-Yun Chen; Da-Ping Xu; Guo-Lian Tan; Wei Cai; Gao-Xiao Zhang; Wei Cui; Jin-Zhao Wang; Cheng Long; Ye-Wei Sun; Pei Yu; Karl Wahkeung Tsim; Zai-Jun Zhang; et al. (Journal of Molecular Neuroscience, 2015)

Hex1-related transcriptome of Trichoderma atroviride reveals expression patterns of ABC transporters associated with tolerance to dichlorvos - Tailong Zhang; Jun Tang; Jianan Sun; Chuanjin Yu; Zhicheng Liu; Jie Chen (Biotechnology Letters, 2015)

Analyses of aerosol optical properties and direct radiative forcing over urban and industrial regions in Northeast China - Huizheng Che; Hujia Zhao; Yunfei Wu; Xiangao Xia; Jun Zhu; Hong Wang; Yaqiang Wang; Junying Sun; Jie Yu; Xiaoye Zhang; Guangyu Shi (Meteorology and Atmospheric Physics, 2015)

DLEC1, a 3p tumor suppressor, represses NF-κB signaling and is methylated in prostate cancer - Lian Zhang; Qian Zhang; LiLi Li; Zhaohui Wang; Jianming Ying; Yu Fan; Qun He; Tianjing LV; Wenke Han; Jun Li; Yang Yang; Ben Xu; et al. (Journal of Molecular Medicine, 2015)

Genes regulating lipid and protein metabolism are highly expressed in mammary gland of lactating dairy goats - Hengbo Shi; Jiangjiang Zhu; Jun Luo; Wenting Cao; Huaiping Shi; Dawei Yao; Jun Li; Yuting Sun; Huifen Xu; Kang Yu; Juan J. Loor (Functional & Integrative Genomics, 2015)

Association between the CYP1A2 polymorphisms and risk of cancer: a meta-analysis - Wen-Xia Sun; Ying-Hua Chen; Zhi-Zhong Liu; Jian-Jun Xie; Wei Wang; Ya-Ping Du; Yu Chen; Xu-Liang Shen; Xiao-Feng He; Li-Xia Wu; Wu Wei; Lin Zhang (Molecular Genetics and Genomics, 2015)

Evaluation of the safety and efficacy of transcatheter aortic valve implantation in patients with a severe stenotic bicuspid aortic valve in a Chinese population - Xian-bao Liu; Ju-bo Jiang; Qi-jing Zhou; Zhao-xia Pu; Wei He; Ai-qiang Dong; Yan Feng; Jun Jiang; Yong Sun; Mei-xiang Xiang; Yu-xin He; You-qi Fan; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Association of Hematocrit and Pre-hypertension Among Chinese Adults: The CRC Study - Xuekui Liu; Jun Liang; Qinqin Qiu; Yan zhu; Yuting Sun; Pei Ying; Fei Teng; Yu Wang; Lu Qi (Cell Biochemistry and Biophysics, 2015)

Comparison of Clinical Outcomes of Anterior Versus Posterior Surgery in Treating Multi-segmental Cervical Degeneration - Qiang Wang; Jun Cai; Yuping Tao; Yu Sun; Xiaolei Li; Zhiqiang Zhang; Yongchao Fang; Jingcheng Wang (Cell Biochemistry and Biophysics, 2015)

Erratum to: Effect of volatile organic compounds absorbed to fresh biochar on survival of Bacillus mucilaginosus and structure of soil microbial communities - Daquan Sun; Jun Meng; Hao Liang; E. Yang; Yuwei Huang; Wenfu Chen; Linlin Jiang; Yu Lan; Weiming Zhang; Jiping Gao (Journal of Soils and Sediments, 2015)

Effect of volatile organic compounds absorbed to fresh biochar on survival of Bacillus mucilaginosus and structure of soil microbial communities - Daquan Sun; Jun Meng; Hao Liang; E. Yang; Yuwei Huang; Wenfu Chen; Linlin Jiang; Yu Lan; Weiming Zhang; Jiping Gao (Journal of Soils and Sediments, 2015)

Phytoplankton and chlorophyll a relationships with ENSO in Prydz Bay, East Antarctica - HaiSheng Zhang; ZhengBing Han; Jun Zhao; PeiSong Yu; ChuanYu Hu; WeiPing Sun; Dan Yang; GenHai Zhu; Bing Lu; Hans-UIrich Peter; Walter Vetter (Science China Earth Sciences, 2014)

Post-stroke pain hypersensitivity induced by experimental thalamic hemorrhage in rats is region-specific and demonstrates limited efficacy of gabapentin - Fei Yang; Han Fu; Yun-Fei Lu; Xiao-Liang Wang; Yan Yang; Fan Yang; Yao-Qing Yu; Wei Sun; Jia-Shuang Wang; Michael Costigan; Jun Chen (Neuroscience Bulletin, 2014)

Analyses on the tectonic thermal evolution and influence factors in the deep-water Qiongdongnan Basin - Zhenfeng Wang; Xiaobin Shi; Jun Yang; Baojia Huang; Zhen Sun; Yahui Wang; Haiyan Jiang; Chuanhai Yu; Xiaoqiu Yang (Acta Oceanologica Sinica, 2014)

Downregulation of Neuregulin 1-ErbB4 Signaling in Parvalbumin Interneurons in the Rat Brain May Contribute to the Antidepressant Properties of Ketamine - Nan Wang; Guang-Fen Zhang; Xiao-Yu Liu; He-Liang Sun; Xing-Ming Wang; Li-Li Qiu; Chun Yang; Jian-Jun Yang (Journal of Molecular Neuroscience, 2014)

Volatiles Emitted from Tea Plants Infested by Ectropis obliqua Larvae Are Attractive to Conspecific Moths - Xiao-Ling Sun; Guo-Chang Wang; Yu Gao; Xin-Zhong Zhang; Zhao-Jun Xin; Zong-Mao Chen (Journal of Chemical Ecology, 2014)

Soil phosphorus bioavailability assessed by XANES and Hedley sequential fractionation technique in a glacier foreland chronosequence in Gongga Mountain, Southwestern China - YanHong Wu; Jörg Prietzel; Jun Zhou; HaiJian Bing; Ji Luo; Dong Yu; ShouQin Sun; JianHong Liang; HongYang Sun (Science China Earth Sciences, 2014)

Generation of a monkey with MECP2 mutations by TALEN-based gene targeting - Zhen Liu; Xue Zhou; Ying Zhu; Zhi-Fang Chen; Bin Yu; Yan Wang; Chen-Chen Zhang; Yan-Hong Nie; Xiao Sang; Yi-Jun Cai; Yue-Fang Zhang; Chen Zhang; et al. (Neuroscience Bulletin, 2014)

Role and Mechanism of Microglial Activation in Iron-Induced Selective and Progressive Dopaminergic Neurodegeneration - Wei Zhang; Zhao-fen Yan; Jun-hua Gao; Li Sun; Xi-yan Huang; Zhuo Liu; Shu-yang Yu; Chen-Jie Cao; Li-jun Zuo; Ze-Jie Chen; Yang Hu; Fang Wang; et al. (Molecular Neurobiology, 2014)

Cloning and identification of a novel thyroid hormone receptor β isoform expressed in the pituitary gland - Rong-Lan Zhao; Bei Sun; Ying Liu; Jing-Hua Li; Wei-Li Xiong; Dong-Chun Liang; Gang Guo; Ai-Jun Zuo; Jing-Yu Zhang (Molecular and Cellular Biochemistry, 2014)

Fluid inclusion and isotope geochemistry of the Yangla copper deposit, Yunnan, China - Xi-An Yang; Jia-Jun Liu; Long-Bo Yang; Si-Yu Han; Xiao-Ming Sun; Huan Wang (Mineralogy and Petrology, 2014)

Induction of autophagy-dependent cell death by the survivin suppressant YM155 in salivary adenoid cystic carcinoma - Yu-Fan Wang; Wei Zhang; Ke-Fei He; Bing Liu; Lu Zhang; Wen-Feng Zhang; Ashok B. Kulkarni; Yi-Fang Zhao; Zhi-Jun Sun (Apoptosis, 2014)

Sex identification and genetic variation of Saccharina (Phaeophyta) gametophytes as revealed by inter-simple sequence repeat (ISSR) markers - Jun-Gang Gu; Yu-Ping Sun; Yu Liu; Yan-Hui Bi; Zhi-Gang Zhou (Journal of Applied Phycology, 2014)

Perception of potential sex pheromones and host-associated volatiles in the cotton plant bug, Adelphocoris fasciaticollis (Hemiptera: Miridae): morphology and electrophysiology - Liang Sun; Hai-Jun Xiao; Shao-Hua Gu; Yu-Yuan Guo; Ze-Wen Liu; Yong-Jun Zhang (Applied Entomology and Zoology, 2014)

Endogenous viral elements in algal genomes - Liang Wang; Shuangxiu Wu; Tao Liu; Jing Sun; Shan Chi; Cui Liu; Xingang Li; Jinlong Yin; Xumin Wang; Jun Yu (Acta Oceanologica Sinica, 2014)

Comparative analysis of four essential Gracilariaceae species in China based on whole transcriptomic sequencing - Jiayue Xu; Jing Sun; Jinlong Yin; Liang Wang; Xumin Wang; Tao Liu; Shan Chi; Cui Liu; Lufeng Ren; Shuangxiu Wu; Jun Yu (Acta Oceanologica Sinica, 2014)

De novo sequencing and comparative analysis of three red algal species of Family Solieriaceae to discover putative genes associated with carrageenan biosysthesis - Lipu Song; Shuangxiu Wu; Jing Sun; Liang Wang; Tao Liu; Shan Chi; Cui Liu; Xingang Li; Jinlong Yin; Xumin Wang; Jun Yu (Acta Oceanologica Sinica, 2014)

Comparative analysis on transcriptome sequencings of six Sargassum species in China - Guoliang Wang; Jing Sun; Guiming Liu; Liang Wang; Jun Yu; Tao Liu; Shan Chi; Cui Liu; Haiyan Guo; Xumin Wang; Shuangxiu Wu (Acta Oceanologica Sinica, 2014)

Analysis of Saccharina japonica transcriptome using the high-throughput DNA sequencing technique and its vanadium-dependent haloperoxidase gene - Xiayuan Liang; Xumin Wang; Shan Chi; Shuangxiu Wu; Jing Sun; Cui Liu; Shengping Chen; Jun Yu; Tao Liu (Acta Oceanologica Sinica, 2014)

Transcriptome characterization of Ishige okamurae (Phaeophyceae) shows strong environmental acclimation - Jieqiong Qu; Xumin Wang; Shan Chi; Shuangxiu Wu; Jing Sun; Cui Liu; Shengping Chen; Jun Yu; Tao Liu (Acta Oceanologica Sinica, 2014)

Transcriptome-wide evolutionary analysis on essential brown algae (Phaeophyceae) in China - Jing Sun; Liang Wang; Shuangxiu Wu; Xumin Wang; Jingfa Xiao; Shan Chi; Cui Liu; Lufeng Ren; Yuhui Zhao; Tao Liu; Jun Yu (Acta Oceanologica Sinica, 2014)

Transcriptome sequencing of essential marine brown and red algal species in China and its significance in algal biology and phylogeny - Shuangxiu Wu; Jing Sun; Shan Chi; Liang Wang; Xumin Wang; Cui Liu; Xingang Li; Jinlong Yin; Tao Liu; Jun Yu (Acta Oceanologica Sinica, 2014)

Phylogenomic analysis of transcriptomic sequences of mitochondria and chloroplasts of essential brown algae (Phaeophyceae) in China - Shangang Jia; Xumin Wang; Tianyong Li; Hao Qian; Jing Sun; Liang Wang; Jun Yu; Lufeng Ren; Jinlong Yin; Tao Liu; Shuangxiu Wu (Acta Oceanologica Sinica, 2014)

Phylogenomic analysis of transcriptomic sequences of mitochondria and chloroplasts for marine red algae (Rhodophyta) in China - Shangang Jia; Xumin Wang; Hao Qian; Tianyong Li; Jing Sun; Liang Wang; Jun Yu; Xingang Li; Jinlong Yin; Tao Liu; Shuangxiu Wu (Acta Oceanologica Sinica, 2014)

Activation of BKCa Channels Mediates Hippocampal Neuronal Death After Reoxygenation and Reperfusion - Ming Chen; Hong-Yu Sun; Ping Hu; Chun-Fei Wang; Bo-Xing Li; Shu-Ji Li; Jian-Jun Li; Hui-Ying Tan; Tian-Ming Gao (Molecular Neurobiology, 2013)

Comprehensive screening for multi-class veterinary drug residues and other contaminants in muscle using column-switching UPLC-MS/MS - Jia Zhan; Di-ming Xu; Shi-jie Wang; Ji Sun; Yin-jun Xu; Mei-lin Ni; Ju-yi Yin; Jie Chen; Xue-jun Yu; Zhi-qiang Huang (Food Additives & Contaminants: Part A, 2013)

Seasonally variable intestinal metagenomes of the red palm weevil ( R hynchophorus ferrugineus ) - Shangang Jia; Xiaowei Zhang; Guangyu Zhang; An Yin; Sun Zhang; Fusen Li; Lei Wang; Duojun Zhao; Quanzheng Yun; Tala; Jixiang Wang; Gaoyuan Sun; et al. (Environmental Microbiology, 2013)
Summary The intestinal microbes residing in the red palm weevil ( RPW , R hynchophorus ferrugineus ) larva consume tender interior fibrous tissues of date palm trunks. The understanding of such microbiota at molecular level provides vital clues for the biological control of this devastating pest. Using pyrosequencing and shotgun strategy, we first study taxonomic profiles of the microbiota sampled at different months ( M arch, J uly and N ovember), and then confirm the impact of high‐temperature stress on the microbial populations based on data from 16S rRNA amplicons using both field and laboratory samples. We further identify K lebsiella pneumoniae in N ovember and L actococcus lactis in J uly as the dominant species of the microbiota. We find that the RPW gut microbiota degrades polysaccharides and sucrose with hydrolases and that different active bacterial species in N ovember and J uly are responsible for the symbiotic relationship between the microbiota and the host. Our results provide vital information for pest control and cellulolytic bacterial species characterization.

Geochronological and geochemical constraints on the Erguna massif basement, NE China – subduction history of the Mongol–Okhotsk oceanic crust - De-You Sun; Jun Gou; Tian-Hao Wang; Yun-Sheng Ren; Yong-Jiang Liu; Hong-Yu Guo; Xiao-Ming Liu; Zhao-Chu Hu (International Geology Review, 2013)

The short chain cell-permeable ceramide (C6) restores cell apoptosis and perifosine sensitivity in cultured glioblastoma cells - Li-sen Qin; Zheng-quan Yu; Shi-ming Zhang; Guan Sun; Jian Zhu; Jin Xu; Jun Guo; Lin-shan Fu (Molecular Biology Reports, 2013)

Identification of human patatin-like phospholipase domain-containing protein 1 and a mutant in human cervical cancer HeLa cells - Ping-An Chang; Ying-Jian Sun; Fei-Fei Huang; Wen-Zhen Qin; Yu-Ying Chen; Xin Zeng; Yi-Jun Wu (Molecular Biology Reports, 2013)

Identification and Field Evaluation of Non-Host Volatiles Disturbing Host Location by the Tea Geometrid, Ectropis obliqua - Zheng-qun Zhang; Xiao-ling Sun; Zhao-jun Xin; Zong-xiu Luo; Yu Gao; Lei Bian; Zong-mao Chen (Journal of Chemical Ecology, 2013)

Dynamic expression profiles of MMPs/TIMPs and collagen deposition in mechanically unloaded rat heart: implications for left ventricular assist device support-induced cardiac alterations - Lu Wang; Yu-Xian Xu; Xiao-Jie Du; Quan-Ge Sun; Ying-Jun Tian (Journal of Physiology and Biochemistry, 2013)

Identification of the proteins in green cotton fiber using a proteomics-based approach - Yan-Jun Li; Fu-Xin Wang; Ya-Qin Wang; Yong-Chang Liu; Xin-Yu Zhang; Yu-Qiang Sun; Jie Sun (Biotechnology Letters, 2013)

The Preferential Binding of a Sensory Organ Specific Odorant Binding Protein of the Alfalfa Plant Bug Adelphocoris lineolatus AlinOBP10 to Biologically Active Host Plant Volatiles - Liang Sun; Shao-Hua Gu; Hai-Jun Xiao; Jing-Jiang Zhou; Yu-Yuan Guo; Ze-Wen Liu; Yong-Jun Zhang (Journal of Chemical Ecology, 2013)

Spatial-temporal characteristics of epidemic spread in-out flow—Using SARS epidemic in Beijing as a case study - BiSong Hu; JianHua Gong; JiePing Zhou; Jun Sun; LiYang Yang; Yu Xia; Abdoul Nasser Ibrahim (Science China Earth Sciences, 2013)

β-Glucanase specific expression in the parotid gland of transgenic mice - Li-zheng Guan; Yu-ping Sun; Qian-yun Xi; Jing-lan Wang; Jun-yun Zhou; Gang Shu; Qing-yan Jiang; Yong-liang Zhang (Transgenic Research, 2013)

Environmental connections of novel avian-origin H7N9 influenza virus infection and virus adaptation to the human - Jun Li; XinFen Yu; XiaoYing Pu; Li Xie; YongXiang Sun; HaiXia Xiao; FenJuan Wang; Hua Din; Ying Wu; Di Liu; GuoQiu Zhao; Jun Liu; et al. (Science China Life Sciences, 2013)

Effect of Fluoride and Low versus High Levels of Dietary Calcium on mRNA Expression of Osteoprotegerin and Osteoprotegerin Ligand in the Bone of Rats - Jun Yu; Yanhui Gao; Dianjun Sun (Biological Trace Element Research, 2013)

Mitochondrial genome sequences of Artemia tibetiana and Artemia urmiana: assessing molecular changes for high plateau adaptation - HangXiao Zhang; QiBin Luo; Jing Sun; Fei Liu; Gang Wu; Jun Yu; WeiWei Wang (Science China Life Sciences, 2013)

Paenibacillus brassicae sp. nov., isolated from cabbage rhizosphere in Beijing, China - Miao Gao; Hui Yang; Ji Zhao; Jun Liu; Yan-hua Sun; Yu-jiong Wang; Jian-guang Sun (Antonie van Leeuwenhoek, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Destrin deletion enhances the bone loss in hindlimb suspended mice - Feng Shuang; Yu Sun; Huai-He Yang; Yin-Chu Shao; Hao Li; Wei Hu; Jun Zhong; Hong-Xing Zou (European Journal of Applied Physiology, 2013)

Phosphorus biogeochemical cycle research in mountainous ecosystems - Yan-hong Wu; Jun Zhou; Dong Yu; Shou-qin Sun; Ji Luo; Hai-jian Bing; Hong-yang Sun (Journal of Mountain Science, 2013)

Evaluation of a DNA vaccine candidate co-expressing GP3 and GP5 of porcine reproductive and respiratory syndrome virus (PRRSV) with interferon α/γ in immediate and long-lasting protection against HP-PRRSV challenge - Yijun Du; Jing Qi; Yu Lu; Jiaqiang Wu; Dongwan Yoo; Xing Liu; Xiumei Zhang; Jun Li; Wenbo Sun; Xiaoyan Cong; Jianli Shi; Jinbao Wang (Virus Genes, 2012)

EBHU18, a novel derivative of fatty acid bile acid conjugates, prevents cholesterol gallstone formation in experimental mice - Lei Yu; Yan-Fang Jiang; Lei Sun; Bo-Hua Zhong; Jun-Qi Niu (Medicinal Chemistry Research, 2012)

Does glyphosate impact on Cu uptake by, and toxicity to, the earthworm Eisenia fetida? - Chui-Fan Zhou; Yu-Jun Wang; Yuan-Chun Yu; Rui-Juan Sun; Xiang-Dong Zhu; Hai-Lin Zhang; Dong-Mei Zhou (Ecotoxicology, 2012)

Multi-environment mapping and meta-analysis of 100-seed weight in soybean - Ya-nan Sun; Jun-bo Pan; Xiang-lin Shi; Xiang-yu Du; Qiong Wu; Zhao-ming Qi; Hong-wei Jiang; Da-wei Xin; Chun-yan Liu; Guo-hua Hu; Qing-shan Chen (Molecular Biology Reports, 2012)

Beta2-Adrenergic Receptor and Astrocyte Glucose Metabolism - Jun-hong Dong; Xin Chen; Min Cui; Xiao Yu; Qi Pang; Jin-peng Sun (Journal of Molecular Neuroscience, 2012)

Large-scale collection and annotation of gene models for date palm (Phoenix dactylifera, L.) - Guangyu Zhang; Linlin Pan; Yuxin Yin; Wanfei Liu; Dawei Huang; Tongwu Zhang; Lei Wang; Chengqi Xin; Qiang Lin; Gaoyuan Sun; Mohammed M. Ba Abdullah; Xiaowei Zhang; et al. (Plant Molecular Biology, 2012)

Mutation spectrum of the GATA4 gene in patients with idiopathic atrial fibrillation - Jun Wang; Yu-Min Sun; Yi-Qing Yang (Molecular Biology Reports, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

Polymorphisms in luteinizing hormone receptor and hypothalamic gonadotropin-releasing hormone genes and their effects on sperm quality traits in Chinese Holstein bulls - Li-Ping Sun; Qing-Zhi Du; Ya-Pan Song; Jun-Na Yu; Shu-Juan Wang; Lei Sang; Luo-Wen Song; Yao-Min Yue; Yu-Ze Lian; Sheng-Li Zhang; Guo-Hua Hua; Shu-Jun Zhang; et al. (Molecular Biology Reports, 2012)

High-throughput sequencing-based gene profiling on multi-staged fruit development of date palm (Phoenix dactylifera, L.) - Yuxin Yin; Xiaowei Zhang; Yongjun Fang; Linlin Pan; Gaoyuan Sun; Chengqi Xin; Mohammed M. Ba Abdullah; Xiaoguang Yu; Songnian Hu; Ibrahim S. Al-Mssallem; Jun Yu (Plant Molecular Biology, 2012)

Co-expression and Synergism Analysis of Vip3Aa29 and Cyt2Aa3 Insecticidal Proteins from Bacillus thuringiensis - Xiumei Yu; Tao Liu; Zhiguang Sun; Peng Guan; Jun Zhu; Shiquan Wang; Shuangcheng Li; Qiming Deng; Lingxia Wang; Aiping Zheng; Ping Li (Current Microbiology, 2012)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)

TP53 codon 72 polymorphism and colorectal cancer susceptibility: a meta-analysis - Jing-Jun Wang; Yuan Zheng; Liang Sun; Li Wang; Peng-Bo Yu; Jian-Hua Dong; Lei Zhang; Jing Xu; Wei Shi; Yu-Chun Ren (Molecular Biology Reports, 2011)

A new QTL for resistance to Fusarium ear rot in maize - Zhi-Min Li; Jun-Qiang Ding; Rui-Xia Wang; Jia-Fa Chen; Xiao-Dong Sun; Wei Chen; Wei-Bin Song; Hua-Fang Dong; Xiao-Dong Dai; Zong-Liang Xia; Jian-Yu Wu (Journal of Applied Genetics, 2011)

Structural Characterization of Extracellular Polysaccharides Produced by the Marine Fungus Epicoccum nigrum JJY-40 and Their Antioxidant Activities - Hai-Hong Sun; Wen-Jun Mao; Jie-Ying Jiao; Jia-Chao Xu; Hong-Yan Li; Yin Chen; Xiao-Hui Qi; Yan-Li Chen; Jian Xu; Chun-Qi Zhao; Yu-Jiao Hou; Yu-Pin Yang (Marine Biotechnology, 2011)

Unusual CT Hyperattenuating Dermoid Cyst of Cerebellum: A New Case Report and Literature Review - Zhao-Jian Li; Yuan-Xin Miao; Peng Sun; Yu-Jun Li; Yi-He Dou; Jian Xu; Xin Chen; Yun-Xia Jiang (The Cerebellum, 2011)

Atmospheric deposition of Cd accumulated in the montane soil, Gongga Mt., China - Yanhong Wu; Haijian Bin; Jun Zhou; Ji Luo; Dong Yu; Shouqin Sun; Wei Li (Journal of Soils and Sediments, 2011)

An uPA cleavable conjugate of a recombinant αvβ3 targeting toxin and its bioactivity - Wen He Zhu; Yu Lai Zhou; De Jun Sun; Zhi Wei Li (World Journal of Microbiology and Biotechnology, 2011)

Molecular characterization and expression analysis of elongation factors 1A and 2 from the Pacific white shrimp, Litopenaeus vannamei - Lei Wang; Yuan Liu; Wei-Na Wang; Wei-Jun Mai; Yu Xin; Jun Zhou; Wen-Yin He; An-Li Wang; Ru-Yong Sun (Molecular Biology Reports, 2011)

Identification and characterization of class I chitinase in Panax ginseng C. A. Meyer - Rama Krishna Pulla; Ok Ran Lee; Jun-Gyo In; Shohana Parvin; Yu-Jin Kim; Ju-Sun Shim; Hua Sun; Yeon-Ju Kim; Kalaiselvi Senthil; Deok-Chun Yang (Molecular Biology Reports, 2011)

Acetylcholine prevents angiotensin II-induced oxidative stress and apoptosis in H9c2 cells - Jin-Jun Liu; Dong-Ling Li; Juan Zhou; Lei Sun; Ming Zhao; Shan-Shan Kong; You-Hua Wang; Xiao-Jiang Yu; Jun Zhou; Wei-Jin Zang (Apoptosis, 2011)

Effect of blue light on indoor seedling culture of Saccharina japonica (Phaeophyta) - Wen-Jun Wang; Xiu-Tao Sun; Guang-Ce Wang; Pu Xu; Xiang-Yu Wang; Zhe-Long Lin; Fei-Jiu Wang (Journal of Applied Phycology, 2010)

Isolation and characterization of a Glutamate decarboxylase (GAD) gene and their differential expression in response to abiotic stresses from Panax ginseng C. A. Meyer - Jung-Hye Lee; Yu-Jin Kim; Dae-Young Jeong; Gayathri Sathiyaraj; Rama Krishna Pulla; Ju-Sun Shim; Jun-Gyo In; Deok-Chun Yang (Molecular Biology Reports, 2010)

DNA barcoding provides distinction between Radix Astragali and its adulterants - HaiYan Guo; WeiWei Wang; Ning Yang; BaoLin Guo; Sun Zhang; RuiJing Yang; Ye Yuan; JunLin Yu; SongNian Hu; QiShi Sun; Jun Yu (Science China Life Sciences, 2010)

Diversity of culturable actinobacteria from Qinghai–Tibet plateau, China - Yu-Qin Zhang; Hong-Yu Liu; Jie Chen; Li-Jie Yuan; Wei Sun; Li-Xin Zhang; Yue-Qin Zhang; Li-Yan Yu; Wen-Jun Li (Antonie van Leeuwenhoek, 2010)

Proteomic Analysis of Interactions Between the Generalist Herbivore Spodoptera exigua (Lepidoptera: Noctuidae) and Arabidopsis thaliana - Ju-Hong Zhang; Li-Wen Sun; Lin-Lin Liu; Jie Lian; Shao-Li An; Xu Wang; Jing Zhang; Jun-Ling Jin; Shan-Yu Li; Jing-Hui Xi (Plant Molecular Biology Reporter, 2010)

Beneficial effects of the ethanol extract from the dry matter of a culture broth of Inonotus obliquus in submerged culture on the antioxidant defence system and regeneration of pancreatic β-cells in experimental diabetes in mice - Hong-Yu Xu; Jun-En Sun; Zhen-Ming Lu; Xiao-Mei Zhang; Wen-Fang Dou; Zheng-Hong Xu (Natural Product Research, 2010)

Phenotypic and molecular characterization of two novel CTX-M enzymes carried by Klebsiella pneumoniae - Jun Cheng; Wei Gao; Jun Yin; Zhen Sun; Ying Ye; Yu-Feng Gao; Xu Li; Jia-Bin Li (Molecular Biology Reports, 2010)

Exercise benefits cardiovascular health in hyperlipidemia rats correlating with changes of the cardiac vagus nerve - You-Hua Wang; Hao Hu; Sheng-Peng Wang; Zhen-Jun Tian; Quan-Jiang Zhang; Qiu-Xia Li; You-You Li; Xiao-Jiang Yu; Lei Sun; Dong-Ling Li; Bing Jia; Bing-Hang Liu; et al. (European Journal of Applied Physiology, 2010)

Synthesis and Fluorescence Properties of Lanthanide (III) Perchlorate Complexes with Naphthyl-Naphthalinesulphonylpropyl Sulfoxide - Wen-Xian Li; Yu-Shan Zheng; Xiao-Jun Sun; Xiao-Yan Shi; Wen-Juan Chai; Tie Ren (Journal of Fluorescence, 2010)

Estrogen Regulation of the Neprilysin Gene Through A Hormone-Responsive Element - Zhi-Min Xiao; Li Sun; Yu-Min Liu; Jun-Jian Zhang; Jian Huang (Journal of Molecular Neuroscience, 2009)

Isolation of S-adenosyl-L-methionine synthetase gene from Panax ginseng C.A. meyer and analysis of its response to abiotic stresses - Rama Krishna Pulla; Yu-Jin Kim; Shohana Parvin; Ju-Sun Shim; Jung-Hye Lee; Yeon-Ju Kim; Jun-Gyo In; Kalai Selvi Senthil; Deok-Chun Yang (Physiology and Molecular Biology of Plants, 2009)

Epigallocatechin-3-gallate affects the growth of LNCaP cells via membrane fluidity and distribution of cellular zinc - Jun-guo Yang; Hai-ning Yu; Shi-li Sun; Lan-cui Zhang; Guo-qing He; Undurti N. Das; Hui Ruan; Sheng-rong Shen (Journal of Zhejiang University-SCIENCE B, 2009)

Osteogenic differentiation of mesenchymal stem cells promoted by overexpression of connective tissue growth factor - Jin-jing Wang; Feng Ye; Li-jia Cheng; Yu-jun Shi; Ji Bao; Huai-qiang Sun; Wei Wang; Peng Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2009)

Human mesenchymal stem cells-like cells as cellular vehicles for delivery of immunotoxin in vitro - Chang-chen Hu; Yi-quan Ke; Xin-lin Sun; Xiao-dan Jiang; Ru-xiang Xu; Jun Lv; Yu-sheng Wang; Ying-qian Cai; Ling-sha Qin; Yu-xi Zou (Biotechnology Letters, 2009)

Occurrence of Fumonisin B1 in Corn from the Main Corn-Producing Areas of China - Hui-Zhi Gong; Rong Ji; Yan-Xi Li; Hong-Yu Zhang; Bing Li; Yue Zhao; Lin Sun; Fei Yu; Jun Yang (Mycopathologia, 2009)

Isolation and Characterization of a Glutaredoxin Gene from Panax ginseng C. A. Meyer - Yu-Jin Kim; Ju-Sun Shim; Pulla Rama Krishna; Se-Young Kim; Jun-Gyo In; Myung-Kyum Kim; Deok-Chun Yang (Plant Molecular Biology Reporter, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Isolation and identification of an arginine deiminase producing strain Pseudomonas plecoglossicida CGMCC2039 - Yong-Mei Liu; Zhi-Hao Sun; Ye Ni; Pu Zheng; Yu-Peng Liu; Fan-Jun Meng (World Journal of Microbiology and Biotechnology, 2008)

Transgenic Bacillus thuringiensis (Bt) cotton (Gossypium hirsutum) allomone response to cotton aphid, Aphis gossypii, in a closed-dynamics CO2 chamber (CDCC) - Gang Wu; Fa Jun Chen; Feng Ge; Yu-Cheng Sun (Journal of Plant Research, 2007)

Involvement of PDCD5 in the regulation of apoptosis in fibroblast-like synoviocytes of rheumatoid arthritis - Ning Wang; Hou-Shan Lu; Zhen-Peng Guan; Tie-Zheng Sun; Ying-Yu Chen; Guo-Rui Ruan; Zhan-Kun Chen; Jun Jiang; Chu-Jie Bai (Apoptosis, 2007)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)